Dictamnine reduces chondrocyte ferroptosis and alleviates osteoarthritis through the HIF-1α/HO-1 pathway - Zezhong Guo; Wenwei Li; Yang Liu; Ming Wei; Zhichao Yang; Zhaoyu Li; Liang Yan; Yang Lu; Zujian Huang; Weiyu Jiang; Wei Huang (Tissue and Cell, 2027)

Structure-based virtual screening identifies dicoumarol as a potent InhA inhibitor against Nocardia seriolae infection in largemouth bass (Micropterus salmoides) - Jin-Lai Gu; Chen-Wang Lu; Lin-Feng Kuang; Jie He; Zheng-Ran Jian; Yuan-Chang Gao; Sheng Lian; Shang-Jie Bai; Zheng-Yang Zhou; Ming-Zhu Liu; Peng-Fei Li; Er-Long Wang; et al. (Aquaculture, 2027)

Investigating frozen strength characteristics and their relationship with microscopic pore structure of chloride silty clay improved by cement - Ya Lu; Ting Zhang; Ping Yang; Lin Li; Ming Zhong; Yaqin Zhang; Xin Shi (European Journal of Environmental and Civil Engineering, 2026)

Freeze-thaw-induced greenhouse gas emissions from a Mollisol agroecosystem: Microbial and edaphic regulation under long-term agricultural management - Dan-Dan Wang; Shan-Shan Dai; Peng He; Zhi-Ming Zhang; Jian-Ying Zhou; Ming-Hui Liu; Shi-Xiu Zhang; Lu-Jun Li (Soil and Tillage Research, 2026)

Endogenous 6-phospho-β-glucosidase overexpression in Lactiplantibacillus plantarum modulates selective enrichment of bioactive and volatile metabolites in black tea extract - Yao-Zeng Zhang; Zhi-Peng Cheng; Pei-Yi Feng; Xin-Xin Liu; Rui-Shan Liu; Zhen-Ming Lu; Li-Juan Chai; Hong-Yu Xu; Jin-Song Shi; Xiao-Juan Zhang; Zheng-Hong Xu (Food Microbiology, 2026)

Beyond direct pathway engineering: reprogramming Fusarium fujikuroi from a GA3 producer into a GA4+7 factory - Hang Xiao; Tao-Xu Lu; Ming-Han Li; Ya-Ling Yi; Hao-Yang Li; Yu-Ke Cen; Zhi-Qiang Liu; Yug-Guo Zheng (Bioresource Technology, 2026)

Recharge sources and genesis of underground brines in the Mahai Basin, Qaidam Basin, China: insights from hydrochemistry and multi-isotope tracers - Ruibo Liu; Xiwei Qin; Wenquan Lu; Haiyan Shi; Zhen Shi; Chenglin Liu; Ying Ma; Xiangjun Li; Sha Yang; Ziwen Jiang; Genhou Wang; Ming Ma; et al. (Carbonates and Evaporites, 2026)

Beyond gastroenteritis: first evidence of systemic biochemical disturbances, predominantly coagulation dysfunction, in Neoboletus poisoning - Jia Li; Yuan-Tian Lu; Xiu-Juan Li; Ming Li; Ping Wei; Tai-Jie Yu; Yu-Xian Gao; Ting Li; Yuan-Yuan Xiong; Yi Liu; Li-Ping Tang (Toxicon, 2026)

Petrogenesis of the middle Jurassic Luorong syenite and Xishan A-type granite in the southern Qin-Hang belt, South China: Implications for contrasting mixed sources and divergent differentiation pathways - Zheng-Wei Qin; Xi-Yao Li; Wolfgang Siebel; Jian-Ming Fu; Sanzhong Li; You-Yue Lu; Yu-Xiao Yao; Yu-Shuai Yu; Bo Bao (Journal of Asian Earth Sciences, 2026)

Correlating gas diffusion layer properties, mass transport, and performance in proton exchange membrane fuel cells at the near-boiling temperature - Shengnan Xu; Yirui Lu; Daijun Yang; Bing Li; Pingwen Ming; Xiangmin Pan (Fuel, 2026)

Thermal-induced tapioca starch/yeast protein composite gels for texture-modified food design: effect of component ratio on gel strength, viscoelasticity and microstructure of protein-filled starch network - Zhiyu Zou; Yiqian Yang; Jieling Chen; Ming Du; Keke Lu; Yaqiu Kong; Xuxu Li; Qilin Huang (Food Research International, 2026)

Vessel-derived metal ions catalyze the accumulation of representative aging markers in multi-round Jiang-flavor base liquor - Wei Zhang; Shi-Yi Wang; Man-Si Niu; Zhen-Ming Lu; Li-Juan Chai; Hong-Yu Xu; Rong-Kun Tu; Song-Tao Wang; Cai-Hong Shen; Jun-Jie Jia; Xiao-Juan Zhang; Zheng-Hong Xu (Food Research International, 2026)

Benzimidazole functionalization enables efficient multi-resonance TADF with accelerated spin-flipping and balanced charge transport - Ji-Hua Tan; Si-Wei Chen; Xin-Lu Li; Han-Nan Shi; Xiao-Long Liu; Yao-Zu Su; Xiaofeng Wang; Jun-Hua Zhuang; Chengxiang Shi; Jia-Ming Jin; Shaoyun Yin; Jia-Xiong Chen; et al. (Chemical Engineering Journal, 2026)

Spatiotemporal temperature trajectories underpin predictive modeling of microbial succession in single-batch high-temperature daqu solid-state fermentation - Jun-Jie Fu; Wei Shi; Han-Jun Shen; Sheng-Bing Yang; Bo Ren; Rong-Ze Ren; Xiao-Juan Zhang; Li-Juan Chai; Hong-Yu Xu; Jin-Song Shi; Song-Tao Wang; Su-Yi Zhang; et al. (Bioresource Technology, 2026)

The progressive formation process of the tectono-metamorphic mélange belt: An example from the Mogutai massif, Dunhuang Orogenic Belt, Northwest China - Yichao Chen; Xue-Li Jia; Qian W.L. Zhang; Zhen M.G. Li; Hui C.G. Zhang; Hao Wang; Wenjiao Xiao; Yan-Lin Zhao; Haiquan Tang; Chang-Ming Lu; Chun-Ming Wu (Journal of Structural Geology, 2026)

Unraveling the anti-listerial activity of noni fruit essential oil: Omics-based mechanistic insights and application in salmon preservation - Qiongping Hong; Jiamu Kang; Xinyu Li; Shanshan Zheng; Ming Yang; Lin Zhang; Yuyun Lu (International Journal of Food Microbiology, 2026)

Integrating ecological networks and metagenomics to decipher core microbial drivers of organic acid metabolism during heaped fermentation of sauce-flavor Baijiu - Hong-Yan Zhang; Ting-Cai Huang; Li-Juan Chai; Wei Shi; Yang-Xue He; Zhen-Ming Lu; Xiao-Juan Zhang; Song-Tao Wang; Cai-Hong Shen; Jin-Song Shi; Zheng-Hong Xu (Food Research International, 2026)

Decoding the thermocyclic solar-driven fermentation: Multi-omics insights into microbial and metabolic dynamics of traditional Chishui river basin soy sauce - Wei-Qin Deng; Zhen-Ming Lu; Xiong-Bo Li; Zhi-Yi Fan; Ting Li; Xiao-Juan Zhang; Li-Juan Chai; Hong-Yu Xu; Qi-Sheng Zhang; Jin-Song Shi; Gong Chen; Zheng-Hong Xu (Food Chemistry, 2026)

Molecular hydrogen mitigates hydroxyl radical–driven oxidative deterioration of tilapia myofibrillar proteins: through the lens of redox microenvironment modulation - Zhuo-Feng Gan; Jia-Ying Li; Ying-Zhi Yao; Hui-Min Lu; Xi-Yang Chen; Ming-Shen Zhu; Duried Alwazeer; Xin-An Zeng; Lan Liao (Food Chemistry, 2026)

Constructing a PANI/MnO2-x@PP photothermal membrane for high-performance solar-driven water purification and energy harvesting - Jian Peng; Hao Li; Yuxin Wang; Yifan Ma; Guozhang Zhu; Jinhong Huang; Yiping Liu; Ming Lu (Desalination, 2026)

Deep removal of Cu-EDTA from saline wastewater via an ozonation-adsorption process: Salt-promoting effect and nanocomposite sequestration - Xin Li; Zhiting Li; Lu Lv; Weiming Zhang; Bingcai Pan; Ming Hua (Chemical Engineering Journal, 2026)

Harnessing sunlight-driven peracetic acid for rapid pathogen inactivation in surface waters - Yibo Wang; Ming Zheng; Jialin Li; Xinyu Ma; Shenqi Lu; Zhiyong Chen; Yajie Gao; Jiayi Wang; Wenhui Qiu; Rongrong Xuan (Chemical Engineering Journal, 2026)

Tracking clinically critical antibiotic-resistant bacteria and resistance genes in biogas slurry-amended soil: occurrence, enrichment and vertical distribution - Jiwei Li; Yi Lu; Xingshuo Wang; Lifeng Ping; Hua Li; Guanyu Zheng; Ming Hung Wong; Shengdao Shan (Bioresource Technology, 2026)

The role of transcription factor MdGeBP3 in Modulating cold stress tolerance and anthocyanin biosynthesis in apple - Ming-Kun Wang; Ran-Xin Liu; Cong-Yu Xu; Yue-Ning Wang; Xiao-Han Qin; Shan-Shan Li; Ying-Xue Lv; Du Liu; Jie Lu; Xiao-Fei Wang (Journal of Plant Physiology, 2026)

Disruption of OsGONST3 reduces grain cadmium accumulation without yield penalty in field-grown rice - Jing Huang; Qiang Zhang; Fang Wei Yu; Ming Qing Liu; Huai Kang Jing; Shen Yun Wang; Hao Yu Wang; Jia Qi Li; Lu Zheng; Hua Shao; Xiao Lin He; Ren Fang Shen; et al. (Journal of Hazardous Materials, 2026)

In situ Raman spectroscopic observation of thiol transformation in hydrothermal fluids: implications for hydrocarbon decomposition and reservoir desulfurization - Qian Wan; Xiaolin Wang; Wenxuan Hu; Binbin Xi; Xuesong Lu; Ye Wan; Junjia Fan; Zhen Li; I-Ming Chou (Geochimica et Cosmochimica Acta, 2026)

Pre-drilling pore pressure prediction using porosity-corrected acoustic modeling and sequential Gaussian co-Kriging method - Xinyu Guo; Taiheng Zhang; Ming Tang; Lu Zou; Shiming He; Hanchang Wang; Huajun Li (Geomechanics for Energy and the Environment, 2026)

Engineering bimetallic Cobalt–Iron glycerate Co-Catalysts on bismuth vanadate for improved charge transfer and photoelectrochemical catalytic water oxidation - Tsung-Rong Kuo; He-Jin Li; Kai-Jie Chuang; Chutima Kongvarhodom; Sibidou Yougbaré; Muhammad Saukani; Hung-Ming Chen; Lu-Yin Lin (Fuel, 2026)

Low-frequency deficit irrigation in a semi-arid vineyard of Xinjiang's Manas region: Effects on grape and wine aroma composition across three vintages - Ning Shi; Meng-Bo Tian; Hao-Cheng Lu; Yi-Fan Zhao; Ming-Yu Li; Jia-Yi Deng; Chi-Fang Cheng; Shu-De Li; Zhen-Zhen Zhang; Keji Yu; Yi-Bin Lan; Fei He; et al. (Food Research International, 2026)

Unraveling the fruity aroma in soy sauce aroma Baijiu by pinpointing key aroma compounds and evaluating their sensory impact - Yu-Jie Li; Xiao-Juan Zhang; Lan Wu; Zhen-Ming Lu; Lu-Qin Tian; Yun-Hao Lu; Li-Juan Chai; Hong-Yu Xu; Xiao-Long You; Yuan-Long Chi; Feng Hu; Zheng-Hong Xu (Food Chemistry, 2026)

Microbial and environmental determinants of 1-propanol biosynthesis in Jiang-flavor Baijiu fermentation - Wei-Tao Zhai; Han Zhao; Li-Juan Chai; Wei Zhang; Xiao-Juan Zhang; Zhen-Ming Lu; Chuan-Qiang Gao; Guan-Ru Si; Wen-Qing Zhang; Song-Tao Wang; Cai-Hong Shen; Zheng-Hong Xu (Food Microbiology, 2026)

Concentration-dependent variation in carbon allocation and microbial assembly in chain elongation microbiota: Comparative effects of acetate, ethanol, and lactate - Ya-Ning Song; Li-Juan Chai; Ling Ao; Jun-Lan Mei; Yu-Long Li; Zhen-Ming Lu; Xiao-Juan Zhang; Song-Tao Wang; Cai-Hong Shen; Jin-Song Shi; Zheng-Hong Xu (Bioresource Technology, 2026)

New enantiomers from Ficus variolosa Lindl. ex Benth. and their anti-inflammatory and neuroprotective activities - Ling-Fei Tong; Yu-Qiong Lu; Qing Li; Shun Pan; Hui Li; An Jin; Wen-Ming Wu (Natural Product Research, 2026)

Grain tailoring enables robust high-temperature ferroelectricity in ultrathin Hf1–xZrxO2 films - Haoyu Lu; Yu Li; Liyang Ma; Geng Huangfu; Xuanyu Zhao; Changsong Xu; Hongjun Xiang; Yingfen Wei; Hao Jiang; Qi Liu; Ming Liu (Science Bulletin, 2026)

A star’s death by a thousand cuts: the runaway periodic eruptions of AT2023uqm - Yibo Wang; Tinggui Wang; Shifeng Huang; Jiazheng Zhu; Ning Jiang; Wenbin Lu; Rongfeng Shen; Shiyan Zhong; Dong Lai; Yi Yang; Xinwen Shu; Tianyu Xia; et al. (Science Bulletin, 2026)

Solving excited states for long-range interacting trapped ions with neural networks - Yixuan Ma; Chang Liu; Weikang Li; Shun-Yao Zhang; Lu-Ming Duan; Yukai Wu; Dong-Ling Deng (Science Bulletin, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Discovery and exploration of lignans from Dendrobiun chrysotoxum as new botanical insecticides against Acyrthosiphon pisum and Bursaphelenchus xylophilus - Wen-Yu Wang; Yue-Tong Zhu; Chuan-Le Guo; Bo-Tao Lu; Chun-Huan Li; Jin-Ming Gao; Meng Yang (Pesticide Biochemistry and Physiology, 2026)

Mechanistic insights into KOH-regulated biochar derived from waste Myriophyllum aquaticum biomass for 1O2-mediated degradation of 2,4,6-trichlorophenol - Guangya Zhou; Dong Zhang; Zhengzheng Lou; Miaomiao Zhao; Dihua Wu; Suling Zhang; Ying Pan; Ting Lü; Hongting Zhao; Jun Lin; Li Lu; Ming Zhang (Journal of Environmental Management, 2026)

Deciphering Qu-aroma in Nongxiangxing baijiu via a customized aroma base solution - Sheng-Bing Yang; Zhen-Ming Lu; Jia-Nan Hu; Ting-Yao Tu; Man-Si Niu; Xiao-Juan Zhang; Li-Juan Chai; Hong-Yu Xu; Song-Tao Wang; Su-Yi Zhang; Cai-Hong Shen; Jin-Song Shi; et al. (Food Research International, 2026)

Tapioca starch-yeast protein 3D printing system for dysphagia: Different hydrocolloids regulate viscoelasticity and 3D printing accuracy through molecular interactions - Jiawen Wang; Jieling Chen; Ming Du; Keke Lu; Xuxu Li; Qilin Huang (Food Chemistry, 2026)

Strip deep rotary tillage reduces the optimal nitrogen rate for high maize yield in the North China Plain: A system-specific optimization of root-shoot growth and soil nitrogen availability - Zhuohan Gao; Hongliang Lan; Zhigang Wang; Xinbing Wang; Zaisong Ding; Rui Wang; Lu Liang; Congfeng Li; Ming Zhao; Baoyuan Zhou (Field Crops Research, 2026)

Associations of residential green and blue space with risk of esophageal squamous cell carcinoma and gastric cancer: Mediating roles of air pollution - Xiaolin Yin; Zhen Li; Aiying Teng; Xiaorong Yang; Weimin Ye; Xingdong Chen; Yuan Zhang; Tongchao Zhang; Ming Lu (Environmental Research, 2026)

A heterotrophic nitrification and aerobic denitrification strain capable of antibiotic degradation: From function to mechanism - Jia-Ying Li; You-Wei Cui; Yuan Sui; Ji-Tao Yan; Xin-Yu Gu; Rui-Chun Yang; Ming-Xin Su; Ze-You Lu (Environmental Pollution, 2026)

Topology-driven multistage strengthening in space-filling tessellated origami lattice structures with hollow prismatic struts - Yulong He; Jiapeng Sun; Xin Li; Ming-Hui Lu; Yan-Feng Chen (Engineering Structures, 2026)

Combinatorial optimization strategy with three-tier constraints of multi-split air conditioners considering thermal comfort, energy cost, and low-carbon: A numerical investigation - Yan-Ao-Ming Xi; Hai-Hao Jiang; Zhen-Yu Li; Yun-Ze Li; Kai-Feng Chang; Ya-Hui Chen; Jia-Lu Xu; Xiao-Ya Si (Building and Environment, 2026)

Decoding, Mapping, and Designing: A New Paradigm for Harnessing Umbilical Cord Mesenchymal Stem Cell Heterogeneity in Obstetric Precision Therapy - Zhang-Lu An; Zhi-Ming Wang; Wen-Hao Zhao; Li-Juan Peng; Er-Meng Gao (Stem Cell Reviews and Reports, 2026)

TianGong database—an open-source, ILCD entry-level life cycle unit process database of china - Ming Xu; Weiqiang Chen; Yutao Wang; Lei Shi; Zhi Cao; Huimin Chang; Chang Chen; Xiangbin Ding; Jianwei Du; Huabo Duan; Kai Fang; Cuiyang Feng; et al. (Journal of Industrial Ecology, 2026)

Effects of photoperiod on gonadal development and neuropeptide Y and NPY1 receptor in Nile tilapia (Oreochromis niloticus) - Yujie Cao; Jun Xiao; Pengfei Gao; Yufang Chen; Zhanyang Tang; Liping Li; Zhongbao Guo; Ming Li; Zhuanling Lu; Ting Huang (Fish Physiology and Biochemistry, 2026)

Acute Myeloid Leukemia Patients with High-Risk Karyotypes Benefit from Decitabine in Combination with Modified CAG - Ping Liu; Chuanyang Lu; Qian Sun; Yu Zhu; Xiaoli Zhao; Jianyong Li; Sixuan Qian; Ming Hong; Wenjie Liu (Biochemical Genetics, 2026)

Beyond compensation: Governing human–wildlife coexistence under climate and land-use change - Yifei Zhang; Wenjun Ming; Zhilong Chen; Xiang Gao; Shuzhi Long; Xiaotong Shang; Lu Dong; Sheng Li; Li Zhang (Ambio, 2026)

Synthesis and biological evaluation of Phorbazole D analogues identify IO-5a as a promoter of hUC-MSC chondrogenic differentiation - Ai-zhu Wang; Xiao-mei Liu; Li-ming Zhang; Lu-lu Fu; Ping Li; Jie-ping Zhang; Hua Han (Molecular Diversity, 2026)

A Protective Role for Melatonin: Enhancing Heat Tolerance in Alisma plantago-aquatica Seedlings - Wen-hui Chen; Jiao Wang; Ke-yu Wang; De-qiang Li; Zi-zhong Tang; Yang-er Chen; Shu Yuan; Lu Zhang; Ming Yuan (Journal of Plant Growth Regulation, 2026)

Antibiofilm activity of berberine against Staphylococcus aureus - Ming Lu; Ze Yao; Chunshuang Li; Xiang Li; Hui Shang; Songtao Bie (Biofouling, 2026)

Persistent testicular glycogenolysis and active lipid metabolism during torpor in hibernating Siberian chipmunks - Zhe Wang; Lu-Fan Li; Yu-Jing Yan; Ming-Yan Yuan; Xiang-Yu Zhao; Li-Na Jiang; Xian-Feng Yi (Journal of Thermal Biology, 2026)

EcR-JHAMT3 axis regulates reproductive plasticity in the predatory beetle Harmonia axyridis - Li Zhu; Jia Lv; Zhen-dong Huang; Zhan-xu Pu; Lian-ming Lu; Shuo Xu (Insect Biochemistry and Molecular Biology, 2026)

Dissecting the division of labor among five jiuqu starters in sesame-flavor baijiu fermentation - Yan-Yan Ma; Wei Zhang; Hui Tian; Tian-Tian Meng; Sheng-Bing Yang; Xiao-Juan Zhang; Li-Juan Chai; Hong-Yu Xu; Wen-Qing Zhang; Chuan-Qiang Gao; Zhen-Ming Lu; Zheng-Hong Xu (Food Bioscience, 2026)

Computational-guided semi-rational design to reprogram phospholipase D into industrially robust enzyme - Xiao-Li Kong; Peng Zhang; Zheng-Qiang Qin; Chang Su; Heng Li; Zhen-Ming Lu; Jin-Song Gong; Zheng-Hong Xu; Jin-Song Shi (Bioresource Technology, 2026)

Glaucoma Drug Target Prioritisation Informs Disease-specific Therapeutic Potentials of Targeting SMAD4 - Chaohui Bao; Tingting Tan; Yisheng Yang; Chenxu Gao; Kaiwen Liu; Chang Lu; Rulin Guo; Zheng Wang; Jiantao Shi; Jinchen Li; Ming Ni; Hai Fang; et al. (Phenomics, 2026)

Temporal transcriptomic profiling identifies core regulators in cytokine-induced gut barrier disruption in differentiated Caco-2 cells - Hyo Shin Yoon; Shining Ma; Matt Kanke; Wan-Jung Wu; Uyen Hoang; Jessica A. Tan; Alex Wilks; Priyanka Patel; Sundeep Chandra; Xin Luo; Daniel Lu; Scott Martin; et al. (Inflammation Research, 2026)
Objective The intestinal epithelial barrier maintains gut homeostasis, and its disruption contributes to inflammatory diseases such as Inflammatory Bowel Diseases (IBD). Although barrier restoration is a promising therapeutic strategy, most current approaches target immune responses rather than epithelial function. Since barrier injury and repair progress through discrete phases, this study aimed to define time-resolved epithelial transcriptional programs and identify candidate regulatory nodes for barrier-focused therapeutic intervention. Methods Differentiated Caco-2 epithelial monolayers were used to model cytokine-induced barrier disruption and profiled by time-resolved bulk RNA-seq. Transcriptional dynamics and candidate regulators were identified using pairwise differential expression, likelihood-ratio testing, pathway enrichment, and upstream-regulator inference. Candidate nodes were tested by pharmacologic perturbation, and disease relevance was assessed by qPCR and histology in human IBD colon tissues. Results Time-resolved profiling revealed dynamic epithelial programs involving the Rho GTPase cycle, sirtuin signaling, non-canonical WNT signaling, and junction/EMT-associated pathways. Upstream-regulator inference highlighted JAK2, TNF, gasdermin D, and β-estradiol, and pharmacologic perturbation of these nodes mitigated cytokine-induced barrier loss. HNF4A emerged as a gut epithelial transcriptional hub regulating targets including SATB2 and SLC26A3. Notably, SLC26A3 was markedly reduced in IBD colon tissues. Conclusions This study provides a time-resolved epithelial framework and highlights therapeutic opportunities for barrier-focused interventions.

A potent TGF-β heterodimer orchestrates germ cell homeostasis in fish - Ming-Tao Wang; Chun Miao; Sheng Yang; Zhi Li; Meng-Di Zhu; Jie He; Miao Ding; Si-Wei Wu; Yang Zhang; Shun Li; Meng Lu; Peng Yu; et al. (Science Bulletin, 2026)

Global material flow analysis of scandium from 2000 to 2024: Insights into supply, stocks, and circularity gaps - Qiang-Feng Li; Yi-Ding Wu; Lu Wang; Dan Lai; Qi-Ming Guo; Zong-Bin Shi; Shen Zhao; Qian-Qian Wang; Wei-Qiang Chen (Resources, Conservation and Recycling, 2026)

Streptochlorin from Streptomyces youssoufiensis YMF3.862 as a potential ecological fungicide for controlling Fusarium head blight on wheat - Min Chen; Chen-Xin Ma; Madjiengui Grace Dieuveille; Xiu-Min Zhang; Lu Wang; Li Ma; Yi Cao; Zi-Xiang Yang; Pei-Ji Zhao; Ming-He Mo (Pesticide Biochemistry and Physiology, 2026)

Recyclable hygroscopic hydrogels with dynamic networks enable efficient solar-driven atmospheric water harvesting - Fu-Yao Zhong; Chen-Xi Li; Lu-Bin Zhong; Chao-Yang Guo; George Zheng Chen; Bo Weng; Jun He; Yu-Ming Zheng (Journal of Environmental Chemical Engineering, 2026)

Experimental investigation on low-temperature performance of the CO2 indirect heat pump integrated system with air and waste heat sources for electric vehicles - Haixu Teng; Ming Li; Shuangyuan Xiong; Zhikun Liu; Chunhong Lu; Xinyue Feng; Haikang Chen; Wei Chang; Yan Jiang (International Journal of Refrigeration, 2026)

Single-cell sequencing reveals metabolic reprogramming and immune regulation underlie the maintenance of teleost granulomas - Zheng-Yang Zhou; Zheng-Ran Jian; Jin-Lai Gu; Xin-Yuan Jiang; Jie He; Yuan-Chang Gao; Sheng Lian; Shang-Jie Bai; Chen-Wang Lu; Lin-Feng Kuang; Ming-Zhu Liu; Peng-Fei Li; et al. (Fish & Shellfish Immunology, 2026)

Rainbow trout (Oncorhynchus mykiss) G3BP1 function as an antiviral molecule against infectious hematopoietic necrosis virus infection - Jing-Zhuang Zhao; Yi-Zhi Shao; Wei-Tong Liu; Tong-Yan Lu; Li-Ming Xu (Fish & Shellfish Immunology, 2026)

Broad-spectrum antiviral activity of molnupiravir against fish rhabdoviruses through entry blockade and induced viral mutagenesis - Jing-Zhuang Zhao; Chun-yan Guan; Yi-Zhi Shao; Wei-Tong Liu; Tong-Yan Lu; Li-Ming Xu (Fish & Shellfish Immunology, 2026)

Multifunctional LiSCN modified SnO2 electron transport layer for efficient and stable n-i-p perovskite solar cells - Liang Lei; Song Zhang; Ting Zhu; Cheng Gao; Yafei Liu; Zhangbo Lu; Zhitao Shen; Ming Li; Dan Chi; Jianlong Kou; Shunchang Liu; Shihua Huang (Chemical Engineering Journal, 2026)

Synergistic rigid-flexible hybrid interface based on PAA and FeF3 towards dendrite-free lithium-oxygen batteries - Dongxu Yin; Guiru Sun; Daming Yang; Baoxin Ni; Ying Li; Wei Lu; Maobin Wei; Ming Feng (Chemical Engineering Journal, 2026)

Salinity decrease leads to recovery of filamentous bacterial bulking in moderately halophilic aerobic granules: Unraveling the role of fungi - Ze-You Lu; You-Wei Cui; Ya-Nan Mi; Xin-Yu Gu; Rui-Chun Yang; Ming-Xin Su; Jia-Ying Li (Bioresource Technology, 2026)

Improved eradication of apple stem grooving virus and apple chlorotic leaf spot virus in apple rootstocks by combining thermotherapy with electrotherapy - Xiao-Yan Ma; Qing Li; Zhi-Wei Kang; Ming-Yuan Jing; Ya-Ting Zhang; Min-Rui Wang; Dong Zhang; Lu Bao; Juan-Juan Ma (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)

Research progress on the application of seaweed extracts in fertilizer synergism - Shaochong Li; Haofeng He; Jingyan Chen; Xinyu Guo; Qiang Li; Ming Lu; Hang Su; Fuli Li (Algal Research, 2026)

The application of Milankovitch cycles in determining provenance direction - Ting-yu Zhang; Hui Xue; Ming-guang Hu; Min-shu Wang; Gen Li; Zhen Lu (Applied Geophysics, 2026)

Microsphazaphilones H–Y: new azaphilone pigments with HIV latency reversal activity from the marine-derived fungus Microsphaeropsis arundinis P1B - Qing-Ren Lu; Xian-Yuan Yang; Lei Li; Lei-Ming Wu; Lu-Xiang Wan; Yi-Fan Fu; Xian-An Chen; Xin-Xiang Xu; Tao Yuan; Xin Chen; Abrar Ahmed; Nirmal Malik; et al. (Marine Life Science & Technology, 2026)

Two new diterpenoid alkaloids from Aconitum legendrei Hand.-Mazz - Ming-Lu Zheng; Feng-Tai Qiu; Qing Tang; Lin Chen; Qin He; Shuai Huang; Xian-Li Zhou (Natural Product Research, 2026)

A NIR Molecular-level Framework Tracks Mercury Ions via Fast and Real-time Determination in Real Samples and Live Cells - Miaoyuan Zhang; Xiaole Chen; Zhijie Luo; Xiangqian Li; Jia Jiang; Jie Deng; Ming Lu; Fuhao Liu; Qianming Wang (Journal of Fluorescence, 2026)

Development of rapid visual LAMP-based assay and nanoencapsulated carvacrol formulation for early detection and sustainable management of Fusarium solani in Morchella esculenta - Ju Ou; Minggui Ou; Qingyin Liu; Xuemei Lu; Bangxi Zhang; Ming Li; Rongyu Li (Crop Protection, 2026)

Chemistry-informed marine copper water quality criteria derived via salinity- and DOC-corrected toxicity modeling - Heng Zhang; Qing-Wei Li; Xin-Ming Pu; Jin-Fen Pan; De-chi Lu (Regional Studies in Marine Science, 2026)

A physics-informed hybrid framework for dynamic wellhead pressure prediction and equipment safety assessment in high-temperature high-pressure condensate gas wells - Lu Zou; Ming Tang; Shiming He; Taiheng Zhang; Ge Wang; Xinyu Guo; Xuliang Zhang; Huajun Li (Process Safety and Environmental Protection, 2026)

Experimental study on dual-heat-source collaborative optimization of vehicle CO2 thermal management system using integrated multi-strategy closed-loop algorithm - Haixu Teng; Ming Li; Yulong Li; Han Su; Shuangyuan Xiong; Chunhong Lu; Xinyue Feng; Yan Jiang (International Journal of Refrigeration, 2026)

Grass carp NLRP12-like 2 facilitates GCRV replication by disrupting the NLRP3-ASC inflammasome axis - Li Qiang Zhang; Xiao Man Wu; Lu Yi Liu; Ming Xian Chang (Fish & Shellfish Immunology, 2026)

Intelligent ROS-triggered NO and isotretinoin co-delivery hydrogel dressings for microenvironment modulation and rapid repair of diabetic wounds - Bin Lu; Hanzhang Wang; Junyi Zhou; Jieying Lai; Xue Zheng; Shuang-Zhuang Guo; Li-Ming Zhang (Chemical Engineering Journal, 2026)

High-voltage-tolerant zirconium-organic nanosheet separator enabling 5 V LiNi0.5Mn1.5O4|Li batteries with enhanced capacity density - Jian-Qiang Shen; Ya-Nan Gao; Ying-Li Song; Lingjuan Zhang; Gen Chen; Guoqiang Tan; Yunfeng Lu; Xian-Ming Zhang (Chemical Engineering Journal, 2026)

Berberine Hydrochloride Enhances the Fluconazole Susceptibility of Candida albicans through Multiple Targets - Lu Yu; Weijia Yi; Wenming Zheng; Dongming Zheng; Jiaqi Li; Lihua Luo; Guining Luo; Ming Xia; Li You; Jiangyan Yong (Current Microbiology, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Effects of Dietary Lipid Levels on Growth Performance and Transport Stress Tolerance in Channel Catfish (Ictalurus punctatus) - Tao Teng; Dehong Zhang; Jianhua Ming; Hualiang Liang; Li Cai; Tingting Li; Xiufang Ren; Lu Zhang; Haifeng Mi (Fishes, 2026)
This study aimed to investigate the effects of dietary lipid levels on growth performance and transport stress resistance in large-sized channel catfish (Ictalurus punctatus). Four experimental diets were formulated with fat levels of 7.5% (control), 10.0%, 12.5%, and 15.0%, using soybean oil as the lipid source. Each diet was assigned to four replicate groups in a 110-day feeding trial, with fish averaging 600.61 ± 1.33 g at the start. Results showed that increasing dietary fat enhanced weight gain rate (WGR) and specific growth rate (SGR), with the 15.0% fat group achieving the best growth performance and the lowest feed conversion ratio (FCR), significantly lower than the control (p

Ubiquitously expressed prefoldin-like chaperone (UXT) regulates putrescine metabolism and promotes colorectal cancer progression - Ming Chen; Shisi Huang; Lu Gong; Xingcheng Wu; Ying Li; Hanbing Wu (Human Cell, 2026)

Hepatotoxicity of environmental acetamiprid and cadmium in Pelophylax nigromaculatus: An integrated analysis from histopathology to molecular mechanisms - Limin Tian; Shaoqin Chen; Renyue Ming; Ya Yang; Li Wang; Yanhua Wang; Ping Lu (Pesticide Biochemistry and Physiology, 2026)

Driving factors on bacterial community of heterotrophic nitrification and aerobic denitrification in real wastewater treatment plants: Evidence from different latitudinal gradients in warm season - Rui-Chun Yang; You-Wei Cui; Zhen-Ying Li; Yuan Sui; Tong Ren; Xin-Yu Gu; Ming-Xin Su; Ze-You Lu (Journal of Water Process Engineering, 2026)

Corrigendum to “Identification of roasting degree and interpretability analysis of Yunnan arabica coffee beans based on multi-dimensional visual features and CNNs-SHAP” [Food Chem. 508 (2026) 148367] - Siheng Lu; Jing Zhao; Qian Qin; Wenxuan Deng; Yue Yu; Yue Huang; Ming Li; Hao Dong; Zhanming Li (Food Chemistry, 2026)

Identification of roasting degree and interpretability analysis of Yunnan arabica coffee beans based on multi-dimensional visual features and CNNs-SHAP - Siheng Lu; Jing Zhao; Qian Qin; Wenxuan Deng; Yue Yu; Yue Huang; Ming Li; Hao Dong; Zhanming Li (Food Chemistry, 2026)

The role of VxrB in Vibrio harveyi and evaluation of a VxrB knock-out as a vaccine candidate - Yinhui Peng; Xin Lu; Ming Liu; Shuo Hu; Lulu Liu; Renjie Li; LuJia Yang; Xiaohui Cai; Shuanghu Cai (Fish & Shellfish Immunology, 2026)

Occurrence, persistence and vertical distribution of high-risk antibiotic resistance genes in biogas slurry-amended soils across China - Liting Zhang; Hao Li; Jiwei Li; Yi Lu; Yanjun Chai; Zichuan Li; Lifeng Ping; Ming Hung Wong; Shengdao Shan (Bioresource Technology, 2026)

Sugarcane Phenotypic Parameters Modeling Using Unmanned Aerial Vehicle Multispectral Data - Yanli Chen; Lu Huang; Mingzhi Li; Ming Sun; Meihua Ding; Lining Huang; Ruisheng Ma; Chi Liang; Xin Yang; Cheng Chen (Sugar Tech, 2026)

Blast Fragmentation Prediction Model Based on Energy Fan Theory - Dongqiang Liu; Xinhua Zeng; Ming Chen; Peng Zhang; Jiangping Yan; Wenbo Lu; Fengze Zhao; Mingze Li; Zhanzhi Tan (Rock Mechanics and Rock Engineering, 2026)

Subcellular Structures in Native Hippocampal Synapses Revealed by Cryo-electron Tomography - Chong-Li Tian; Lei Qi; Zhen-Hang Lu; Shuo Liu; Min-Ling Gu; Wen-Lan Huang; Yi-Tong Yan; Yun-Tao Liu; Jing Wu; Peiyi Wang; Z. Hong Zhou; Guo-Qiang Bi; et al. (Neuroscience Bulletin, 2026)

Physical Activity and Depressive Mood Share the Structural Connectivity Between Motor and Reward Networks - Shiqi Di; Na Luo; Weiyang Shi; Zhengyi Yang; Jing Sui; Rongtao Jiang; Yue Cui; Zongchang Du; Jiaqi Zhang; Yawei Ma; Haiyan Wang; Congying Chu; et al. (Neuroscience Bulletin, 2026)

Responses of Soil Water Infiltration and Recharge to Irrigation Methods in the Semi‐Arid Farming–Pastoral Ecotone of Northern China - Zhenguo Xing; Ruimin He; Jie Fang; Mingzhe Lei; Lu Bai; Xuejia Li; Xiaoqing Liu; Gang Liu; Ming Zhao (Irrigation and Drainage, 2026)
Water scarcity poses a critical challenge in arid regions of northwest China, where suboptimal irrigation practices have led to significant water resource depletion. This study examines soil water transport mechanisms in maize fields under different irrigation regimes in a representative farming‐pastoral ecotone through field monitoring and HYDRUS‐1D modelling during the 2023 growing season (June–September). The results revealed that, compared with conventional flood irrigation, drip irrigation substantially reduced water loss. The total infiltration amount under drip irrigation was 358 mm, of which 196 mm contributed to deep percolation. The total infiltration amount and deep percolation amount under flood irrigation were 588 and 288 mm, respectively. In contrast, drip irrigation significantly reduced these losses, cutting deep percolation by 39% and improving irrigation water use efficiency by 12%. Furthermore, we identified the optimal groundwater depth for maximizing recharge efficiency. Specifically, the optimal groundwater depths were identified as 1.5 m for drip irrigation and 2.0 m for flood irrigation, yielding irrigation infiltration coefficients of 0.46 and 0.65, respectively. These findings provide a scientific basis for developing efficient irrigation strategies and sustainable groundwater management practices in the water‐limited farming–pastoral ecotones of northern China.

Global Patterns and Drivers of Recent Decoupling Between Extratropical Spring Phenology and Temperature - Ziyu Lu; Ming Shao; Jiayan Li; Jingyuan Lin; Peiyuan Tao; Mengyu Li; Siqi Zhang; Peng Yao; Yang Fu (Global Change Biology, 2026)
While spring phenology has been widely studied, the magnitude and drivers of its decoupling from thermal cues across extratropical biomes remain poorly understood. Using satellite data from 1982 to 2021, we show that the onset of vegetation green‐up (GSOS) generally lags the onset of the thermal growing season (TSOS). This mismatch (ΔSOS) has increased by 1.51 days per decade ( p 15 days), warming‐driven advances in TSOS are increasingly decoupled from GSOS, as declining precipitation and enhanced evaporative demand intensify moisture limitation and delay green‐up; in temperate forests (both coniferous and broadleaf), warming together with enhanced shortwave radiation promotes faster GSOS advancement relative to TSOS, thereby dampening the mismatch. These contrasting pathways reveal an accelerating yet heterogeneous phenology–temperature decoupling, with far‐reaching consequences for ecosystem synchrony, seasonal carbon uptake, and land–climate feedbacks. Our results underscore the need to incorporate non‐thermal drivers and biome‐specific controls into phenological and Earth system models to better constrain future climate–biosphere interactions.

Source Control of the Seismic Energy Radiation in Rock Blasting - Yongzhen Li; Wenbo Lu; Yang Wang; Ming Chen; Peng Yan; Ting Meng; Jiawei Zheng (Rock Mechanics and Rock Engineering, 2026)

Application of a Modified In Situ Perfusion Model to Quantify Intestinal Drug Excretion and Transporter-Mediated Interactions after Intravenous Administration - Rongjin Sun; Li Li; Lu Wang; Zuoxu Xie; Dinh Bui; Zicong Zheng; Xiaofeng Zhao; Jia Hao; John Chen; Taijun Yin; Yiding Hu; Yurong Lai; et al. (The AAPS Journal, 2026)

Application of GA-SA Optimization Algorithm with Two-Level Precision Control in Inversion - Rui-qing Hu; Kai Gao; Lu Yu; Yi-Ming Zhang; Qing Li; Jie Meng (Applied Geophysics, 2026)

Chronological and climatic insights from Karst Cave Silt Sediment in Southwest China - Yuan-Yuan Mu; Qing-Duo Wang; Chang-Sheng Wang; Tian-Zhou Zhang; Shao-Qin Ma; Jing-Ming Yang; Hai-Cheng; Wen-Jun Sun; Jun-Yun Li; Yan-Min Dong; Lu-Peng Yu; Ting-Yong Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Static magnetic field coupled with control of sludge retention time enhancing nitrogen removal via heterotrophic nitrification-aerobic denitrification - Ming-Xin Su; You-Wei Cui; Rui-Chun Yang; Yuan Sui; Xin-Yu Gu; Jia-Ying Li; Ze-You Lu (Journal of Water Process Engineering, 2026)

Flavor profiles and microbial mechanisms of suansun: A comparative study of homemade and commercial production - Qiao Qian; Zheng-Pei Chen; Ke Li; Sha-Sha Fang; Zhen-Ming Lu; Hong-Yu Xu; Zheng-Hong Xu (International Journal of Food Microbiology, 2026)

Dynamic light exposure from afternoon shading reveals aromatic plasticity in grapes and wines from a semi-arid region - Meng-Bo Tian; Ning Shi; Hao-Cheng Lu; Ming-Yu Li; Jia-Yan Wei; Jia-Yi Deng; Chi-Fang Cheng; Shu-De Li; Fei He; Yi-Bin Lan; Chang-Qing Duan; Keji Yu; et al. (Food Chemistry, 2026)

Engineering a high-performance, sustainable food packaging film: Zinc-doped carbon dots reinforced konjac glucomannan nanocomposite - Lijun Wu; Jiacheng Li; Yin Zhang; Ming Zhang; Xiaoli Han; Tian Liang; Jian Liu; Qingfa Zhang; Lu Wang; Lei Zheng (Food Packaging and Shelf Life, 2026)

Side-deep placement of controlled-release urea combined with alternate wetting and drying irrigation achieves sustainable intensification of rice production in the rice–wheat system - Yuan Wang; Li Zhang; Kai Ming; Lin Cao; Song Guo; Jiaming Lu; Ziwei Li; Weiling Wang; Can Zhao; Fengping Yang; Ke Xu; Hongcheng Zhang; et al. (Field Crops Research, 2026)

Linking green space patterns to elderly stress: The serial roles of greenery perception and physical activity - Anan Guan; Chun-Ming Hsieh; Tunan Deng; Na Li; Fei Lu (Environmental Research, 2026)

Breaking the pH barrier: Doping-induced stable Cu/Cu2O heterojunction for robust nitrate-to-ammonia conversion in acidic electrolytes - Wenqi Zu; Zhenfeng Lu; Haobo Shi; Ming Li; Rongxing He (Chemical Engineering Journal, 2026)

Intelligent nanofiber membrane with humidity sensing and thermoregulation dual functions - Weibing Zhong; Yue Li; Xin Chen; Yanyan Li; Xincheng Ding; Yi Xiong; Mufang Li; Xiaojuan Ming; Jing Lu; Dong Wang (Chemical Engineering Journal, 2026)

Fast Sweeping Method Based on Equivalent Slowness for Solving the Eikonal Equation - Hong-Yi Jiang; Jian-Xun Yang; Yong-ming Lu; Jun-xin Guo; Hao Zhang; Li-chan Wang (Applied Geophysics, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Anatomical connectivity development constrains medial–lateral topography in the dorsal prefrontal cortex - Wen Li; Weiyang Shi; Haiyan Wang; Jin Li; Congying Chu; Yu Zhang; Yue Cui; Luqi Cheng; Kaixin Li; Yuheng Lu; Liang Ma; Ming Song; et al. (Science Bulletin, 2026)

Mitigating vertical clogging and managing blockage migration in bioelectrochemical constructed wetlands: Electrification time regulation as a strategy - Ming Zhou; Chao Li; Li Hu; Yantang Wang; Jiashun Cao; Hongtao Shi; Yanhong Lu; Lisha Zhu; Jinyan Guo (Journal of Environmental Management, 2026)

Post-mortem analysis of degradation behavior in catalyst layers of proton exchange membrane fuel cell under near-water boiling temperature - Daijun Yang; Bo Zhou; Yirui Lu; Jiaming Lou; Bing Li; Pingwen Ming (Fuel, 2026)

Long‐Term Dispersal Ability and Climate Drive Genetic and Biogeographic Divergence in Two Lizards With Contrasting Distribution Ranges - Shan Su; Wei Qian; Lu‐Wen Zhang; Xiang‐Mo Li; Li Ma; Xiao‐Ming Wang; Zheng‐Huan Wang; Xiang Ji (Journal of Biogeography, 2026)
Aims Long‐term dispersal ability fundamentally shapes genetic structure and biogeographic patterns, yet its role in driving divergence between closely related species with contrasting ranges remains less explored. Here, we assess its influence on genetic differentiation and range dynamics in two Eremias lizards, the widespread E. argus and the narrowly distributed E. brenchleyi . Location Northeast, Central North, and Northwest China. Taxon Mongolia racerunner Eremias argus and Ordos racerunner Eremias brenchleyi (Sauria: Lacertidae). Methods We sequenced two mitochondrial (COI and cyt b ) genes from 240 E. argus and 98 E. brenchleyi adults across their Chinese ranges, performed phylogenetic analyses using Maximum Likelihood and Bayesian Inference, assessed genetic diversity and differentiation via haplotype metrics and pairwise F ST , and projected suitable habitats under past, present and future climates using ensemble species distribution models (SDMs). Results The two species diverged approximately 4.28 million years ago. Eremias brenchleyi exhibited strong isolation‐by‐distance, high genetic differentiation, and limited post‐LGM (Last Glacial Maximum) demographic expansion, indicating topography‐constrained dispersal. In contrast, E. argus showed higher genetic connectivity and rapid expansion from the late LGM to the post‐glacial period. SDMs indicate that E. argus expanded following the LGM, while E. brenchleyi persisted in restricted ranges. By 2070, both species are projected to expand northward under SSP2‐4.5 and SSP5‐8.5, with E. brenchleyi benefiting more from warming in net range gain. Main Conclusions Long‐term dispersal ability, interacting with landscape and climate, drives genetic and biogeographic divergence. Eremias brenchleyi remains vulnerable to isolation and genetic erosion, while E. argus is threatened by climate‐driven range loss. Their contrasting responses underscore the necessity of integrating genetic and environmental data to understand species resilience under climate change.

The pineal gland in ageing and alzheimer’s disease: age-related molecular changes - Meiqi Li; Hongwei Xie; Jie Li; Yuxian Shen; Li Cai; Ming Lu; Xueyan Wu (Brain Structure and Function, 2026)

Structural characterisation of a novel polysaccharide from pseudostellaria heterophylla fibrous root and its anti-inflammatory and antioxidant activities in vitro - Meng-Yu Li; Hai-Tian Deng; Ming-Zhu Ye; Li-Li Lu; Hong-Yuan Chen; Wen Rui (Natural Product Research, 2026)

A new isoprenyl-phenol-type meroterpenoid from mangrove endophytic fungus Aspergillus sp. GXNU-Y65 - Fan-Fan Wang; Guo-Bao Huang; Cai-Hong Lu; Li-Jun Chen; Hui-Zhen Chen; Meng-Qin Luo; Ping-Fang Tao; Ming-Xiong Tan; Feng Qin (Natural Product Research, 2026)

Tetrandrine inhibits IHNV replication and improves rainbow trout survival likely by targeting Asp-81 on viral phosphoprotein - Min Wu; Yi-zhi Shao; Tong-yan Lu; Ai-jun Lv; Li-ming Xu; Jing-zhuang Zhao (Aquaculture, 2026)

Single-cell RNA sequencing reveals the immune cell landscape of head kidney in the Perciform fish (Micropterus salmoides) - Zheng-Yang Zhou; Chen-Wang Lu; Zheng-Ran Jian; Shang-Jie Bai; Lin-Feng Kuang; Jin-Lai Gu; Ming-Zhu Liu; Peng-Fei Li; Gao-Xue Wang; Qing Yu; Fei Ling; Jorge Galindo-Villegas; et al. (Aquaculture, 2026)

Efficient decomplexation of Cu(II) complexes and Cu(II) recovery via one-step Fenton-like oxidation/adsorption processes mediated by nanoconfined hydrous Co-Zr oxides - Xin Li; Xuewei Song; Lu Lv; Weiming Zhang; Bingcai Pan; Ming Hua (Water Research, 2026)

A new attenuation model for the surface blast vibration induced by underground blasting - Fengze Zhao; Ming Chen; Yang Wang; Wenbo Lu; YongZhen Li; YiFan Yu; MingZe Li (Tunnelling and Underground Space Technology, 2026)

Metabolic activation of pentachlorophenol: TCBQ as a potent inhibitor of gonadal steroidogenesis via 3β-hydroxysteroid dehydrogenase NAD+ binding-site thiolalkylation - Yao Lv; Jingwei Zhang; Ming Su; Shun Lu; Shaowei Wang; Ren-shan Ge; Huitao Li (Reproductive Toxicology, 2026)

Enhancement role of corncob slow-release carbon source on heterotrophic nitrification and aerobic denitrification process in low C/N wastewater treatment - Xin-Yu Gu; You-Wei Cui; Yuan Sui; Jia-Ying Li; Ming-Xin Su; Ze-You Lu; Rui-Chun Yang (Journal of Environmental Management, 2026)

Bacterial community in household municipal solid waste and bioaerosols released: Implications to health risks - Boning Kong; Shuang Li; Muhammad Asad; Yanqing Liu; Yuyang Long; Yan Zhao; Xia Huang; Ming Zhao; Wenjing Lu (Journal of Environmental Management, 2026)

Compact-pol to quad-pol SAR reconstruction via a joint mathematical-physical-constrained multimodal correlation-preserving latent diffusion framework - Zihuan Guo; Hong Zhang; Ji Ge; Xiao-Ming Li; Peifeng Ma; Haoxuan Duan; Lu Xu; Chao Wang (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Copper mediates oxidative stress and immune response in snakehead (Channa argus) through Nrf2 and NF-κB pathway - Xue-qin Wu; Ming-ze Li; Lu Lu; Xiu-mei Chen; Xiao-tian Niu; Yi-di Kong; Gui-qin Wang; Chang-ge Xia; Min Li (Fish & Shellfish Immunology, 2026)

Post-mortem analysis of the degradation behavior of the fuel cell gas diffusion layer under near to water boiling point conditions - Yirui Lu; Daijun Yang; Jiaming Lou; Bo Zhou; Xiangyang Zhou; Xiangmin Pan; Bing Li; Pingwen Ming (Chemical Engineering Journal, 2026)

Construction of bonded CoAl-LDH/COF-316 hybrid photocatalysts with Z-scheme heterojunction for efficient reduction of diluted CO2 - Chao Fan; Rui-Yao Li; Can-Can Yu; Ya Wang; Yu-Xin Xie; Nan-Nan Zhang; Lu-Hua Shao; Gui-Ling Zhang; Hong Dong; Feng-Ming Zhang (Chemical Engineering Journal, 2026)

Accurate prediction and screening of Ni-based bimetallic catalysts for hydrogen production from biogas reforming: An interpretable machine learning study - Wen-ming Zhang; Bin Hu; Bo-yuan Zheng; Ji Liu; Qi Niu; Kai Li; Zhi-mo Fang; Bing Zhang; Qiang Lu (Chemical Engineering Journal, 2026)

Secondary metabolites from the arial parts of Hyssopus cuspidatus Boriss. and their chemotaxonomic significance - Jian-Kang Lu; Gui-Juan Zheng; Jing-Jing Li; Xiao-Xia Jiang; Jin-Xin Zhan; Chang-Hao Yu; Xu Wang; Yi-Xuan Zeng; Tian-Jiao Qi; Hong Liu; Hui-Ming Peng; Jin-Bo Fang (Biochemical Systematics and Ecology, 2026)

Impact of surface and entrainment heat fluxes on the thermodynamic structure of the convective boundary layer over the Tibetan Plateau: Observations and modeling analysis - Xiaolan Li; Xiao-Ming Hu; Wei Wei; Lu Zhang; Yan Ren; Hongsheng Zhang (Atmospheric Research, 2026)

amh alleles on XY sex chromosomes regulate male differentiation in amphidiploid Carassius auratus - Chun Miao; Meng Lu; Miao Ding; Ming-Tao Wang; Zhi Li; Tian-Zi Yao; Zhi-Xuan Zhu; Wen-Xuan Du; Jun-Sheng Niu; Xiao-Juan Zhang; Shun Li; Peng Yu; et al. (Science China Life Sciences, 2026)

QTL analysis of single-segment substitution lines dissected from a rice CSSL-Z668 and fine-mapping of qGL3.4 for grain length - Si-Qian Xiang; Yu-Zhu Tao; Zhao-Peng Yu; Zhuo-Wen Zhao; Han Zhang; Qiao-Long Li; Lu Li; Ao-Ni Xiang; Jing-Hong Xu; Fan Zhang; Xu Yan; Zheng-Lin Yang; et al. (Euphytica, 2026)

Calculation method for cut blasting millisecond-delay time in a viscoelastic rock mass - Fengze Zhao; Ming Chen; Kanggui Li; Wenbo Lu; Yang Wang; Zhiwei Ye (Earthquake Engineering and Engineering Vibration, 2026)

A coral-derived neuropeptide suppresses pentylenetetrazol (PTZ)-induced epileptic seizures and improves recognition memory deficits by modulating NPY-Y1R - Qian Chen; Congshuang Deng; Xiaoshan Huang; Aili Wang; Nan Xu; Kaixun Cao; Min Yang; Shang Li; Qiumin Lu; Guiyi Gong; Simon Ming-Yuen Lee (Archives of Toxicology, 2026)
Epilepsy is a prevalent neurological disorder characterized by recurrent and unprovoked seizures. Despite the availability of anti-epileptic drugs (AEDs), a significant number of patients are still suffering from drug-resistant epilepsy. Neuropeptide Y (NPY) signaling system has emerged as a potential target for the development of anti-epileptic drugs due to its modulation of epileptic activity. In this study, we investigated the therapeutic potential of our previously discovered Scleractinia-derived NPY-like peptide (TpNPY) in seizure disorders. The anticonvulsant effects of TpNPY were evaluated using PTZ-induced seizures in zebrafish and mice in vivo. Furthermore, the underlying molecular mechanisms of TpNPY were assessed using glutamate-induced excitotoxicity models in HT22 mouse hippocampal cells in vitro. Our findings indicated that TpNPY could alleviate PTZ-induced seizure behavior, reduce the expression of seizure-associated immediate-early genes and the production of Reactive Oxygen Species (ROS) in zebrafish. In mice, TpNPY improved seizure behaviors, decreased inflammatory cytokine levels, and ameliorated abnormal glial activation in a PTZ kindling epileptic model. Besides, the administration of TpNPY could attenuate the PTZ-induced anxiety levels and improve recognition memory deficits. Moreover, TpNPY promotes neurogenesis and neural synaptic plasticity through the BDNF/TrkB signaling pathway. Additionally, TpNPY restored cell injury and attenuated oxidative stress in glutamate-challenged HT22 cells through the Nrf2/HO-1 signaling pathway. These results highlight the potential therapeutic efficacy of TpNPY in the treatment of seizures and provide new insights into the development of coral-derived anti-epileptic peptide-based drugs.

Baicalin-aluminum complexes inhibit growth and suppress virulence of enterotoxigenic Escherichia coli in vitro - Chun Ye; Xingyue Li; Yunqi Liu; Yuqian Chen; Ming Zhao; Ronghua Yin; Qirong Lu; Jin Liu; Yu Liu; Shulin Fu; Yinsheng Qiu (Toxicon, 2025)

Di-2-ethylhexyl phthalate may exaggerate allergic response in boys with atopic dermatitis – 4-year follow-up of the Taiwan Maternal and Infant Cohort Study - Chin-Li Lu; Hui-Ju Wen; Chiung-Shiow Wang; Chien-Wen Sun; Ming-Tsang Wu; Mei-Lien Chen; Chia-Jung Hsieh; Shu-Li Wang (Science of The Total Environment, 2025)

Synergistic antifungal activity and mechanism of carvacrol/citral combination against fusarium oxysporum in Dendrobium officinale - Xuemei Lu; Ke Hu; Minggui Ou; Min Li; Xinchun Zhang; Xingyu Zhan; Xun Liao; Ming Li; Rongyu Li (Pesticide Biochemistry and Physiology, 2025)

Improving runoff simulation in cold alpine regions based on VIC-glacier by combining LSTM error correction technology - Chen Shi; Qin Liu; Yungang Bai; Qiying Yu; Zhenlin Lu; Chengshuai Liu; Biao Cao; Lei Ren; Ming Li; Gan Miao; Caihong Hu (Journal of Hydrology, 2025)

Tailoring the asymmetric structure of Cu-Co bimetallic catalysts to promote peroxydisulfate activation for pollutant degradation - Li-Ming Sun; Qin-Chen Li; Yong-Sheng Tan; Qi-Nian Wang; Yi-Lin Lu; Yi-Jun Zhang; Dong-Hua Xie; Heng-Heng Guo; Xing Zhang (Journal of Environmental Chemical Engineering, 2025)

Investigation of heavy hydrocarbon contamination impact on CO2 separation performance of polyimide membranes - Yingchao Ma; Lina Wang; Wei Lu; Zhigang Tang; Changchun Wang; Guohui Xu; Jianhui Liu; Dandan Liu; Yunhao Li; Guodong Kang; Haijun Yu; Yiming Cao; et al. (Journal of Environmental Chemical Engineering, 2025)

Recovering carbon fibers from waste carbon fiber reinforced polymer composites via electrified Joule heating-assisted pyrolysis - Ming-xin Xu; Jie Yang; Xiang-xi Meng; Jun-ping Zhang; Yi-ye Lu; Ya-chang Wu; Wei Li; Qiang Lu (Journal of Environmental Sciences, 2025)

Multiscale Elucidation of kerogen heterogeneity in Lucaogou Formation based on experiment and simulation: Structural Determinants of reactivity and stability for shale oil conversion - Youjie Li; Huifei Tao; Zhuanhong Lu; Qian Wang; Ming Yan; Zaibo Xie; Zhongping Li (Fuel, 2025)

Lipid metabolism homeostasis and low-level glycogen metabolism in the Harderian gland of hibernating Daurian ground squirrels - Lu-Fan Li; Yu-Jing Yan; Yi-Man Liu; Qing-Ying Wang; Ming-Di Wang; Jin-Hui Xu; Zhe Wang (Cryobiology, 2025)

CuO/PVA-based ultra-low-volume oral H2S detection system to reveal tongue coating effects - Moumita Deb; Chang-Chuan Huang; Yen-Ming Lai; Chang-Ju Chu; Yu-Shan Lee; Chien-Ting Chen; William Lee; Hsin-Fei Meng; Li-Yin Chen; Olivier Soppera; Chao-Sung Lai; Ding-Han Wang; et al. (Chemical Engineering Journal, 2025)

Machine learning-aided design of adapted water treatment adsorbents: Advances, challenges, and opportunities - Ling Yuan; Sheng Li; Yujia Ma; Han Zhang; Chen Chen; Weiming Zhang; Yanyang Zhang; Ming Hua; Lu Lv; Bingcai Pan (Chemical Engineering Journal, 2025)

Cryogenic pre-activation induces structural optimization and performance boost for Li-rich Mn-based cathodes - Rui-Chi Li; Lan-Fang Que; Jun-Sen Jiang; Fu-Da Yu; Ji-Huai Wu; Xuan Wang; Can-Zhong Lu; Yi-Ming Xie (Chemical Engineering Journal, 2025)

Structural characterization and oxidative stress modulation activity of an acidic Heteropolysaccharide from Microctis folium - Xiao-lu Liang; Yu-wen Liang; Jing Tian; Fei-fan Mo; Tian-ming Pan; Yan-feng Chen; Xiao-qi Shao; Kun-Ping Li (Carbohydrate Polymers, 2025)

Pan-genomic insights into RLK family evolution and adaptation in Dioscorea alata - Zhi-Yan Wei; Sai-Xi Li; Ming-Han Li; Jie Tang; Yu-Qian Jiang; Xin-Yu Lu; Yan-Mei Zhang; Jia-Yu Xue (Plant Molecular Biology, 2025)

Araloside A Induces Raf/MEK/ERK-Dependent Autophagy to Mitigate Alzheimer’s and Parkinson’s Pathology in Cellular and C. elegans Models - Xue Chen; Xing-Yue Zhou; Cai Lan; Hai-Jun Fu; Zhi-Chao Li; Meng-Yi Chen; Yong-Ping Wen; Lu Yu; Da-Lian Qin; An-Guo Wu; Jian-Ming Wu; Xiao-Gang Zhou (Molecular Neurobiology, 2025)

Syringaldehyde Ameliorates Cognitive Dysfunction in APP/PS1 Mice by Stabilizing the NLRP3 Pathway - Ruidan Chen; Hua Gao; Tianshu Zhu; Ni Zheng; Yan Jin; Ming Li; Zhiming Lu (Molecular Neurobiology, 2025)

Intestinal NF-κB pathway–mediated pyroptosis contributes to endotoxemia-induced intestinal injury - Xinrui Wang; Wen Lu; Ruibin Cai; Jie Jiang; Chuyue Wang; Jinli Liao; Yongshu Zhang; Danni Li; Zi Ye; Ming Long; Zhihao Liu (Inflammation Research, 2025)

Xuanhong Dingchuan Tang suppresses bronchial asthma inflammation via the microRNA-107-3p/PTGS2/MAPK axis - Xi Ming; Yingzhu Lu; Huihui Huang; Jialin Zheng; Tianzi Wang; Zhuoqun Li; Xingzhu Yu; Lei Xiong (Functional & Integrative Genomics, 2025)

Multigenerational toxic effects of Butylparaben and Hexylparaben on Moina macrocopa - Xue Lei Hu; Ming Chen; Jin Lan Peng; He Ping Huang; Sui Jun Cai; Jin Ling Liu; Yun Hui Li; Lu Wang (Ecotoxicology, 2025)

Self-repair mechanisms of spiking neuron–astrocyte networks in working memory under diverse injury conditions - Bingyi Mo; Xiaoqian Liu; Lin Li; Shanshan Cheng; Yuan Zhu; Ming Yi; Lulu Lu (Cognitive Neurodynamics, 2025)

A practicable land subsidence prediction model considering the coupling effect of coal mining and loose layer drainage based on Boltzmann function - Bang Zhou; Jianrong Kang; Shengcai Li; Lu Zhang; Jinman Zhang; Ming Li (Geosciences Journal, 2025)

Plumbagin disrupts the mature biofilm of Staphylococcus aureus - Hui Yuan; Ming Lu; Chen Shi; Chunshuang Li; Ze Yao; Hui Shang; Xiang Li; Heshui Yu; Songtao Bie (Biofouling, 2025)

Three-dimensional quantum anomalous Hall effect in Weyl semimetals - Zhi-Qiang Zhang; Yu-Hang Li; Ming Lu; Hongfang Liu; Hailong Li; Hua Jiang; X.C. Xie (Science Bulletin, 2025)

Femtoscopy can tell whether Z c ( 3900 ) and Z cs ( 3985 ) are resonances, virtual states, or bound states - Zhi-Wei Liu; Jun-Xu Lu; Ming-Zhu Liu; Li-Sheng Geng (Science Bulletin, 2025)

Environmental concentration effects of imidacloprid on the renal system of Xenopus laevis: Multifaceted insights from histopathology to molecular biology - Kejia Chen; Lanying Li; Limin Tian; Renyue Ming; Ping Lu (Pesticide Biochemistry and Physiology, 2025)

From exposure to elimination: A comprehensive study of the potential risks of the chiral pesticide dinotefuran to Xenopus laevis tadpoles - Renyue Ming; Ya Yang; Lanying Li; Kejia Chen; Yanhua Wang; Ping Lu (Journal of Hazardous Materials, 2025)

Gestational joint exposure to air pollutants and intrauterine skeletal development: Mediating effect of placental metabolome in a Chinese birth cohort - Zhong-Hua Lu; Chong Liu; Chen Tang; Jun-Feng Tan; Hao Chang; Yu-Jie Chen; Guang-Ming Li; Wen-Qing Lu; Yi-Xin Wang; Jie Zhang (Journal of Hazardous Materials, 2025)

Unraveling Qu-aroma variation between inner and outer layers of medium-temperature Daqu: A multi-omics and sensory approach - Sheng-Bing Yang; Zhen-Ming Lu; Han-Jun Shen; Jun-Jie Fu; Yang Yang; Xiao-Juan Zhang; Li-Juan Chai; Song-Tao Wang; Su-Yi Zhang; Cai-Hong Shen; Jin-Song Shi; Zheng-Hong Xu (International Journal of Food Microbiology, 2025)

Comprehensive analysis of microbial communities, metabolites, and biogenic amines in bagged fermented chili paste at varying salt levels - Wei-Qin Deng; Zhen-Ming Lu; Ze-Liang Wang; Si-Qiang Jiang; Xiong-Bo Li; Zhi-Yi Fan; Xiao-Juan Zhang; Li-Juan Chai; Qi-Sheng Zhang; Jin-Song Shi; Gong Chen; Zheng-Hong Xu (Food Bioscience, 2025)

Bisphenol F promoted the differentiation of preadipocytes via ER-mediated PI3K/AKT pathway - Yanchao Zhang; Jingyi Cao; Yiwa Liu; Yinghan Lu; Haoqi He; Mingwei Xu; Meifen Wu; Yuguo Liu; Li Li; Xiaoying Xu; Ming Shi (Food and Chemical Toxicology, 2025)

Variation in the response of maize (Zea mays L.) root-shoot growth and grain yield to tillage practices under various soil compactions - Zhuohan Gao; Xinbing Wang; Zhigang Wang; Zaisong Ding; Lu Liang; Wenchao Zhen; Zheng Liu; Congfeng Li; Ming Zhao; Baoyuan Zhou (Field Crops Research, 2025)

Data-driven discovery of thermo-mechanically compatible Mn-based air electrodes for high-performance reversible protonic ceramic cells - Yuhao Zhao; Liya Zhu; Yihang Li; Heng Pan; Chuanwang Ming; Wenhao Li; Guixin Jia; Yubin Chen; Youjun Lu (Chemical Engineering Journal, 2025)

The proteo- and chitinolytic coordinate mechanisms of Streptomyces sp. SCUT-3 and its application in chitinous wastes recycling - Ming-Shu Zhang; Zhi-Wei Li; Lei Wu; Zi-Yang Luo; Can Qin; Fu-Gen Zhang; Chu-Yan Liang; Hai-Ning Wang; De-Lin Lu; Jun-Jin Deng; Xiao-Chun Luo (Chemical Engineering Journal, 2025)

[3 + 2 + 1] iridium(III) complexes for high-efficiency saturated red organic light-emitting diodes - Ping Chen; Qingwu Wu; Gui-Yan Yang; Qifei Xie; Sheng Yu; Ming-Yu Teng; Huabo Han; Guo-Li Huang; You-Xuan Zheng; Guangzhao Lu (Chemical Engineering Journal, 2025)

Identifying Risk Transition Pattern of Compound Flooding Using the Copula Integrated Markov Chain - Xiaodi Li; Ming Zhong; Xueyou Li; Jiao Wang; Lu Zhuo; Feng Ling; Lixiang Song; Xianwei Wang; Jinhui Li; Xiaohong Chen (Water Resources Management, 2025)

Recognizing Prunus persica (peach) and allied Rosaceae by the morphological characteristics of their fruitstones - Yi-Ming Wu; Li-Li Lu; Bin Sun; David K. Ferguson; Jin-Feng Li; Shi-Liang Zhou; Yu-Fei Wang; Jian Yang (Vegetation History and Archaeobotany, 2025)

Research on Magnetic Z-component Anomalies and Probabilistic Time Series Prediction Based on High-Density Geomagnetic Data in Southwest Yunnan - Lu-Qiang Sun; Tian Song; Chao-Qun Ma; Yan-Li Liu; Ming-Dong Zhang (Applied Geophysics, 2025)

Development and Application of Infectious Hematopoietic Necrosis Virus Antigen-Specific DAS-ELISA Detection Method - Jing-Zhuang Zhao; Min Wu; Li-Ming Xu; Yi-Zhi Shao; Wei-Tong Liu; Tong-Yan Lu (Fishes, 2025)
Infectious hematopoietic necrosis virus (IHNV), a salmonid rhabdovirus, causes severe mortality exceeding 90% in both wild and farmed salmon and trout. Frequent outbreaks of IHNV highlight the urgent need for rapid detection methods to support effective prevention and control. This study developed a double-antibody sandwich ELISA (DAS-ELISA) targeting the nucleocapsid (N) protein of IHNV. Two peptides derived from the N protein—selected for their strong antigenicity, high level of conservation, and surface accessibility—were used as immunogens to generate two specific monoclonal antibodies. Following optimization, the DAS-ELISA was established using monoclonal antibody N-15 as the capture antibody and horseradish peroxidase (HRP)-conjugated antibody N-106 as the detection antibody. The results of this study demonstrated that DAS-ELISA exhibited high specificity for multiple IHNV strains and showed no cross-reactivity with IPNV, SVCV, or VHSV. The detection sensitivity of DAS-ELISA for IHNV was determined to be 103 TCID50/mL. Parallel analysis of 293 clinical samples using DAS-ELISA and WOAH reference method demonstrated a concordance rate of 92.83% (κ = 0.856). These results confirm that the established DAS-ELISA exhibits high sensitivity, specificity, broad-spectrum applicability, and repeatability. In conclusion, this DAS-ELISA provides a reliable and efficient tool for high-throughput early detection of IHNV infection in clinical settings.

ZWINT down-regulated by miR-495-3p inhibited lung metastasis of breast cancer by blocking p38 MAPK signaling pathway activation - Ming-tao Shao; Wei-wen Li; Yong Li; Ping Chen; Shuai-shuai Yu; Wen-jie Lu; Chun-mei Chen; Yan Dong; Yi-wen Zhang; Qun-chen Zhang (Human Cell, 2025)
Breast cancer metastasis is the primary cause of patient mortality, yet effective therapeutic targets remain limited. Building on our prior identification of ZWINT as a prognostic marker linked to metastasis, this study defines its critical functional role and regulatory mechanism. Multi-omics analysis revealed a strong association between ZWINT expression and metastatic processes across breast cancer subtypes. Functionally, ZWINT knockdown significantly inhibited breast cancer cell migration and invasion in vitro and dramatically reduced lung metastasis in vivo. Mechanistically, we discovered that miR-495-3p directly targets and suppresses ZWINT expression, and this miR-495-3p/ZWINT axis acts through inhibiting p38 MAPK pathway activation to suppress metastatic progression in vitro. Our findings demonstrate that ZWINT drives breast cancer metastasis and is negatively regulated by miR-495-3p. The newly identified miR-495-3p/ZWINT/p38 MAPK axis may provide a promising therapeutic target for suppressing breast cancer progression.

Unraveling the enrichment mechanisms of U, Re, Se and V in the Bayinqinggeli Deposit, Northern Ordos Basin through in situ mineralogical analysis - Xiao-Wen Hu; Ming-Xing Ling; Jian-Bing Xu; Fei Xia; De-Ru Xu; Ya-Lun Li; Xiao-Yong Yang; Chao Lu; Hua-Ming Li; Zhen-Cheng Li; Long-Hui Wang; Feng Zhang; et al. (Journal of Geochemical Exploration, 2025)

Effect of Zn/Fe dual-modification on the adsorption and advanced oxidation properties of Jerusalem artichoke stalk biochar - Jiacheng Li; Ming Zhang; Lijun Wu; Gaigai Xue; Jian Liu; Peiyong Ma; Lu Wang (Journal of Environmental Chemical Engineering, 2025)

Simplified synthetic community reveals the enrichment of phthalate-degrading bacteria in maize rhizosphere enhancing phthalate degradation - Jia-Lu Wei; Yu-Hong Huang; Jun-Hua Li; Huixiong Lü; Hai-Ming Zhao; Lei Xiang; Hui Li; Yan-Wen Li; Ce-Hui Mo; Quan-Ying Cai; Qing X. Li (Journal of Environmental Chemical Engineering, 2025)

Experimental study on performance optimization control of CO2 refrigeration cycle in the indirect-loop integrated system for electric vehicles - Haixu Teng; Ming Li; Shaolong Chen; Jun Wang; Chunhong Lu; Guoliang Liu; Haikang Chen; Wei Chang; Yan Jiang (International Journal of Refrigeration, 2025)

Adaptive responses and molecular mechanisms of Lactiplantibacillus plantarum to citric acid stress - Han Xie; Wei Zhang; Cong-Rong Shi; Rui-Shan Liu; Zhen-Ming Lu; Li-Juan Chai; Hong-Yu Xu; Jin-Song Shi; Xiao-Juan Zhang; Zheng-Hong Xu (International Journal of Food Microbiology, 2025)

Flavoromics analysis and sensory evaluation of wines produced from nine red grape cultivars in Manas region, Xinjiang, China: Implications for terroir adaptation - Ning Shi; Yi-Fan Zhao; Hao-Cheng Lu; Meng-Bo Tian; Ming-Yu Li; Jia-Yi Deng; Jia-Yan Wei; Ai-Sai Chen; Chi-Fang Cheng; Shu-De Li; Fei He; Keji Yu; et al. (Food Chemistry, 2025)

Latent diffusion model for quantitative precipitation estimation and forecast at km scale - Weidong Li; Baoxiang Pan; Tiejian Li; Congyi Nai; Zhaoxi Li; Jie Chao; Bo Lu; Qingyun Duan; Ming Pan (Environmental Modelling & Software, 2025)

Aptamer-anchored hydrophobic nanopores for electrochemical/fluorescent dual-mode identification of pathogenic bacteria - Jiangxue Dong; Tianyi Lu; Yufan Zhang; Ming Su; Jingjing Wang; Yajie Fan; Yanlei Li; Hongyuan Yan; Shigang Shen; Qun Ma; Zhongfeng Gao (Chemical Engineering Journal, 2025)

Optimizing electrochemical performance and temperature stability of NVPF via copper doping - Ramon Alberto Paredes Camacho; Xin-Yu Wang; Lei Shen; Qiang Wang; Yi-Ming Zhao; Ming-Xia Gao; Li Lu (Chemical Engineering Journal, 2025)

Highly efficient and sustainable bioconversion of cottonseed meal to high-value products through solid-state fermentation by protease-enhanced Streptomyces sp. SCUT-3 - Zhen-Jie Dai; Ming-Shu Zhang; Zhi-Wei Li; De-Lin Lu; Lei Wu; Can Qin; Hai-Ning Wang; Jun-Jin Deng; Xiao-Chun Luo (Chemical Engineering Journal, 2025)

Editorial Expression of Concern: HP-β-CD-PLGA nanoparticles improve the penetration and bioavailability of puerarin and enhance the therapeutic effects on brain ischemia–reperfusion injury in rats - Hai-quan Tao; Qingfeng Meng; Ming-hui Li; Hui Yu; Mei-fang Liu; Dan Du; Shou-li Sun; Hai-cheng Yang; Yan-ming Wang; Wei Ye; Li-zhuang Yang; Da-ling Zhu; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

The deformation characteristics analyses of reactivate water-rich landslide based on DS-InSAR monitoring technology - Yongwei Huang; Xianchun Ma; Qiang Li; Ming Chang; Shibo Huang; Lingjie Lu (Natural Hazards, 2025)

Myogenic induced adipose-derived stem cells sheets combined with electrospun scaffolds of silk fibroin and poly(lactide-co-glycolide) for stress urinary incontinence treatment - Ming Liu; Yongwei Li; Yining Zhao; Fengze Sun; Youyi Lu; Jitao Wu; Qingsong Zou (Journal of Molecular Histology, 2025)

Advances in the transcriptional regulation and lipid droplet turnover in microalgae - Huidan Zhang; Er-Ying Jiang; Yingjun Zhou; Hui Wang; Yong Fan; Xiaojin Song; Ming Lu; Fuli Li (Algal Research, 2025)

Microtremor survey for exploring intermediate-to-deep geothermal resources in the urban periphery: A case study of Xining city - Sheng He; Xiao-long Han; Jing-he Li; Yu-guo Lu; De-ming Zhang; Jian-jun Hou (Applied Geophysics, 2025)

The effects of pond purification system on intestinal function of channel catfish (Ictalurus punctatus): a focus on intestinal development, digestion and absorption, and junction integrity - Zhong-Bing Zheng; Yu Yang; Jun Liu; Ming-Cheng Zhou; Ju-Hua Li; Long-Jiang Tang; Hai-Long Nie; Kang-Sheng Chen; Feng Liu; Xiang-Ning He; Zhi-Yuan Lu (Frontiers in Marine Science, 2025)
Pond purification system (PPS) is an outdoor aquaculture system designed based on recirculating aquaculture system (RAS) principles, utilizing recirculating water technology, which can achieve large-scale fish farming in the recirculating water system. The purpose of this experiment is to investigate the alterations in growth performance, intestinal histology, digestion-absorption function, and structural integrity of channel catfish raised in PPS. The findings indicated a significant optimization in water quality indicators pertinent to aquaculture, including total nitrogen, total phosphorus, chemical oxygen demand (COD), ammonia nitrogen, nitrite, and dissolved oxygen. Additionally, the growth performance of channel catfish reared in the PPS group was markedly improved. The intestinal morphology of these channel catfish exhibited increased villus height and a reduced number of mucus cells. Furthermore, serum levels of diamine oxidase and D-lactic acid were significantly decreased in channel catfish raised in the PPS group, while the expression of genes related to the apical junction complex was significantly upregulated, suggesting improved intestinal structural integrity. Moreover, the activities of digestive and absorptive enzymes, such as trypsin, amylase, lipase, and Na + -K + -ATPase, were elevated, indicating enhanced digestive and absorptive functions. In conclusion, based on the conditions of this experiment, the pond purification system module used in this study can effectively improve the quality of the aquaculture water, enhance fish growth performance and improve their intestinal health.

Co-transport behavior of aged polymeric methyl methacrylate nanoplastics and florfenicol antibiotic in porous media: Effects of electrolyte, pH, and aging duration - Lihui Tan; Ming Wu; Yanru Hao; Hui Li; Cehui Mo; Guoping Lu (Water Research, 2025)

Putting the recent 100-year of Asian summer monsoon weakening into context - Jingyao Zhao; Hai Cheng; Liangkang Pan; Kexin Wang; Jiahui Cui; Ming-Qiang Liang; Xiyu Dong; Jiayu Lu; Qiang Li; Yan Yang (Science Bulletin, 2025)

Advanced upcycling of spent electrolyte: Detoxification and selective alkene production via vacuum co-pyrolysis catalyzed by in-situ generated alkyl lithium-synergized ZSM-5 - Yu Zhang; Ming Xu; Lin Li; Dennis Yong Lu; Zhenkun Sun; Lunbo Duan (Journal of Hazardous Materials, 2025)

Association between per- and polyfluoroalkyl substances with serum hepatobiliary system function biomarkers in patients with acute coronary syndrome - Fang Xiao; Ming Yang; Junli Lv; Jing Li; Mingmei Guo; WenJing Duan; Haoran Li; Ziwen An; Zhengyi Su; Ang Li; Yi Liu; Jingchao Lu; et al. (Journal of Environmental Sciences, 2025)

Investigation on quality discrepancies of Soy Sauce Aroma Baijiu: Flavor chemical characteristics in single-source and cross-source samples - Chen Li; Xiao-Juan Zhang; Shi-Yi Wang; Zhen-Ming Lu; Li-Juan Chai; Hong-Yu Xu; Jin-Song Shi; Song-Tao Wang; Bo Yang; Cai-Hong Shen; Zheng-Hong Xu (Food Control, 2025)

Bioinspired plasmonic compound eye for on-particle label-free surface-enhanced Raman spectroscopic biosensing of multianalytes - Mingyang Chen; Yaxuan Lu; Renata Solarska; Ming Li (Chemical Engineering Journal, 2025)

Deciphering ion-specific synergy: Al3+/Zn2+ orchestrated cellulose-copolymer interfacial engineering for all-weather wearable electronics - Xin Li; Huicong Jiang; Qianqian Jia; Xi Guan; Ming Yan; Lili Zhang; Juan Yu; Jinxia Ma; Chuanwei Lu; Zhiguo Wang (Chemical Engineering Journal, 2025)

Evolution of the Rich Club Properties in Mouse, Macaque, and Human Brain Networks: A Study of Functional Integration, Segregation, and Balance - Xiaoru Zhang; Ming Song; Wentao Jiang; Yuheng Lu; Congying Chu; Wen Li; Haiyan Wang; Weiyang Shi; Yueheng Lan; Tianzi Jiang (Neuroscience Bulletin, 2025)

How did the white-spotted flower chafer (Protaetia brevitarsis) come to Xinjiang? - Jing Liu; Ziqing Wang; Chengmin Shi; Weicheng Lu; Jiaxin Pang; Deying Ma; Ming Bai; Jing Li (Journal of Pest Science, 2025)

Design and construction of cuttlefish ink derived melanin complexed microneedles for microenvironment regulation to improve vitiligo treatment - Weimiao Li; Yan Shi; Ruimin Zhan; Lu Liu; Jiarui Wang; Minhyeock Lee; Bingqiang Zhang; Shaoshuai Liang; Zhiguo Wang; Ming Kong (Marine Life Science & Technology, 2025)
Vitiligo is an autoimmune disorder marked by melanocyte destruction and epidermal depigmentation, primarily driven by inflammatory and oxidative stress within the affected skin lesions. Consequently, there is an urgent need for therapeutic strategies focused on protecting melanocytes and replenishing melanin for effective vitiligo management. In this study, a novel microneedle-based therapeutic platform (C/D/E@MN) was fabricated that was composed of cuttlefish ink nanoparticles (CINPs) for melanin supplementation, dipotassium glycyrrhizinate (DPG) for inflammation regulation, and skin-derived exosomes (EXO) to promote melanocyte proliferation. In addition, microneedles with varying dissolution profiles (swellable, slow-dissolving, and fast-dissolving) were designed and evaluated their performance to optimize therapeutic efficacy. In vitro results demonstrated that fast-dissolving microneedles (FDMN) significantly reduced cellular reactive oxygen species (ROS) and the secretion of vitiligo-related inflammatory cytokines and chemokines, such as IL-8, CXCL-16, and HMGB-1. Upon a vitiligo mice model, C/D/E@FDMN treatment group generated a significant increase in skin melanin content and a 15.5% reduction of whitening degree. The microneedles protected melanocytes and promoted lesion repigmentation through synergistic antioxidant, anti-inflammatory and cyto-proliferative mechanisms, offering a promising strategy for improved vitiligo therapy.

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Efficiencies, pathways and mechanism on simultaneous biodegradation of phthalates and polycyclic aromatic hydrocarbons by bacterial consortium - Yao-Si Chen; Jia-Lu Wei; Jie-Bin Zhou; Yu-Hong Huang; Guang-Xuan Tang; Yan-Wen Li; Hai-Ming Zhao; Lei Xiang; Nai-Xian Feng; Ce-Hui Mo; Quan-Ying Cai; Qing X. Li (Journal of Environmental Chemical Engineering, 2025)

Strawberry preservation using multilayer chitosan films grafted with phenolic acids and loaded with γ-CD-MOFs encapsulated antifungal agents - Linyun Mou; Wei Jiang; Ya Lu; Jianlong Li; Ganpeng Li; Hai Yuan; Ziyi Jiang; Lingzhi Zhang; Tingyin Ming (International Journal of Food Microbiology, 2025)

Exploring the effects of environmentally relevant concentrations of buprofezin and cadmium on tadpoles: A phenotypic and molecular analysis - Lanying Li; Lvzhuang Wang; Kejia Chen; Renyue Ming; Ya Yang; Yuping Zhang; Ping Lu (Environmental Research, 2025)

De-aggregation of sonosensitizers enhances bactericidal activity in sonodynamic therapy of deep-seated bacterial osteomyelitis - Gang Zhao; Qiang Yu; Ming Li; Guanghua Lu; Hanqing Li; Li Wei; Jiong Zhang; Shen Wang; Min Lu (Chemical Engineering Journal, 2025)

Intensified performance and mechanism of nitrogen removal in constructed wetland incorporating algal pond for treating low carbon nitrogen ratio wastewater - Xin Zhao; Ruigang Wang; Mingjun Li; Xiaochun Guo; Shaoyong Lu; Ming Li; Haiming Wu (Bioresource Technology, 2025)

Seasonal variations in the phenolic compounds and antioxidant activity of Pyrrosia petiolosa (Christ et bar.) Ching - Xiangxiang Cui; Xuan Lu; Chunling Meng; Jianhua Chen; Shaorong Chen; Ruhong Ming; Rongshao Huang; Liangbo Li (Biochemical Systematics and Ecology, 2025)

Olfactory GnRH3 crypt sensory neurons transduce sex pheromone signals to induce male courtship behavior in zebrafish - Xuefan Cui; Lu Chen; Binbin Tao; Xiya Zhang; Yanlong Song; Ji Chen; Ming Duan; Weiwei Li; Kuangxin Chen; Yang Pei; Xuerui Hu; Ke Feng; et al. (Science China Life Sciences, 2025)

Effect of rootstocks on growth potential, soil properties and rhizosphere microbiome of Vitis vinifera L. cv. Cabernet Sauvignon - Ning Shi; Xiao Han; Hao-Cheng Lu; Meng-Bo Tian; Ming-Yu Li; Fei He; Chang-Qing Duan; Ke-Ji Yu; Jun Wang (Plant and Soil, 2025)

Soil compaction reduces the yield potential of densely planted maize (Zea mays L.) by disrupting root and shoot growth coordination - Zhuohan Gao; Lu Liang; Xinbing Wang; Wenchao Zhen; Zaisong Ding; Congfeng Li; Zheng Liu; Ming Zhao; Zhigang Wang; Baoyuan Zhou (Plant and Soil, 2025)

Effectiveness of bioretention system with saturated zone and different dry–wet alterations on nitrogen removal: performance and microbial community - Ran Li; Binyu Lu; Wen-wen Liu; Zebing Li; Yi-Ming Kuo (Environmental Geochemistry and Health, 2025)

Novel lineages of fungicolous Cordieritidaceae (Helotiales, Leotiomycetes) from southwest China - Feng-Ming Yu; Kandawatte Wedaralalage Thilini Chethana; Cui-Jin-Yi Li; Lei Lei; Jin-Rong Lu; Yi-Yun Guo; Qin-Yun Yang; Vinodhini Thiyagaraja; Qi Zhao (Mycological Progress, 2025)

A multi-objective evolutionary algorithm for adjustable-speed job shop scheduling with multi-trip automated guided vehicles constraints - Ming Lu; Chengjie Zhang; Gongfu Su; Long Chen; Ying Zou; Pei Li (Swarm and Evolutionary Computation, 2025)

Exploring possible ancient applications of perilla: evidence from 3 million fruit remains from Han Dynasty tombs in China - Yun-Jun Bai; Ming Jiang; Xue-Ping Wei; Zhi-Jun Zhao; Xin-Ying Zhou; Hong-En Jiang; Tao Xie; Xiao-Lin Li; Yu-Yang Zhao; Xue Yan; Meng Cheng; Lu-Qi Huang; et al. (Science Bulletin, 2025)

New insights into rhizosphere bacterial community shaped by lettuce genotypes for divergent degradation efficiencies of phthalates - Guang-Xuan Tang; Yu-Hong Huang; Li-Wan Feng; Yu-Chang Hu; Jia-Lu Wei; Huixiong Lü; Li-Hui Liu; Hai-Ming Zhao; Lei Xiang; Hui Li; Ce-Hui Mo; Yan-Wen Li; et al. (Journal of Hazardous Materials, 2025)

PtBi nanocatalysts with controlled chain-like structure and composition: Solvothermal synthesis and ethanol oxidation performance - Luo-Yi Yan; Han-Tao Zhang; Xiao-Yu Lu; Li-Ming Liu; Rong-Hua Zhang; Zheng Cheng; Shuai-Wei Fan; Xin-Wen Zhou (Fuel, 2025)

Rapid evaluation of Curcuma origin and quality based on E-eye, flash GC e-nose, and FT-NIR combined with machine learning technologies - Qiang Guo; Ming-xuan Li; Rao Fu; Xin Wan; Wen-hao Dong; Chun-qin Mao; Zhen-hua Bian; De Ji; Tu-lin Lu; Yu Li (Food Chemistry, 2025)

Chronic and Intergenerational Toxicity of Chloramine-T in Moina macrocopa Following Prolonged Exposure - Xue Lei Hu; Sui Jun Cai; Ming Chen; Le Yi Lin; Jin Lan Peng; Jin Ling Liu; Yun Hui Li; Lu Wang (Bulletin of Environmental Contamination and Toxicology, 2025)

Great Oxidation Event was caused by Neoarchean global cratonization: opportunity and challenge from rock and sedimentary records in China - Li-Gang Zhou; Jun-Ping Liu; Jing Li; Zai-Bo Sun; Lu Xiang; Yan-Yan Zhou; Hao-Shu Tang; Yan-Bin Zhang; Xi-Yan Zhu; Hai-Long He; Ming-Guo Zhai (Science Bulletin, 2025)

Pan-genome and haplotype map of cassava cultivars and wild ancestors provide insights into its adaptive evolution and domestication - Zhiqiang Xia; Zhenglin Du; Xincheng Zhou; Sirong Jiang; Tingting Zhu; Le Wang; Fei Chen; Luiz Carvalho; Meiling Zou; Luis Augusto Becerra Lopez-Lavalle; Xiaofei Zhang; Liangye Xu; et al. (Molecular Plant, 2025)

Comprehensive assessment of 45 antibiotics in ten urban wastewater treatment plants in Northeastern China: Terminal treatment is not a reliable guard - Xin-Ming Guo; Xi-Mei Lu; Jing-Wen Jia; De-Feng Xing; Yi-Fan Li; Guang-Li Cao; Zi-Feng Zhang (Journal of Hazardous Materials, 2025)

Co-transport of polyethylene microplastics and antibiotic resistance genes in soil: Influencing factors, mechanisms, and control strategies - Xiao-Ming Lu; Li-Bo Lu; Xi-Cheng Huang; Xue-Ping Liu (Journal of Environmental Chemical Engineering, 2025)

Co3O4@carbon nanofiber aerogel electrodes with wide detection range for electrochemical detection of Cd(II) in cigarette butts - Wei Wu; Jieqiong Wang; Diyin Luo; You Wu; Zhengchuan Hu; Weibo Zhou; Qi Wang; Xingyue You; Ming Li; Lu Wang (Journal of Environmental Chemical Engineering, 2025)

Energy utilization of CO2 thermal management system for electric vehicles in cold climate: Assessment of different heat source modes - Haixu Teng; Ming Li; Jun Wang; Shuangyuan Xiong; Chunhong Lu; Zhanzhuo Song; Haikang Chen; Yan Jiang (International Journal of Refrigeration, 2025)

Differential global gene transcription of Saccharomyces cerevisiae by zinc sulfate addition under acetic acid stress and identification of novel zinc and stress-responsive genes related to cell wall function - Ming-Ming Zhang; Bing Yuan; Yu-Zhen Li; Xiao-Lu Wang; Verawat Champreda; Drauzio Eduardo Naretto Rangel; Xin-Qing Zhao (Fungal Biology, 2025)

Time series comparative genomics analysis reveals the adaptive evolution of caproic acid-producing bacteria to the long-term liquor brewing environment - Gan-Lin Li; Jun-Lan Mei; Li-Juan Chai; Xiao-Zhong Zhong; Ya-Ning Song; Zhen-Ming Lu; Xiao-Juan Zhang; Song-Tao Wang; Cai-Hong Shen; Jin-Song Shi; Zheng-Hong Xu (Food Bioscience, 2025)

Nitrogen reduction and split application increased grain yield and agronomic nitrogen use efficiency of oilseed flax (Linum usitatissimum. L) by increasing nitrogen status - Ming Wen; Yuhong Gao; Lizhuo Guo; Bin Yan; Peina Lu; Bin Wu; Yifan Wang; Yue Li; Zhengjun Cui; Peng Xu; Haidi Wang; Yuanyuan Cui; et al. (Field Crops Research, 2025)

Tenecteplase Plus Butyphthalide for Stroke Within 4.5–6 Hours of Onset (EXIT-BT): a Phase 2 Study - Hui-Sheng Chen; Ming-Rui Chen; Yu Cui; Xin-Yu Shen; Hong Zhang; Jiang Lu; Li-Wei Zhao; Ying-Jie Duan; Jing Li; Ya-Mei Wang; Lian-Qiu Min; Li-Hong Zhao; et al. (Translational Stroke Research, 2025)

Graph Neural Networks and Multimodal DTI Features for Schizophrenia Classification: Insights from Brain Network Analysis and Gene Expression - Jingjing Gao; Heping Tang; Zhengning Wang; Yanling Li; Na Luo; Ming Song; Sangma Xie; Weiyang Shi; Hao Yan; Lin Lu; Jun Yan; Peng Li; et al. (Neuroscience Bulletin, 2025)

The Nerve-Induced Adipose Stem Cells Promote Nerve Repair in Stress Urinary Incontinence by Regulating Schwann Cell Repair Phenotype Conversion Through Activation of the Notch Pathway - Ming Liu; Youyi Lu; Fengze Sun; Yongwei Li; Jitao Wu; Qingsong Zou (Molecular Neurobiology, 2025)

Potential Enhancement in Anaerobic Digestion Performance of High Salinity Organic Wastewater with Nickel-Loaded Biochar - Chen-Shun Lu; Jin-Ming Qiu; Xiang Li; Hongyu Jiang; Yanlong Zhang; Yong Hu (International Journal of Environmental Research, 2025)

New fungal taxa of Ascomycota from China - Lu Li; Vinodhini Thiyagaraja; DarbheJayarama Bhat; Dian‐Ming Hu; Fatimah Al‐Otibi; Kevin D. Hyde (New Zealand Journal of Botany, 2025)
Freshwater fungi exhibit a remarkable diversity and are commonly found on submerged wood, freshwater insects, herbaceous materials, sediments, leaves, foam, and living plants. Sordariomycetes in the Ascomycota is the most frequently reported group in freshwater environments. Three samples of submerged decaying wood and twigs samples were collected and examined during in this study from freshwater habitats in Yunnan and Sichuan provinces in China. Detailed morphological studies, complemented by phylogenetic analyses based on ITS, LSU, SSU, RPB2 and TEF1‐α sequence data, revealed them to be three hitherto known species, namely Acrogenospora thailandica , Cancellidium cinereum and Chloridium humicola . Of these, Acrogenospora thailandica is a new geographical record for China. Chloridium humicola is also reported for the first time in China which enhances the geographical and host distribution of this species, providing new insights into its ecological preferences. Cancellidium cinereum is reported as an additional provincial record from China, contributing to our knowledge of its regional distribution. All three species, reported in their asexual state, are illustrated with detailed morphological descriptions and phylogenetic analyses. In addition, we also provide a new host record of the saprobic species Isthmolongispora quadricellularia in hyphomycetous asexual state on decaying wood for the first time in a terrestrial habitat.

Three-Dimensional Shallow P-wave Velocity Distribution in the Source Area of the 2021 MS6.0 Luxian Earthquake from Dense Array Seismic Imaging - Jian-xun Yang; Qi-yan Yang; Da-hu Li; Yong-ming Lu; Ping-ping Wu; Hui-li Guo; Ning-bo Jiang; Mi Gao; Heng Pan (Applied Geophysics, 2025)

Impact of dispersion correction in DFT-enhanced anisotropic NMR for stereochemical elucidation of flexible marine natural products - Lu-Ping Chi; Xiao-Lu Li; Anton F. Ketzel; Armando Navarro-Vázquez; Caspar J. Schattenberg; Xiao-Ming Li; Xin Li; Han Sun; Bin-Gui Wang (Marine Life Science & Technology, 2025)
Although anisotropic NMR spectroscopy has emerged as a powerful method for determining the relative configuration of complex natural products, major challenges persist with structurally flexible molecules. In this study, we conducted a systematic comparative analysis of stereochemical elucidation, combining anisotropic NMR spectroscopy and density functional theory (DFT) calculations on spiroepicoccin B ( 1 ) and epicoccin V ( 2 ), which were characterized as thiodiketopiperazine marine natural products isolated from the deep-sea-derived fungus Epicoccum nigrum SD-388. For the flexible compound 2 , we compared various conformational sampling approaches, including an assessment of the quality of relative energies within the obtained ensembles. We demonstrated the critical role of dispersion correction within DFT computations to precisely account for weak non-bonded intramolecular interactions. By integrating anisotropic NMR analysis, chemical shifts, electronic circular dichroism, and DFT computations, we determined the absolute configurations and conformational ensembles for 1 and 2 , respectively, highlighting the significance of the intramolecular methyl–π interaction in stabilizing one of the conformers. Our study introduces new strategies to address conformational flexibility in the stereochemical elucidation of challenging organic molecules.

The outer membrane vesicles of Vibrio parahaemolyticus elicit innate immune responses in mud crab (Scylla paramamosain) - Qian Sun; Linying Yun; Kaichun Hu; Han Li; Pengfei Li; Yiyuan Lu; Runwu Gao; Ming Zhang; Ngoc Tuan Tran; Xiuli Chen; Yongzhen Zhao; Yueling Zhang; et al. (Aquaculture, 2025)

Self-propagated clonal seed production in dicotyledonous Arabidopsis - Wen-Qiang Chen; Liping Xu; Yuchun Rao; Chaolei Liu; Zhengyuan Hong; Hongwei Lu; Chun-Ming Liu; Hong-Ju Li; Kejian Wang (Science Bulletin, 2025)

Engineering a thermophilic Bacillus thermoamylovorans for degradation of polyethylene terephthalate waste - Yi-Mei Cai; Cui-Can Lu; Tian-Tian Wang; Li-Jun Song; Yu-Ming Deng; Han Xu; Sheng Chen; Wei Xia; Jing Wu; Zheng-Fei Yan (Journal of Cleaner Production, 2025)

Evaluation of the freshness (TVB-N) of pork patty during storage based on PLS-DA, SVM and BP-ANN models - Hui Lu; Aiying Song; Ming Li; Xianqi Yao; Yuling Cai; Longlong Dong; Dacheng Kang; Yunguo Liu (Food Control, 2025)

Bonding of wood with high strength and excellent water resistant cellulose colloidal adhesives - Yuyan Jiang; Tian Ju; Liangxian Liu; Haiyu Li; Yue Zhang; Na Wang; Zetan Lu; Ming Wei; Dexiu Min; Yanjun Xie; Jian Li; Yonggui Wang; et al. (Chemical Engineering Journal, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Effect of food addiction of lysine on feeding habit in fish - Hong-Liang Lu; Yun-Liang Miao; Jia-Ming Zou; Zi-Jun Hu; Ying-Cen Li; Xu-Fang Liang; Shan He (Aquaculture, 2025)

Bicyclic polyprenylated acylphloroglucinol-related meroterpenoids as potent DRAK2 inhibitors from Hypericum patulum - Jin-Chang Huang; Xin-Yu Jia; Yi-Fan Lv; Hong-Hong Xu; Ming Han; Qiang-Qiang Yu; Yu-Ting Lu; Hong-Xun Yang; Yang Yang; Jing-Ya Li; Ai-Jun Hou (Phytochemistry, 2025)

Mechanisms and mitigation control of clogging in constructed wetlands: Insight into the enhancement of the bioelectrochemical systems - Ming Zhou; Jiashun Cao; Jinyan Guo; Yantang Wang; Yanhong Lu; Lisha Zhu; Li Hu; Weijing Liu; Chao Li (Journal of Environmental Management, 2025)

Experimental and computational study on xylan pyrolysis: The effect of branch structures - Bin Hu; Wen-ming Zhang; Xue-Wen Guo; Ji-hong Li; Xiao Yang; Zhi-mo Fang; Ji Liu; Qiang Lu (Fuel, 2025)

Lactic acid bacteria-mediated transformation of black tea extract: Insights into metabolite profile and sensory characteristics - Zhi-Peng Cheng; Yao-Zeng Zhang; Zhong-Zheng Guan; Rui-shan Liu; Zhen-Ming Lu; Li-Juan Chai; Hong-Yu Xu; Jin-Song Shi; Xiao-Juan Zhang; Zheng-Hong Xu (Food Bioscience, 2025)

Influence of freeze-thaw cycles on change of arsenic speciation and toxic effects to bacteria in paddy soil - Xiaohui Lu; Jiaxing Yu; Jinfeng Li; Yong Yu; Long Sun; Ming Li (Environmental Pollution, 2025)

2-Mercapto-1,3,4-thiadiazole-functionalized gold nanoclusters as a comparable bactericidal nanoantibiotic to vancomycin in treating methicillin-resistant Staphylococcus aureus infections - Quan-Quan Zhuang; Jia-Xin Ma; Yi-Ming Zheng; Lin-Yan Lu; Jia-Lin Yang; Qing-Qing Chen; Xiao-Li Yan; Yan-Cheng Jiang; Hao-Hua Deng; Wei Chen; Gang Liu (Chemical Engineering Journal, 2025)

Anisotropic thermal expansion suppression of Cu doped with oriented reduced graphene oxide by anharmonic vibration restriction - Yuhang Li; Shan Lu; Tianyu Zhang; Xiangyu Ren; Sibo Zhao; Shenghong Ju; Ming Li; Yunwen Wu (Chemical Engineering Journal, 2025)

Simple and robust method for the quantification of nine organic acids in beer using 3-chloropropyl bonded C18 materials with HPLC-UV analysis - Yu Shi; Huifan Li; Yuqi Lu; Ming Chen; Hua Yang; Dongmei Fu (Systems Microbiology and Biomanufacturing, 2025)

Phosphorus transformation after amendment applications in rapeseed soil with cadmium contamination - Zhuoqing Li; Yuexing Huang; Jiayi Wu; Boqing Tie; Xia Lu; Ming Lei; Xinqi Wang (Journal of Soils and Sediments, 2025)

Effects of expansion of protected areas and habitat transformation on spatiotemporal variation in human–wildlife conflict - Yumei Li; Chao Zhang; Huayao Gao; Ming Lu; Yonggang Nie (Conservation Biology, 2025)
Land‐use changes and the expansion of protected areas (PAs) have fostered increased interactions between humans and wildlife, resulting in an escalation of human–wildlife conflict (HWC) globally. However, HWC spatiotemporal pattern variation and its associations with PAs and land‐use change remain poorly understood. To address this knowledge gap, we mapped and analyzed HWCs from 1990 to 2022 across China. We comprehensively mapped the spatiotemporal dynamics of HWCs in ArcGIS with data sets stratified by county, year, and species; assessed the impact of PAs through propensity score matching; and analyzed the effects of habitat transformation with linear mixed models. As PA increased from 0 to 20,000 km 2 , the likelihood of HWCs initially increased (50%) before declining (20%). Conversely, as the distance from a PA grew, the likelihood of HWC gradually decreased (0 beyond 65 km). There was a temporal lag between the establishment of a PA and the occurrence of HWC. Habitat loss catalyzed HWCs, whereas decreased levels of habitat fragmentation sometimes initially caused a temporary increase in HWCs. In general, the distribution of PAs greatly affected HWC occurrence, and habitat loss and fragmentation were critical drivers of HWCs, both of which exhibited time‐lagged effects. HWC has become more challenging to address as conservation initiatives have led to significant recovery of the habitats and populations of wild animals. Further measures to address the HWCs are needed to ensure the preservation of animal welfare while fostering the mutually beneficial coexistence of humans and animal species. Finally, our study provides an important starting point for informing future HWC research and conservation planning on a global scale.

Probiotic potential of intestinal bacteria isolated from the digestive tract of hybrid snakehead (Channa argus♀ × Channa maculata♂) - Wen-Hao Wu; Yan-Xin Sun; Jia-Hao Zhang; Kun-Ming Huang; Xi-Chao Liu; Shu Tang; Wei Li; Biao Jiang; You-Lu Su (Aquaculture, 2025)

Origin and evolution of sub-caldera magmatic systems before and during the caldera-forming eruptions of the Furongshan caldera, SE China - Ming-Lu Li; Zhen-Yu He; Tian-Yu Lu; Li-Li Yan (Lithos, 2025)

Low model-dependent sensor placement method for water distribution networks using adaptive attributed graph clustering - Qingshuai Sun; Yingjie Zhang; Ming Li; Hualiang Liu; Biliang Lu; Shujie Li (Journal of Water Process Engineering, 2025)

Automatic extraction and quantitative analysis of characteristics from complex fractures on rock surfaces via deep learning - Mingze Li; Ming Chen; Wenbo Lu; Peng Yan; Zhanzhi Tan (International Journal of Rock Mechanics and Mining Sciences, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

O-O bridge adsorption catalysis of different metal single atoms toward high-sensitive detection of H2O2 - Juan Li; Jinggao Wu; Fan Shi; Mingyuan Wang; Zhuo Zou; Zhisong Lu; Liming Dai; Chang Ming Li (Chemical Engineering Journal, 2025)

Single-Neuron Reconstruction of the Macaque Primary Motor Cortex Reveals the Diversity of Neuronal Morphology - Siyu Li; Yan Shen; Yefei Chen; Zexuan Hong; Lewei Zhang; Lufeng Ding; Chao-Yu Yang; Xiaoyang Qi; Quqing Shen; Yanyang Xiao; Pak-Ming Lau; Zhonghua Lu; et al. (Neuroscience Bulletin, 2025)

Cholesterol suppresses AMFR-mediated PDL1 ubiquitination and degradation in HCC - Wei-Qing Shao; Yi-Tong Li; Xu Zhou; Sheng-Guo Zhang; Ming-Hao Fan; Dong Zhang; Zhen-Mei Chen; Chen-He Yi; Sheng-Hao Wang; Wen-Wei Zhu; Ming Lu; Ji-Song Chen; et al. (Molecular and Cellular Biochemistry, 2025)

Forest Microclimate as a Driver of Epiphytic Bryophyte Diversity Along a Subtropical Elevational Gradient - Zun Dai; Shi‐chen Xing; S. Robbert Gradstein; Min Li; Shu‐wen Tu; Xing Chen; Xue Yao; Shuang Gao; Rui‐ping Shi; Lu‐yan Tang; Ran Zhang; Zhao‐chen Zhang; et al. (Journal of Biogeography, 2025)
Aim Considering the importance of microclimate in maintaining the diversity of epiphytic bryophytes, we investigated epiphytic bryophytes along an elevational gradient in the subtropical forest of eastern China to unravel the diversity patterns of epiphytic liverworts and mosses along the elevational gradients and the roles of forest microclimates, topographic variables and host plant composition attributes in shaping these elevational diversity patterns. Location Tianmushan National Nature Reserve, Zhejiang, China. Taxon Epiphytic bryophytes. Methods Species diversity patterns of liverworts and mosses were compared based on an inventory of 16 plots along an elevational gradient from 367 to 1470 m. In situ microclimatic data of air temperature and moisture were collected under constant monitoring for over 3 years. Spatial linear models and structural equation models were used to assess the relative roles of the environmental variables in shaping the patterns of species diversity along elevation. Results We found that epiphytic liverwort and moss richness showed different elevational patterns; overall richness patterns of epiphytic bryophytes were largely driven by mosses. Epiphytic mosses exhibited a decline, followed by a hump‐shaped pattern of species richness with increasing elevation, while epiphytic liverworts showed a mid‐elevation plateau with a richness maximum between 800 and 1300 m. Forest microclimate, topography and host plant composition attributes influence epiphytic moss and liverwort patterns differently and interact in a complex way. Overall, species richness of epiphytic liverworts was most strongly affected by microclimate (mean annual air temperature of growing season) and of epiphytic mosses richness by topography (slope). Further, epiphytic liverwort species richness was more influenced by temperature than moisture. Main Conclusions This study highlights the importance of collecting climatic factors at a fine scale (microhabitats) for understanding the patterns and drivers of bryophyte diversity. Further, our findings demonstrate the differences between liverworts and mosses in terms of their response to different environments in the forest ecosystem.

U(VI) removal on polymer adsorbents: Recent development and future challenges - Yong-Gang Zhao; Li-Hui Chen; Ming-Li Ye; Wei-Si Su; Chao Lei; Xin-Jie Jin; Yin Lu (Critical Reviews in Environmental Science and Technology, 2025)

Monitoring investigation on impact of pile-based PV modules on several typical environmental elements in coastal mudflat intertidal zone - Yonghua Tan; Zipeng Qin; Yan Tian; Dui’an Lu; Qingying Zhao; Ming Gong; Xiaoyan Li (Environmental Monitoring and Assessment, 2025)

Growth, biochemical indexes, and intestinal microbiota response of red tilapia (Oreochromis spp.) under different densities and feeding frequencies in the land-based aquaculture tank - Yu-Xiang Xie; Jun-Neng Liang; Gen Kaneko; Lu-Ting Wen; Yi-Jian Li; Qui-Wei Ao; Li-Ming Huang; Qiong Yang; Zhen-Ping Liao; Xue-Ming Yang; Hong-ping Zhang; Lin-Yuan Jiang; et al. (Aquaculture, 2025)

Analysis of genetic diversity and population structure of Pinellia ternata using EST-SSR markers - Mingxing Wang; Rong Xu; Ming Luo; Xinyao Li; Lu Wei; Mi Lei; Dahui Liu; Yuhuan Miao (Journal of Applied Research on Medicinal and Aromatic Plants, 2025)

Dynamic thermal and mass transport in PEM fuel cells at elevated temperatures and pressures: A 3D model study - Qianqian Wang; Jixuan Lu; Weibo Zheng; Bing Li; Jim P. Zheng; Guomin Cui; Liang Hao; Pingwen Ming (Fuel, 2025)

Exploration of the impact of different drying methods on the quality of Gastrodia elata: A study based on drying kinetics and multidimensional quality evaluation - Ming-xuan Li; Bin Wang; Yu Li; Xin-ru Nie; Jing Mao; Qiang Guo; Nuo Xu; Rao Fu; Zhi-jun Guo; Xiao-li Zhao; Zhen-hua Bian; Tu-lin Lu; et al. (Food Chemistry, 2025)

Carbon catabolite repression during the simultaneous utilization of lignocellulose-derived sugars in lactic acid production: Influencing factors and mitigation strategies - Mingxi Li; Wenbin Zhu; Jiamei Fan; Ming Gao; Xiaona Wang; Chuanfu Wu; Ying Wang; Yuan Lu (Environmental Research, 2025)

Regional disparities in PPCPs contamination of urban wastewater treatment plants: Unveiling influential factors and ecological effects - Xing Chen; Xiaofei Lu; Jiahua Peng; Guijin Su; Jing Meng; Qianqian Li; Yukang Hua; Ming Hu; Bin Shi (Environmental Pollution, 2025)

Effect of materials types of water-land junction settings on soil bacterial community structure in Shanghai riverside ecological corridor - Wei Guan; Songshuo Li; Qing Wang; Chenyan Sha; Jinghua Su; Min Wang; Ming Nie; Meng Lu (Ecological Engineering, 2025)

Research on the dielectric properties of flexible β-CD/PVDF all-organic films - Ming Wang; Hongwei Lu; Bengang Li; Shijia Yang; Weitao Su (Carbohydrate Polymers, 2025)

Efficient transformation of starch food wastes into bio-based levulinate products over earth-abundant aluminum salts: Performances and economics - Ke-Ming Li; Jia-Yue Chen; Yao Xiao; Feng-Shuo Guo; Yao-Bing Huang; Qiang Lu (Biomass and Bioenergy, 2025)

Erroneous Differentiation of Tendon Stem/Progenitor Cells in the Pathogenesis of Tendinopathy: Current Evidence and Future Perspectives - Yucheng Gao; Hao Wang; Liu Shi; Panpan Lu; Guangchun Dai; Ming Zhang; Bowen Han; Mumin Cao; Yingjuan Li; Yunfeng Rui (Stem Cell Reviews and Reports, 2025)

Salinity affects C/N ratio through differential responses of carbon and nitrogen metabolism in mangrove Avicennia marina leaves revealed by combined analysis of transcriptome and metabolome - Jing Li; Ling-Yu Song; Ze-Jun Guo; Chao-Qun Xu; Lu-Dan Zhang; Ji-Cheng Wang; Han-Chen Tang; Ming-Jin Dai; Xue-Yi Zhu; Hai-Lei Zheng (Plant and Soil, 2025)

Intrasporangium zincisolvens sp. nov., A Novel Actinobacterium Isolated from Rhizosphere Soil - Lu-Yao Feng; Jiang‑Yuan Zhao; Zhu-Feng Shi; Ming‑Gang Li; Te Pu; Zhu-Li Shi; Xin Liu; Yu Wang; Le‑Le Li; Pei‑Wen Yang (Current Microbiology, 2025)

Influence of northward-propagating intraseasonal oscillations and ENSO background states on summer monsoon onset over the Arabian Sea and India - Tsung-Hsun Lin; Mong-Ming Lu; Tim Li (Climate Dynamics, 2025)

H-NS represses fliD transcription for lateral flagellar filament cap in Vibrio parahaemolyticus - Kui Liu; Min Chen; Jingyang Chang; Jing Yang; Daqing Wang; Xuefeng Ding; Ming Yang; Yiquan Zhang; Renfei Lu; Li Chen (Archives of Microbiology, 2025)

Influence of oxygen carrier on NOx and N2O emissions in biomass combustion within fluidized beds - Guang Sun; Lin Li; Dennis Lu; Ming Hu; Zhenkun Sun; Rongtao Wang; Yuqing Chen; Lunbo Duan (Process Safety and Environmental Protection, 2025)

The miR172a–SNB module orchestrates both induced and adult-plant resistance to multiple diseases via MYB30-mediated lignin accumulation in rice - He Wang; Zhe-Xu Wang; Hong-Yuan Tian; Yu-Long Zeng; Hao Xue; Wan-Ting Mao; Lu-Yue Zhang; Jun-Ni Chen; Xiang Lu; Yong Zhu; Guo-Bang Li; Zhi-Xue Zhao; et al. (Molecular Plant, 2025)

Simultaneous effects of nanoscale zero-valent iron on wastewater decontamination and energy generation: Mechanisms of sulfamethoxazole degradation and methanogenesis - Lingyun Zhou; Jibin Li; Xingcheng Lu; Weiming Zhang; Bingcai Pan; Ming Hua (Journal of Hazardous Materials, 2025)

Yeast community in the first-round fermentation of sauce-flavor Baijiu: Source, succession and metabolic function - Zheng-Pei Chen; Qian Cao; Tian-Tian Meng; Wei Shi; Xiao-Juan Zhang; Li-Juan Chai; Jin-Song Shi; Fu-Wei Chen; Song-Tao Wang; Su-Yi Zhang; Cai-Hong Shen; Zhen-Ming Lu; et al. (Food Research International, 2025)

Bioconversion of agriculture by-products with functionally enhanced Streptomyces sp. SCUT-3: Fish skin as a model - Jing-Tao Ni; Ming-Shu Zhang; De-lin Lu; Wen-jun Lu; Lei Wu; Zhen-dong Yang; Can Qin; Zhen-jie Dai; Zhi-wei Li; Wen-jing Feng; Hua-hong Cai; Jia-rui Zhang; et al. (Food Chemistry, 2025)

RDT-FragNet: A DCN-Transformer network for intelligent rock fragment recognition and particle size distribution acquisition - Mingze Li; Ming Chen; Wenbo Lu; Fengze Zhao; Peng Yan; Jie Liu (Computers and Geotechnics, 2025)

Multi-modal resonance of topological hybrid graphene foam for enhanced acoustic absorption - Chengqi Zhang; Wenhao Tong; Huasong Qin; Xin Ming; Lidan Wang; Yue Yu; Yi Mao; Jiahao Lu; Peng Li; Tongyang Shi; Kai Pang; Yingjun Liu; et al. (Chemical Engineering Journal, 2025)

The impeded film-formation kinetics with ameliorated carrier trap density to construct efficient as-cast organic solar cells through short multi-branched alkylthio chains strategy - Ling Li; Na Li; Jiefeng Hai; Shenzheng Gao; Hao Xu; Ming Luo; Xinjie Zhou; Xiaoyu Shi; Shanlei Xu; Xueming Li; Zhenhuan Lu; Youyong Pang; et al. (Chemical Engineering Journal, 2025)

Oriented bioconversion of food waste to lactic acid for external carbon source production: Microbial communities and comparison of denitrification performance - Haichuan Pan; Yuan Li; Wenbin Zhu; Chuanfu Wu; Ming Gao; Qunhui Wang; Ying Wang; Yuan Lu; Yi Rao; Chunjiang Yu (Bioresource Technology, 2025)

H-NS-Mediated Regulation of Swimming Motility and Polar Flagellar Gene Expression in Vibrio parahaemolyticus - Yue Zhou; Jingyang Chang; Feng Li; Mei He; Rui Li; Yaqin Hou; Yiquan Zhang; Renfei Lu; Ming Yang (Current Microbiology, 2025)

Life cycle assessment of hydrogenotrophic denitrification in membrane aerated biofilm reactors for sustainable wastewater treatment - Rui Li; Ming-yi Lu; Rong-bo Guo; Haoran Duan; Bing-jie Ni; Shan-fei Fu (Water Research, 2024)

Species-specific sensitivity to CuO nanoparticles: Establishing seawater quality criteria for Chinese marine ecosystems - De-chi Lu; Qing-Wei Li; Xin-Ming Pu; Heng Zhang; Lei Huang; Zhenguang Yan; Jin-Fen Pan (Science of The Total Environment, 2024)

Preconception exposure to bisphenol A and its alternatives: Effects on female fecundity mediated by oxidative stress and ovarian reserve - Wei Qiu; Shengju Yin; Kadila Abulaiti; Xinyu Li; Yao Lu; Qianlong Zhang; Ming Zhan; Jun Zhang (Science of The Total Environment, 2024)

A comprehensive genetic variant reference for the Chinese population - Tao Jiang; Hongzhe Guo; Yadong Liu; Gaoyang Li; Zhe Cui; Xinran Cui; Yue Liu; Yang Li; Anqi Zhang; Shuqi Cao; Tianyi Zhao; Liran Juan; et al. (Science Bulletin, 2024)

Partial nitrification-denitrification triggered the enhanced nitrogen removal in an integrated internal circulation aerated reactor - Ming Tao; Geng Li; Juan Mao; Feixiang Zan; Xiao Liu; Wei Zhang; Xiaohui Wu; Xiejuan Lu (Journal of Water Process Engineering, 2024)

Calcium regulates the physiological and molecular responses of Morus alba roots to cadmium stress - Ming-Jin Dai; Lu-Dan Zhang; Jing Li; Chun-Quan Zhu; Ling-Yu Song; He-Zi Huang; Chao-Qun Xu; Qing-Hua Li; Lin Chen; Chen-Kai Jiang; Hong-Ling Lu; Qiu-Tong Ling; et al. (Journal of Hazardous Materials, 2024)

Highly dispersed CuOx decorated ZnO photocatalyst for low-concentration methane removal - Yun Wang; Sheng Xu; Haiyuan Zhang; Yuyin Wang; Enmao Wang; Zeyu He; Jiahua Zhu; Xiaohua Lu; Lilong Zhang; Yang Bai; Kunfeng Zhao; Qingwei Gao; et al. (Journal of Environmental Chemical Engineering, 2024)

Mode of action underlying toxicity of Camptothecin to Spodoptera frugiperda (Lepidoptera) larvae - Jun-li Lv; Wen-qing Lai; Lei Pang; Xiao-ying Zhang; Kai-yi Zheng; Qiang Zhang; Zhan-peng Lu; Zhi-sheng Wang; Fasihul Lisan; Xue-yang Wang; Lu-feng Hu; Ming-jie Deng (Journal of Asia-Pacific Entomology, 2024)

Bridging real and simulated data for cross-spatial- resolution vegetation segmentation with application to rice crops - Yangmingrui Gao; Linyuan Li; Marie Weiss; Wei Guo; Ming Shi; Hao Lu; Ruibo Jiang; Yanfeng Ding; Tejasri Nampally; P. Rajalakshmi; Frédéric Baret; Shouyang Liu (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Selective production of phenol from the end-of-life wind turbine blade through catalytic pyrolysis - Ji-hong Li; Hao Jiang; Wei-wei Chen; Ya-chang Wu; Ming-xin Xu; Jin-yi Di; Wei Li; Qiang Lu (Fuel, 2024)

Volatilomics of Cabernet Sauvignon grapes and sensory perception of wines are affected by canopy side in vineyards with different row orientations - Hao-Cheng Lu; Meng-Bo Tian; Ning Shi; Hui-Qing Li; Ming-Yu Li; Chi-Fang Cheng; Wu Chen; Shu-De Li; Fei He; Chang-Qing Duan; Andrea Schubert; Jun Wang (Food Chemistry, 2024)

Seasonality shapes the microbiota and metabolome of strong-flavor Baijiu during fermentation and affects its flavor characteristics - Li-Juan Chai; Jing-Yi Zhang; Tao Gao; Long-Yun Zhang; Xiao-Juan Zhang; Zhen-Ming Lu; Jin-Song Shi; Xiang Chen; Zheng-Hong Xu (Food Bioscience, 2024)

Molecular cloning and gene expression of acc2 from grass carp (Ctenopharyngodon idella) and the regulation of glucose metabolism by ACCs inhibitor - Manxia Cao; Xinyuan Li; Lixue Dong; Hua Wen; Ming Jiang; Xing Lu; Feng Huang; Juan Tian (Molecular Biology Reports, 2024)

Peroxynitrite-Triggered Carbon Monoxide Donor Improves Ischemic Stroke Outcome by Inhibiting Neuronal Apoptosis and Ferroptosis - Xin-Jian Guo; Lin-Yan Huang; Shi-Tong Gong; Ming Li; Wan Wang; Jie Chen; Yi-De Zhang; Xicun Lu; Xiaohua Chen; Lan Luo; Youjun Yang; Xiao Luo; et al. (Molecular Neurobiology, 2024)

Solibacillus ferritrahens sp. nov., a novel siderophore-producing bacterium isolated from Wumeng Mountain National Nature Reserve in Yunnan Province - Xiao-Di Liu; Jiang-Yuan Zhao; Le-Le Li; Jian-Yu Li; Pei-Wen Yang; Song-Guo Liang; Lu-Yao Feng; Zhu-Feng Shi; Zhang-Gui Ding; Ming-Gang Li; Shu-Kun Tang (Antonie van Leeuwenhoek, 2024)

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

The role of Nocardia seriolae-induced autophagy in the development of chronic inflammation in the liver and the formation of granulomas in largemouth bass (Micropterus salmoides) - Shang-Jie Bai; Zheng-Ran Jian; Sheng-Yu He; Lin-Feng Kuang; Zheng-Yang Zhou; Chen-Wang Lu; Zhen-Dong Zhong; Jie He; Quan-Xin Xiong; Shuang-Yan Xiao; Peng-Fei Li; Ming-Zhu Liu; et al. (Aquaculture, 2024)

A high-performance electrochemical sensor based on dendritic Au/Zn modified carbon cloth for the determination of nitrite in aquaculture - Zhaoyang Zhang; Hao Li; Chao Duan; Guo Chen; Yiping Liu; Ming Lu (Science of The Total Environment, 2024)

Ozone production sensitivity analysis for the Chengdu Plain Urban Agglomeration based on a multi-site and two-episode observation - Ming Zhou; Yuhan Liu; Keding Lu; Dan Yu; Chunmeng Li; Tianyu Zhai; Suding Yang; Zhaofeng Tan; Xuefei Ma; Xin Li; Huabin Dong; Limin Zeng; et al. (Science of The Total Environment, 2024)

Recent selection and introgression facilitated high-altitude adaptation in cattle - Yang Lyu; Fuwen Wang; Haijian Cheng; Jing Han; Ruihua Dang; Xiaoting Xia; Hui Wang; Jincheng Zhong; Johannes A. Lenstra; Hucai Zhang; Jianlin Han; David E. MacHugh; et al. (Science Bulletin, 2024)

Sustainable protein/polysaccharide aerogel for the simultaneous and efficient removal of multiple organic contaminants: Insights from DFT calculations and phenomenological mass–transfer modeling - Ming-Xing Li; Yan-Shu Xiong; Qi-Qi Huang; Yi-Wen Luo; Wei Wei; Hai-Qin Lu; Fang-Xue Hang; Wen Li; Fujie Liu; Kai Li (Journal of Hazardous Materials, 2024)

Influence of freeze-thaw process on As migration and microorganisms in aggregates of paddy soil - Jinfeng Li; Xiaohui Lu; Ping Wang; Yong Yu; Long Sun; Ming Li (Journal of Environmental Management, 2024)

Decoding the Qu-aroma of medium-temperature Daqu starter by volatilomics, aroma recombination, omission studies and sensory analysis - Sheng-Bing Yang; Jun-Jie Fu; Jia-Huan He; Xiao-Juan Zhang; Li-Juan Chai; Jin-Song Shi; Song-Tao Wang; Su-Yi Zhang; Cai-Hong Shen; Zhen-Ming Lu; Zheng-Hong Xu (Food Chemistry, 2024)

Bio-derived modified halloysite nanotubes as eco-friendly flame retardants to endow epoxy with high thermal stability, mechanical performance and flame retardancy - Qing-Qing Bi; Ying-Ming Li; Lu He; De-Yi Wang (Chemical Engineering Journal, 2024)

Boosting charge separation and active sites exposure by hollow S-scheme MoSe2/Fe2O3 heterojunction for enhanced photocatalytic peroxymonosulfate activation towards ciprofloxacin removal - Lu Li; Cheng-Gang Niu; Hai Guo; Ya-Ya Yang; Hui-Yun Liu; Ming Yan (Chemical Engineering Journal, 2024)

Amine-functionalized soy protein/graphene oxide aerogel for efficient removal of multiple sugar-derived contaminants (SDCs): Full life cycle exploration and interaction simulation - Yan-Shu Xiong; Ming-Xing Li; Mei Li; Hai-Qin Lu; Yang Liu; Wei Wei; Yan-Hong Wei; Wen Li; Kai Li (Chemical Engineering Journal, 2024)

Inhibition of human and rat placental 3β-hydroxysteroid dehydrogenases by bisphenol A analogues depends on their hydrophobicity: In silico docking analysis - Shaowei Wang; Han Lu; Yingna Zhai; Yunbing Tang; Ming Su; Huitao Li; Yiyan Wang; Yi Liu; Ren-shan Ge (Chemico-Biological Interactions, 2024)

Assessment of Microseismic Events via Moment Tensor Inversion and Stress Evolution to Understand the Rupture of a Hard–Thick Rock Stratum - Jie-Fang Song; Cai-Ping Lu; Arno Zang; Xiu-Feng Zhang; Jian Zhou; Zhao-Wei Zhan; Li-Ming Zhao (Rock Mechanics and Rock Engineering, 2024)

Experimental Study on Temperature Variation in Saturated Warm Frozen Soil Under Dynamic Triaxial Conditions - Hongchun Li; Hu Zhang; Suiqiao Yang; Bo Zheng; Zheng Li; Jintao Hu; Ming Lu (Geotechnical and Geological Engineering, 2024)

From Skin to Gut: Understanding Microbial Diversity in Rana amurensis and R. dybowskii - Ming-he Yang; Hong Liu; Hao Wang; Zhao-ning Lu; Xiao-yun Han; Zhi-wen Luo; Li-gang Wu; Qing Tong (Current Microbiology, 2024)

Trichoderma harzianum promoting chrysanthemum cutting rooting and reshaping microbial communities in endophytic and rhizosphere environments - Ya-Jie Wu; Murad Muhammad; Yu Jiao; Xiu Chen; Hai-Long Wang; Chun-Mei Lu; Xiao-Ming Wang; Guo-Xing Zhu; Kai-Qing Liu; Yue Zhang; Zi-Chao Liu; Zhi-Xing Chen; et al. (Applied Soil Ecology, 2024)

Ecosystem risk-based prioritization of micropollutants in wastewater treatment plant effluents across China - Jianchao Liu; Tian Ouyang; Guanghua Lu; Ming Li; Yiping Li; Jun Hou; Chao He; Peng Gao (Water Research, 2024)

EtROP38 suppresses apoptosis of host cells infected with Eimeria tenella by inhibition of the p38MAPK pathway - Bu-ting Duan; Hao-yu Zhang; Zi-hao Song; Xiao-yi Han; Kai-ling Cui; Tong Xu; Yu Zhang; Yong-juan Zhao; Xuan Lei; Fan Tan; Lu-lu Guo; Hui-lin Yang; et al. (Veterinary Parasitology, 2024)

BrARR10 contributes to 6-BA-delayed leaf senescence in Chinese flowering cabbage by activating genes related to CTK, GA and ABA metabolism - Ci-mei Wang; Ze-xiang Zeng; Zong-li Liu; Jian-hua Zhu; Xin-guo Su; Ri-ming Huang; Wei Wei; Wei Shan; Jian-fei Kuang; Wang-jin Lu; Jian-ye Chen; Ying-ying Yang (Postharvest Biology and Technology, 2024)

Unraveling the mechanism of selective dissolution in anthracite coal for enhanced permeability through sodium hypochlorite oxidation treatment - Yu Lu; Yili Kang; Zhigang Li; Ming Yue; Teng Zhang; Feng He; Chong Lin; Yue Hu; Ying Li; Zhenjiang You (Fuel, 2024)

Deciphering the effects of different types of high-temperature Daqu on the fermentation process and flavor profiles of sauce-flavor Baijiu - Wei Shi; Li-Juan Chai; Han Zhao; Ya-Ning Song; Jun-Lan Mei; Yang-Xue He; Zhen-Ming Lu; Xiao-Juan Zhang; Bo Yang; Song-Tao Wang; Cai-Hong Shen; Zheng-Hong Xu (Food Bioscience, 2024)

Comparative genomics of Clostridium tyrobutyricum reveals signatures of environment-specific adaptation and metabolic potentials - Guan-Yu Fang; Li-Juan Chai; Zhen-Ming Lu; Xiao-Juan Zhang; Hong-Yu Xu; Song-Tao Wang; Cai-Hong Shen; Jin-Song Shi; Zheng-Hong Xu (Food Bioscience, 2024)

Impact of diatomit on the transport behavior of unmodified and carboxyl-modified nanoplastics in saturated porous media - Yuheng Wu; Ming Wu; Zhou Cheng; Yanru Hao; Cehui Mo; Qusheng Li; Jianfeng Wu; Jichun Wu; Bill X. Hu; Guoping Lu (Environmental Pollution, 2024)

Precise intramolecular-charge-transfer property modulation of D-A-type fluorescent probes for bifunctional detection of phosgene and nerve agent - Wenjing Liu; Kuo Lv; Chen Lu; Xin Miao; Chenxi Zhao; Feng Li; Ming Zhang (Chemical Engineering Journal, 2024)

Confined dual functionalized ionic liquids in metal-organic frameworks for selective NH3 adsorption - Haiyan Jiang; Li Xu; Kuilin Peng; Xiaoling Zhang; Shaojuan Zeng; Yangyang Guo; Lu Bai; Ming-Shui Yao; Xiangping Zhang (Chemical Engineering Journal, 2024)

Effects of aerosol on downward diffuse radiation under blowing dust and haze conditions - Huaping Li; Ming Zhang; Lunche Wang; Yunbo Lu; Lan Yu; Yingying Ma; Wei Gong (Atmospheric Environment, 2024)

Decoding the fish genome opens a new era in important trait research and molecular breeding in China - Qian Zhou; Jialin Wang; Jiongtang Li; Zhangfan Chen; Na Wang; Ming Li; Lei Wang; Yufeng Si; Sheng Lu; Zhongkai Cui; Xuhui Liu; Songlin Chen (Science China Life Sciences, 2024)

Dietary vitamin B6 could improve the utilization of high carbohydrate diet by promoting carbohydrate degradation and lipid synthesis in Pacific white shrimp (Litopenaeus vannamei) - Xinyue Tao; Tingting Zhu; Ming Li; Jingling Lu; Min Jin; Weijian Liu; Qicun Zhou (Animal Feed Science and Technology, 2024)

Integrated systematic functional screen and fine-mapping decipher the role and genetic regulation of RPS19 in colorectal cancer development - Can Chen; Wenzhuo Wang; Caibo Ning; Zequn Lu; Ming Zhang; Ying Zhu; Jianbo Tian; Haijie Li; Yue Ge; Beifang Yang; Xiaoping Miao (Archives of Toxicology, 2024)

Summer sea ice melting enhances phytoplankton and dimethyl sulfide production - Cheng‐Xuan Li; Kan Chen; Xia Sun; Lu Liu; Ming Xin; Xuan‐Li Liu; Bao‐Dong Wang (Limnology and Oceanography, 2024)
The relationships among sea ice melting, phytoplankton assemblages, and the production of climate‐relevant trace gases in the Southern Ocean are gaining increasing attention from the scientific community. This is particularly true for dimethyl sulfide (DMS), which plays an important role in atmospheric chemistry by influencing the formation of sulfated aerosols with radiative impacts and constituting cloud condensation nuclei. In the current study, chlorophyll a (Chl a ), DMS and its precursors dimethylsulfoniopropionate (DMSP), were quantified in the Weddell–Scotia Confluence (WSC) during the 2018 record ice extent minimum period. Mixed layer changes were found to be generally associated with spatial variation in sea ice melt, with the depth being six times deeper in ice‐free, well‐mixed regions than in seasonal ice‐melting zones. The surface Chl a concentration increased from ice‐free to ice‐melting regions with elevated sea ice meltwater percentages and drawdown surface nutrient concentrations. The concentrations of surface and depth‐integrated Chl a in the upper 150 m reached maxima in the ice‐melting region with the highest fraction of sea ice meltwater, illustrating that sea ice melting promoted the occurrence of phytoplankton blooms. The DMS and DMSP concentrations in the vicinity of the ice‐melting zone were approximately three times higher than those in the ice‐free waters. The observations of this study show that the regions of ice melting in the WSC were a zone of particularly high sea–air fluxes of DMS, which could significantly contribute to the atmospheric budget of DMS in the polar regions.

Inoculation of Saccharomyces cerevisiae for facilitating aerobic composting of acidified food waste - Puhong Yi; Qinping Li; Xueli Zhou; Ruiqi Liang; Xiaoyan Ding; Ming Wu; Kun Wang; Ji Li; Weixia Wang; Guangxin Lu; Tingheng Zhu (Environmental Science and Pollution Research, 2024)

The time-advance effect of China's rooftop solar photovoltaics program on the dual carbon targets and its implication on the globe - Hong-Wei Lu; Yi-Ming Yan; Dong-Zhe Liang; Xu Duan; Heng-Chen Li; Yun-Long Liu; Zhen-Jie Tang (Sustainable Cities and Society, 2024)

Influence of Chinese herbal plants on greenhouse gas emissions from pig manure composting and fermentation - Ya-jun Duan; Hong-sheng Wu; Guang-yao Chen; Feng-yi Hu; Yan-hui Li; Zhen-wei Li; Jin-he Chi; Dong-ming Lu; Xiao-ming Gu; Ming-chun Di (International Biodeterioration & Biodegradation, 2024)

Copper/Cobalt based metal phosphide composites as positive material for supercapacitors - Hao Zhou; Ramzi Nasser; Lu Zhang; Zhou Li; Feng Li; Ji-Ming Song (Chemical Engineering Journal, 2024)

Manipulating d-band center of bimetallic Sn-alloy coupling with carbon nanofibers for high-performance electrocatalytic production of ammonia from nitrate - Ruikai Qi; Qiuling Jiang; Mengxiao Zhong; Weimo Li; Siyu Ren; Ying Wang; Ming Feng; Xiaofeng Lu (Chemical Engineering Journal, 2024)

Micafungin protects mouse heart against doxorubicin-induced oxidative injury via suppressing MALT1-dependent k48-linked ubiquitination of Nrf2 - Li-Qun Lu; Ming-Rui Li; Lin-Lu Huang; Yan-Xi Che; Ya-Nan Qi; Xiu-Ju Luo; Jun Peng (Chemico-Biological Interactions, 2024)

Dietary chitosan reversed the toxic effects of polystyrene microplastics on Nile tilapia (Oreochromis niloticus) liver by inhibiting mitochondrial damage - Di Wu; Xing Lu; Li-Xue Dong; Juan Tian; Hua Wen; Shan Zhong; Yun-feng Li; Ming Jiang (Reviews in Fish Biology and Fisheries, 2024)

Convergent Neuroimaging and Molecular Signatures in Mild Cognitive Impairment and Alzheimer’s Disease: A Data-Driven Meta-Analysis with N = 3,118 - Xiaopeng Kang; Dawei Wang; Jiaji Lin; Hongxiang Yao; Kun Zhao; Chengyuan Song; Pindong Chen; Yida Qu; Hongwei Yang; Zengqiang Zhang; Bo Zhou; Tong Han; et al. (Neuroscience Bulletin, 2024)
The current study aimed to evaluate the susceptibility to regional brain atrophy and its biological mechanism in Alzheimer’s disease (AD). We conducted data-driven meta-analyses to combine 3,118 structural magnetic resonance images from three datasets to obtain robust atrophy patterns. Then we introduced a set of radiogenomic analyses to investigate the biological basis of the atrophy patterns in AD. Our results showed that the hippocampus and amygdala exhibit the most severe atrophy, followed by the temporal, frontal, and occipital lobes in mild cognitive impairment (MCI) and AD. The extent of atrophy in MCI was less severe than that in AD. A series of biological processes related to the glutamate signaling pathway, cellular stress response, and synapse structure and function were investigated through gene set enrichment analysis. Our study contributes to understanding the manifestations of atrophy and a deeper understanding of the pathophysiological processes that contribute to atrophy, providing new insight for further clinical research on AD.

Overexpression of the MiAGL1 gene from mango promoted flowering in transgenic Arabidopsis - Xue-mei Zeng; Xin-hua He; Wen-jing Mo; Hai-xia Yu; Ting-ting Lu; Li-ming Xia; Yi-li Zhang; Jia-wei Zhu; Cong Luo (Journal of Plant Biochemistry and Biotechnology, 2024)

A Hybrid Dung Beetle Optimization Algorithm with Simulated Annealing for the Numerical Modeling of Asymmetric Wave Equations - Xu-ruo Wei; Wen-lei Bai; Lu Liu; You-ming Li; Zhi-yang Wang (Applied Geophysics, 2024)

Application of the Conditional Nonlinear Local Lyapunov Exponent to Second-Kind Predictability - Ming Zhang; Ruiqiang Ding; Quanjia Zhong; Jianping Li; Deyu Lu (Advances in Atmospheric Sciences, 2024)

Inflammatory biomarkers mediate the association between polycyclic aromatic hydrocarbon exposure and dyslipidemia: A national population-based study - Jiaqi Chen; Yurong Zhang; Ruijie Wu; Zilin Li; Tongchao Zhang; Xiaorong Yang; Ming Lu (Chemosphere, 2024)

The role of Pleistocene dispersal in shaping species richness of sky island wintergreens from the Himalaya-Hengduan Mountains - Xiao-Juan Cheng; Peter W. Fritsch; Yan-Jun Lin; Guo-Hong Li; Yan-Quan Chen; Ming-Ying Zhang; Lu Lu (Molecular Phylogenetics and Evolution, 2024)

Investigation of high-risk antibiotic resistance bacteria and their associated antibiotic resistance genes in different agricultural soils with biogas slurry from China - Yi Lu; Junhui Wu; Jiwei Li; Zailin Du; Changai Zhang; Yanjun Chai; Zewen Jin; Zichuan Li; Jun Meng; Haifeng Zhuang; Lifeng Ping; Ming Hung Wong; et al. (Journal of Hazardous Materials, 2024)

Spatiotemporal variations and risk assessment of estrogens in the water of the southern Bohai Sea: A comprehensive investigation spanning three years - Shuang Lu; Jing Wang; Baodong Wang; Ming Xin; Chunye Lin; Xiang Gu; Maoshan Lian; Yun Li (Journal of Hazardous Materials, 2024)

Elemental differentiation and isotopic fractionation during space weathering of Chang’E-5 lunar soil - Qingshang Shi; Yongsheng He; Jian-Ming Zhu; Yang Wang; Yang Wang; Hongjie Wu; Peijie Wang; Ruyi Yang; Aiying Sun; Yinchu Zhang; Guangliang Wu; Ruoqi Wan; et al. (Geochimica et Cosmochimica Acta, 2024)

Comparative analysis of physicochemical properties and biological activities of crude polysaccharides isolated from selected Auricularia cornea strains - Asif Ali Khan; Fang-Jie Yao; Feng-Jie Cui; Yu Li; Lixin Lu; Ismail Khan; Abdul Jalal; Ming Fang; Khulood Fahad Alabbosh; Mohamed F. Awad; Noureddine Elboughdiri; Muhammad Wajid Ullah (Food Bioscience, 2024)

Conformational transformation of activator strand directly regulates CRISPR/Cas12a system activity for live cell sensing of multiple biomolecules - Qing-Nan Li; Dong-Xia Wang; Zhi-Qi Dai; Shun-Li Wu; Gui-Mei Han; Sha Lu; Li-Na Zhu; Hong-Xin Jiang; De-Ming Kong (Chemical Engineering Journal, 2024)

Towards Stem/Progenitor Cell-Based Therapies for Retinal Degeneration - Hui Liu; Shuaiyan Lu; Ming Chen; Na Gao; Yuhe Yang; Huijuan Hu; Qing Ren; Xiaoyu Liu; Hongxu Chen; Qunyan Zhu; Shasha Li; Jianzhong Su (Stem Cell Reviews and Reports, 2024)

Mitigation Effect of Exogenous Dopamine Treatment on Downy Mildew-Infected Cucumber - Ze-Yu Ji; Ze-Yu Liu; Li-Ming Shi; Xin-Yu Lu; Yu-Ying Han; Yan Sun (Journal of Plant Growth Regulation, 2024)

Replacing soybean meal with fermented rapeseed meal in diets: potential effects on growth performance, antioxidant capacity, and liver and intestinal health of juvenile tilapia (Oreochromis niloticus) - Yaxue Li; Xing Lu; Lixue Dong; Di Peng; Jianmin Zhang; Zongbin Cui; Hua Wen; Juan Tian; Ming Jiang (Fish Physiology and Biochemistry, 2024)

Phylogenetic origin of an insect fauna at the boundary of the Palaearctic and Oriental realms: Evidence from ‘site‐based’ mitogenomics - Rui‐E Nie; Lu‐Lu Li; Anderson Feijó; Mei‐Xia Yang; Ming Bai; Thomas J. Creedy; Xu Jin; Jia‐Sheng Hao; Yong‐Ying Ruan; Hua‐Xi Liu; Beulah H. Garner; Ladislav Bocak; et al. (Journal of Biogeography, 2024)
Aim Knowledge of taxonomy and species distributions in highly diverse lineages of invertebrates remains too incomplete for the study of biogeographical patterns at the global scale. This limits the understanding of processes leading to the formation and maintenance of boundaries between major biogeographical realms. Site‐based metagenomic approaches may provide an alternative source of data for inference of historical processes of in situ speciation and interchange among biogeographical regions. We applied the methodology to explore the historical biogeography of the Qinling Mountains at the boundary of the Oriental and Palaearctic regions. Location The focal area in the Qinling Mountains; sites in Borneo, Panama, and Spain, representing the Oriental, Neotropical and Palaearctic faunas. Time Period Contemporary. Major Taxa Studied Chrysomelidae, a group of ~40,000 species with worldwide distribution. Methods Mass‐trapped insects were subjected to deep Illumina DNA sequencing and mitochondrial genome assembly, followed by phylogenetic analysis and historical biogeographical inference on a dated tree. The methodology produced 622 mitogenomes (304 newly sequenced) each representing a morphologically distinct species. Results Ancestral area reconstruction revealed that the Qinling fauna is a composite of distinct clades that, respectively, have Oriental or Palaearctic ancient origins, while in situ speciation and local clade formation were limited. The global diversity of Chrysomelidae consists of regionalised deep clades at the level of the major zoogeographic realms, which remain recognisable where these realms abut in the Qinling mountains. Yet, the Qinling fauna is clearly distinct from the source areas although local lineage ages are generally Main Conclusions The Qinling fauna is a composite of clades that have either Oriental or Palaearctic origin, indicating the important role of immigration at the realm boundary. Global site‐based phylogenetic analyses based on metagenomic sequencing can address previously intractable questions about the historical biogeography of poorly studied groups even without a fully developed taxonomy.

Correction to: Association of sudden sensorineural hearing loss with meteorological factors: a time series study in Hefei, China, and a literature review - Xiao‑Bo Li; Yan‑Xun Han; Zi‑Yue Fu; Yu‑Chen Zhang; Min Fan; Shu‑Jia Sang; Xi‑Xi Chen; Bing‑Yu Liang; Yu‑Chen Liu; Peng‑Cheng Lu; Hua‑Wei Li; Hai‑Feng Pan; et al. (Environmental Science and Pollution Research, 2024)

Mitochondrial damage and activation of NLRP3 induced by Yersinia ruckeri infection play an important role in the occurrence of diffuse acute inflammation of channel catfish (Ictalurus punctatus) - Chen-Wang Lu; Jie He; Quan-Xin Xiong; Zhen-Dong Zhong; Bin Yang; Sheng Lian; Meng-Meng Wang; Shang-Jie Bai; Lin-Feng Kuang; Zheng-Yang Zhou; Zheng-Ran Jian; Yuan-Chang Gao; et al. (Aquaculture, 2024)

Recovering carbon fibers from waste CFRPs via pyrolysis-oxidation method: Implications for reuse in remanufactured materials - Ming-xin Xu; Xiang-xi Meng; Qi-si Li; Wei-wei Chen; Hong-ji Xue; Hao Jiang; Hai-wen Ji; Qiang Lu (Waste Management, 2024)

Comparison and improvement of energy balance establishment methods for heat pretreatment prior to anaerobic digestion - Ming Wang; Kai Liu; Jianlin Wang; Yunting Li; Hao Peng; Lu Ding (Fuel, 2024)

Dietary cholesterol intervention could alleviate the intestinal injury of Oreochromis niloticus induced by plant-based diet via the intestinal barriers - Jiayuan Jiang; Xing Lu; Li-Xue Dong; Di Peng; Jian-Min Zhang; Juan Tian; Hua Wen; Ming Jiang (Fish & Shellfish Immunology, 2024)

Newly graphene/polypyrrole (rGO/PPy) modified carbon felt as bio-cathode in bio-electrochemical systems (BESs) achieving complete denitrification - Yue-Jia Yang; Shuai Wang; Da Kang; Xin Lu; Zi-Chang Lu; Zhuo-Chao Liu; Li-Ming Yang; Dan Cui (Environmental Research, 2024)

Bioconcentration, oxidative stress and molecular mechanism of the toxic effect of acetamiprid exposure on Xenopus laevis tadpoles - Hong Chen; Ya Yang; Lina Ai; Lanying Li; Renyue Ming; Ping Lu (Aquatic Toxicology, 2024)

LbCOPT1 is a copper transporter induced in Lycium barbarum mycorrhizal roots, which allows tobacco with improved growth and nutrient uptake - Yuhao Zhou; Yuning Li; Jingru Jia; Yinjun Lu; Beijia Feng; Ming Tang; Haoqiang Zhang (Plant Cell Reports, 2024)

Direct Ischemic Postconditioning Following Stroke Thrombectomy: A Promising Therapy for Reperfusion Injury - Jing Wang; Lu Yang; Longfei Wu; Sijie Li; Changhong Ren; Yuchuan Ding; Ming Wei; Xunming Ji; Wenbo Zhao (Neuroscience Bulletin, 2024)

Potential Plausible Role of Stem Cell for Treating Depressive Disorder: a Retrospective Review - Zhuo Chang; Qing-yi Wang; Lu-hao Li; Bei Jiang; Xue-ming Zhou; Hui Zhu; Yan-ping Sun; Xue Pan; Xu-xu Tu; Wei Wang; Chen-yue Liu; Hai-xue Kuang (Molecular Neurobiology, 2024)

Association of sudden sensorineural hearing loss with meteorological factors: a time series study in Hefei, China, and a literature review - Xiao-Bo Li; Yan-Xun Han; Zi-Yue Fu; Yu-Chen Zhang; Min Fan; Shu-Jia Sang; Xi-Xi Chen; Bing-Yu Liang; Yu-Chen Liu; Peng-Cheng Lu; Hua-Wei Li; Hai-Feng Pan; et al. (Environmental Science and Pollution Research, 2024)
Air pollution can cause disease and has become a major global environmental problem. It is currently believed that air pollution may be related to the progression of SSNHL. As a rapidly developing city in recent years, Hefei has serious air pollution. In order to explore the correlation between meteorological variables and SSNHL admissions, we conducted this study. This study investigated the short-term associations between SSNHL patients admitted to the hospital and Hefei climatic variables. The daily data on SSNHL-related hospital admissions and meteorological variables containing mean temperature (T-mean; °C), diurnal temperature range (DTR; °C), atmospheric pressure (AP; Hp), and relative humidity (RH; %), from 2014 to 2021 (2558 days), were collected. A time-series analysis integrating distributed lag non-linear models and generalized linear models was used. PubMed, Embase, Cochrane Library, and Web of Science databases were searched. Literature published up to August 2023 was reviewed to explore the potential impact mechanisms of meteorological factors on SSNHL. The mechanisms were determined in detail, focusing on wind speed, air pressure, temperature, humidity, and air pollutants. Using a median of 50.00% as a baseline, the effect of exceedingly low T-mean in the single-day hysteresis effect model began at a lag of 8 days (RR = 1.032, 95% CI: 1.001 ~ 1.064). High DTR affected the admission rate for SSNHL on lag 0 day. The significance of the effect was the greatest on that day (RR = 1.054, 95% CI: 1.007 ~ 1.104) and then gradually decreased. High and exceedingly high RH affected the admission rate SSNHL on lag 0 day, and these effects lasted for 8 and 7 days, respectively. There were significant associations between all grades of AP and SSNHL. This is the first study to assess the effect of meteorological variables on SSNHL-related admissions in China using a time-series approach. Long-term exposures to high DTR, RH values, low T-mean values, and all AP grades enhance the incidence of SSNHL in residents. Limiting exposure to extremes of ambient temperature and humidity may reduce the number of SSNHL-related hospital visits in the region. It is advisable to maintain a suitable living environment temperature and avoid extreme temperature fluctuations and high humidity. During periods of high air pollution, it is recommended to stay indoors and refrain from outdoor exercise.

Bioaccessibility and human health risks of arsenic from geological origin in lateritic red soil on construction land - Lu-Yao Ding; Guang-Yong Tang; Ming-Zhu Chen; Fo-Peng Wang; Jun-Feng Wang; Han-Jie Ye; Qu-Sheng Li (Chemosphere, 2024)

Neoarchean clockwise P-T trajectories with evolution sequence from HP to UHT metamorphism during decompression: Evidence from petrology, mineralogy, and phase equilibria modeling of mafic granulites in the Sittampundi Complex, southern India - Xu Kong; Jun-Sheng Lu; Ming-Guo Zhai; Cheng-Li Zhang; M.P. George; Long-Long Gou; Yan Zhao; Wen-Hao Ao; Yu-Hua Hu; Qiang Feng; Gang Liu (Precambrian Research, 2024)

The Janus kinase/signal transducers and activators of transcription (JAK/STAT) pathway contributes to the defense against bacterial infection in the pea aphid - Yu-Jie Zhao; Yue-Ming Li; Ting Yang; Zhiqiang Lu (Pesticide Biochemistry and Physiology, 2024)

A prospective cohort study of exposure to household pesticide with cardiovascular diseases mortality in older adults - Xiyao Zhao; Jiayuan Li; Yongqi Liu; Yunjie Liu; Xia Jiang; Lu Long; Jintao Wang; Yuqing Yao; Qin Zhang; Ming Li; Xiaomeng Li; Ben Zhang; et al. (Journal of Hazardous Materials, 2024)

Lotus pollen-derived nitrogen and phosphorus self-doped TiO2/carbon materials for photoelectrochemical application - Rui Chen; Ying-Ying Wang; Xia Jiang; Ming-Hao Ji; Ke-Xian Li; Hao-Yan Shi; Hai-Long Wang; Yan-Xin Chen; Can-Zhong Lu (Journal of Environmental Chemical Engineering, 2024)

Preparation of slag-based foam concrete and its carbon dioxide sequestration performance - Jing Zhao; Yu-qing Li; Jing-jing Yang; Xiao-qiang Cao; Jun-xiang Wang; Gang Wang; Lu-lu Sun; Qi-ming Huang; Wei-min Cheng; Zhi-wen Lyu (International Journal of Greenhouse Gas Control, 2024)

Nonionic surfactant Tween 80-facilitated bacterial transport in porous media: A nonmonotonic concentration-dependent performance, mechanism, and machine learning prediction - Dong Zhang; Jiacheng Jiang; Huading Shi; Li Lu; Ming Zhang; Jun Lin; Ting Lü; Jingang Huang; Zhishun Zhong; Hongting Zhao (Environmental Research, 2024)

Significance of non-DLVO interactions on the co-transport of levofloxacin and titanium dioxide nanoparticles in porous media - Yiqun Cui; Ming Wu; Guoping Lu; Zhou Cheng; Meng Chen; Yanru Hao; Cehui Mo; Qusheng Li; Jianfeng Wu; Jichun Wu; Bill X. Hu (Environmental Pollution, 2024)

Hydrophobic sisal cellulose paper-based TENG for collecting rain energy and raindrop-based sensor - Yating Pan; Ming Li; Yuxiang Lu; Manli Lu; Bin Guo; Xianming Liu; Kaiyou Zhang; Yu Wang; Liang Feng; Aimiao Qin (Chemical Engineering Journal, 2024)

Preparation of crab-shell-based N, O co-doped graded porous carbon for supercapacitors using the confined nanospace deposition method - Yiming Li; Zhihao Yu; Mengyan Guo; Ming Zhang; Jian Xiong; Yina Qiao; Rui Zhang; Xuebin Lu (Waste Disposal & Sustainable Energy, 2024)

Delayed Chronic Acidic Postconditioning Improves Poststroke Motor Functional Recovery and Brain Tissue Repair by Activating Proton-Sensing TDAG8 - Yan-Ying Fan; Yu Li; Xiao-Ying Tian; Ying-Jing Wang; Jing Huo; Bao-Lu Guo; Ru Chen; Cai-Hong Yang; Yan Li; Hui-Feng Zhang; Bao-Long Niu; Ming-Sheng Zhang (Translational Stroke Research, 2024)

Co4+ in porous ZIF-67-derives intercalating-bridging adsorption of 2-reaction sites for simultaneous 2-electron transfer toward sensitive detection of uric acid - Li Peng Gan; Juan Li; Fan Shi; Zhuo Zou; Ke Jiang Li; Zhuan Zhuan Shi; Xiao Shuai Wu; Yun Peng Li; Wei Sun; Zhi Song Lu; Tao Hu; Liming Dai; et al. (Analytica Chimica Acta, 2024)

A Four Amino Acid Metabolism-Associated Genes (AMGs) Signature for Predicting Overall Survival Outcomes and Immunotherapeutic Efficacy in Hepatocellular Carcinoma - Lu-sheng Liao; Zi-jun Xiao; Jun-li Wang; Ting-jun Liu; Feng-die Huang; Yan-ping Zhong; Xin Zhang; Ke-heng Chen; Run-lei Du; Ming-you Dong (Biochemical Genetics, 2024)

Fault and lithology interpretation for the northern coastal zone of Taizhou based on aeromagnetic data - Ming Wang; Jiao-jiao Li; Yong-jun Zhang; Yi-chuan Li; Lu-ping Xu (Applied Geophysics, 2024)

Mycorrhizal associations relate to stable convergence in plant–microbial competition for nitrogen absorption under high nitrogen conditions - Zhenggang Du; Lingyan Zhou; Madhav P. Thakur; Guiyao Zhou; Yuling Fu; Nan Li; Ruiqiang Liu; Yanghui He; Hongyang Chen; Jie Li; Huimin Zhou; Ming Li; et al. (Global Change Biology, 2024)
Nitrogen (N) immobilization (Nim, including microbial N assimilation) and plant N uptake (PNU) are the two most important pathways of N retention in soils. The ratio of Nim to PNU (hereafter Nim:PNU ratio) generally reflects the degree of N limitation for plant growth in terrestrial ecosystems. However, the key factors driving the pattern of Nim:PNU ratio across global ecosystems remain unclear. Here, using a global data set of 1018 observations from 184 studies, we examined the relative importance of mycorrhizal associations, climate, plant, and soil properties on the Nim:PNU ratio across terrestrial ecosystems. Our results show that mycorrhizal fungi type (arbuscular mycorrhizal (AM) or ectomycorrhizal (EM) fungi) in combination with soil inorganic N mainly explain the global variation in the Nim:PNU ratio in terrestrial ecosystems. In AM fungi‐associated ecosystems, the relationship between Nim and PNU displays a weaker negative correlation ( r = −.06, p r = .25, p

The potential use of Zymomonas mobilis for the food industry - Lu Liu; Jian-Ting Li; Sheng-Hao Li; Lin-Pei Liu; Bo Wu; Yan-Wei Wang; Shi-hui Yang; Cheng-Han Chen; Fu-Rong Tan; Ming-Xiong He (Critical Reviews in Food Science and Nutrition, 2024)

Antihypertensive treatment during pregnancy induces long-term changes in gut microbiota and the behaviors of the attention deficit hyperactivity disorder offspring - Hong-Bao Li; Meng-Lu Xu; Wen-Jie Xia; Yuan-Yuan Dong; Bo Peng; Qing Su; Xiao-Min Wang; Jia-Yue Yu; Ya-Nan Gao; Jun-Zhe Wu; Meng-Yue Xu; Jin-Bao Yang; et al. (Toxicology and Applied Pharmacology, 2024)

Corrigendum to “Effects and mechanisms of polycyclic aromatic hydrocarbons in inflammatory skin diseases” [Sci. Total Environ. 925 171492] - Hui Jin; Ziyuan Lin; Tianyi Pang; Jingwen Wu; Cheng Zhao; Ying Zhang; Yu Lei; Qilin Li; Xu Yao; Ming Zhao; Qianjin Lu (Science of The Total Environment, 2024)

Environmental exposure to polycyclic aromatic hydrocarbons: An underestimated risk factor for systemic lupus erythematosus onset and progression - Hui Jin; Cheng Zhao; Yiran Chen; Ying Zhang; Zeng Yong; Yu Lei; Qilin Li; Xu Yao; Ming Zhao; Qianjin Lu (Science of The Total Environment, 2024)

Effects and mechanisms of polycyclic aromatic hydrocarbons in inflammatory skin diseases - Hui Jin; Ziyuan Lin; Tianyi Pang; Jingwen Wu; Cheng Zhao; Ying Zhang; Yu Lei; Qilin Li; Xu Yao; Ming Zhao; Qianjin Lu (Science of The Total Environment, 2024)

Multi-failure theory of non-uniformly ring-stiffened composite shells under hydrostatic pressure [Ocean Eng. 299, May 2024] - Ming Li; Lu Zhang; Boen Huang; Hengyi Zhu; Hualin Fan (Ocean Engineering, 2024)

Multi-failure theory of non-uniformly ring-stiffened composite shells under hydrostatic pressure - Ming Li; Lu Zhang; Boen Huang; Hengyi Zhu; Hualin Fan (Ocean Engineering, 2024)

Endophytic bacteria for Cd remediation in rice: Unraveling the Cd tolerance mechanisms of Cupriavidus metallidurans CML2 - Yuan Zhang; Qi Zhou; Chang Gao; Yue Lu; Yang Sheng; Ming Xiao; Yueli Yun; Jonathan Nimal Selvaraj; Xianhua Zhang; Yadong Li; Xuejing Yu (Journal of Hazardous Materials, 2024)

Decoding the genome of bloodsucking midge Forcipomyia taiwana (Diptera: Ceratopogonidae): Insights into odorant receptor expansion - Ming-Der Lin; Chia-Hsien Chuang; Chih-Hsin Kao; Shu-Hwa Chen; Szu-Chieh Wang; Ping-Heng Hsieh; Guan-Yu Chen; Chun-Chia Mao; Jeng-Yi Li; Mei-Yeh Jade Lu; Chung-Yen Lin (Insect Biochemistry and Molecular Biology, 2024)

E-eye and FT-NIR combined with multivariate algorithms to rapidly evaluate the dynamic changes in the quality of Gastrodia elata during steaming process - Jiu-ba Zhang; Bin Wang; Yun-fei Zhang; Yi Wu; Ming-xuan Li; Ting Gao; Tu-lin Lu; Zhen-hua Bian; Lian-lin Su (Food Chemistry, 2024)

Li10GeP2S12-based solid electrolyte induced by high pressure for all-solid-state batteries: A facile strategy of low-grain-boundary-resistance - Junkai Zhang; Juncheng Lv; Wei Lu; Xin Li; Yang Liu; Jihui Lang; Jia Liu; Zhao Wang; Ming Lu; Hao Sun (Chemical Engineering Journal, 2024)

Strong Lewis acid-induced self-healing of loose FeOOH for alkaline oxygen evolution - Ning Yu; Jing Yi Lv; Zi-Chuan Guo; Xin-Jie Tian; Yu-Sheng Zhang; Wen-Jing Li; Yu-Lu Zhou; Yong-Ming Chai; Bin Dong (Chemical Engineering Journal, 2024)

Inhibition of PARP1 improves cardiac function after myocardial infarction via up-regulated NLRC5 - Jia-Ming Luo; Hong-Bin Lin; Ya-Qian Weng; Ying-Hui Lin; Lu-Ying Lai; Ji Li; Feng-Xian Li; Shi-Yuan Xu; Hong-Fei Zhang; Wei Zhao (Chemico-Biological Interactions, 2024)

Maintenance of callus-associated endophyte balance to mitigate oxidative browning in plant tissue culture practices - Yu-Tao Wang; Chun-Xiao Chen; Ping Zhou; Chun-Xi Lu; Yun Wen; Yu Li; Xiao-Xia Pan; Shu-Sheng Zhu; Ming-Zhi Yang (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Socio-scientific quantification of the comprehensive benefits of debris flow mitigation measures for villages in western Sichuan, China - Ting Deng; Pei Xu; Ming Li; Yafeng Lu; Yukuan Wang; Zhengyang Li; Kumar Ghimire Shravan (Journal of Mountain Science, 2024)

Changes in size-dependent Chlorophyll a concentration and group-specific picophytoplankton abundance in short-term nutrient-addition experiments in the Equatorial Eastern Indian Ocean - Ping Sun; Kai-Ming Sun; Yuping Zhou; Lu Liu; Chao Yuan; Zongjun Xu; Yan Li; Xuelei Zhang; Zongling Wang (Frontiers in Marine Science, 2024)
To clarify the changes in phytoplankton community and influencing factors in short-term nutrient-addition experiments in the Equatorial Eastern Indian Ocean, we conducted three experiments (one in situ-like experiment, one on-deck experiment with deep seawater, and one on-deck experiment with surface seawater). Our findings indicate that when nutrients were added, there was a more significant increase in the chlorophyll a (chl a ) concentrations of microphytoplankton (>20 μm) compared to those of nanophytoplankton (2-20 μm) and picophytoplankton (<2 μm). The chl a concentrations for phytoplankton <20 μm only exhibited significant increases in the on-board incubation of surface seawater collected at 1300 hr when grazing stress have likely been weak. In picophytoplankton, occasional increases in the abundances of Synechococcus were found, while the abundances of Prochlorococcus and eukaryotic picophytoplankton (Peuk) did not increase significantly. It results likely from the preference of grazing effect by herbivores and bottle effects. Additionally, the Prochlorococcus from 75 m was more adapted to weak light, thus its abundance sharply decreased when incubated under high light. We suggest that the nutrient effects have greater influence on microphytoplankton, but other factors, such as grazing and light, might contribute more to <20 μm phytoplankton. Furthermore, bottle effects should be considered when conducting incubation experiments.

Petrogenetic link between leucogranite and spodumene pegmatite in Lhozhag, eastern Himalaya: Constraints from U–(Th)–Pb geochronology and Li–Nd–Hf isotopes - Lei Yang; Jia-Min Wang; Xiao-Chi Liu; Fang-Yang Hu; Kang-Shi Hou; Jian-Gang Fu; Guang-Ming Li; Yu-Lu Tian; Fu-Yuan Wu (Lithos, 2024)

Microbial consortium degrading of organic pollutants: Source, degradation efficiency, pathway, mechanism and application - Huixiong Lü; Jia-Lu Wei; Guang-Xuan Tang; Yao-Si Chen; Yu-Hong Huang; Ruiwen Hu; Ce-Hui Mo; Hai-Ming Zhao; Lei Xiang; Yan-Wen Li; Quan-Ying Cai; Qing X. Li (Journal of Cleaner Production, 2024)

Demethoxylation of curcumin enhances its inhibition on human and rat 17β-hydroxysteroid dehydrogenase 3: QSAR structure-activity relationship and in silico docking analysis - Zhongyao Ji; Jianmin Sang; Hong Wang; Miaomiao Xia; Ting Hao; Liping Chen; Han Lu; Shaowei Wang; Ming Yao; Linxi Li; Ren-shan Ge (Food and Chemical Toxicology, 2024)

Chronic Aroclor 1260 exposure alters the mouse liver proteome, selenoproteins, and metals in steatotic liver disease - Kellianne M. Piell; Belinda J. Petri; Jason Xu; Lu Cai; Shesh N. Rai; Ming Li; Daniel W. Wilkey; Michael L. Merchant; Matthew C. Cave; Carolyn M. Klinge (Environmental Toxicology and Pharmacology, 2024)

Citric acid/chitosan adhesive with viscosity-controlled for wood bonding through supramolecular self-assembly - Lijian Cai; Yutong Chen; Zetan Lu; Ming Wei; Xin Zhao; Yanjun Xie; Jian Li; Shaoliang Xiao (Carbohydrate Polymers, 2024)

Effects of Dietary Fish Meal Replaced by Cottonseed Protein Concentrate on Growth Performance, Antioxidant Capacity, and Liver and Intestinal Health of Juvenile Hybrid Culter - Guangming Xu; Huijie Wei; Di Peng; Lang Zhang; Xing Lu; Qing Li; Lixue Dong; Juan Tian; Hua Wen; Guiying Wang; Ming Jiang (Fishes, 2024)
The objective of this study was to assess the impact of concentrated cottonseed protein (CPC) as a substitute for fishmeal (FM) in juvenile hybrid culter (Erythroculter ilishaeformis ♀ × Ancherythroculter nigrocauda ♂). A total of 360 fish with an initial body weight of 10.0 ± 0.5 g were randomly allocated into 12 indoor culture tanks, with each tank containing 30 fish. Four diets were formulated in which fish meal (FM) was replaced by CPC at different inclusion levels: 0% (T0), 15% (T15), 30% (T30), and 45% (T45). The corresponding amounts of CPC included were 0, 61, 122, and 182 g/kg, respectively. At the end of the 10-week feeding trial, the findings revealed an inverse correlation between the proportion of CPC replacing FM and both final body weight (FBW) and weight growth rate (WG) in hybrid culter. Specifically, the T30 and T45 groups exhibited significantly lower FBW and WG compared to the T0 group (p 0.05). However, the crude lipid content was highest in hybrid culter fed the T45 diet and lowest in the T0 group (p 0.05). The contents of total protein (TP) and albumin (ALB) declined slightly as the proportion of FM substituted by CPC increased, yet this decline did not reach statistical significance (p > 0.05). Serum alanine aminotransferase (ALT) activity elevated with increasing dietary CPC, and the T45 group exhibited significantly higher ALT activity compared to the T0 group (p

Compound flood effects, challenges and solutions: Lessons toward climate-resilient Chinese coastal cities - Faith Ka Shun Chan; Xiaohui Lu; Jianfeng Li; Yangchen Lai; Ming Luo; Yongqin David Chen; Donghai Wang; Nan Li; Wei-Qiang Chen; Yong-Guan Zhu; Hing Kai Chan (Ocean & Coastal Management, 2024)

CRISPR/Cas9-mediated ebony knockout causes melanin pigmentation and prevents moth Eclosion in Ectropis grisescens - Jia-Li Li; Shun-Si Li; Zi-Jun Luo; Ji Lu; Xiao-Ming Cai; Zong-Xiu Luo; Lei Bian; Chun-Li Xiu; Nan-Xia Fu; Nai-Yong Liu; Zhao-Qun Li (Pesticide Biochemistry and Physiology, 2024)

Feasibility of reconstructing atmospheric chloride deposition rates based on tritium tracer in the unsaturated zone - Yanwei Lu; Peiyue Li; Min Li; Haoyan Wei; Mingyi Wen; Yupu Ming; Bingcheng Si (Journal of Hydrology, 2024)

Facile synthesis of hydroxylated triazine-based magnetic microporous organic network for ultrahigh adsorption of phenylurea herbicides: An experimental and density-functional theory study - Lu Liu; Lu-Qin Qiao; Feng Liu; Qian-Yun Sun; Yan-Fang Zhao; Xiao-Li Wang; Na Li; Hai-Long Jiang; Xiang-Feng Chen; Ming-Lin Wang; Yong-Ning Wu; Ru-Song Zhao (Journal of Hazardous Materials, 2024)

Impact of microplastics on nicosulfuron accumulation and bacteria community in soil-earthworms system - Qingchuan Gao; Xiaohui Lu; Jinfeng Li; Ping Wang; Ming Li (Journal of Hazardous Materials, 2024)

Nano polystyrene microplastics could accumulate in Nile tilapia (Oreochromis niloticus): Negatively impacts on the intestinal and liver health through water exposure - Di Wu; Xing Lu; Li-Xue Dong; Juan Tian; Jin Deng; Lei Wei; Hua Wen; Shan Zhong; Ming Jiang (Journal of Environmental Sciences, 2024)

An ultra-sensitive electrochemical sensing platform based on nanoflower-like Au/ZnO array on carbon cloth for the rapid detection of the nitrite residues in food samples - Chao Duan; Guo Chen; Zhiling Wang; Hao Li; Zhaoyang Zhang; Yiping Liu; Ming Lu (Food Chemistry, 2024)

Influence on the volatilization of ethyl esters: Nonnegligible role of long-chain fatty acids on Baijiu flavor via intermolecular interaction - Qing-Ru Liu; Xian-Li Lin; Zhen-Ming Lu; Li-Juan Chai; Song-Tao Wang; Jin-Song Shi; Su-Yi Zhang; Cai-Hong Shen; Xiao-Juan Zhang; Zheng-Hong Xu (Food Chemistry, 2024)

Photocurable 3D-printed AgNPs/Graphene/Polymer nanocomposites with high flexibility and stretchability for ECG and EMG smart clothing - Jia-Wun Li; Ho-Fu Chen; Yu-Zhe Liu; Jui-Hsin Wang; Ming-Chang Lu; Chih-Wei Chiu (Chemical Engineering Journal, 2024)

Combating drug-resistant helicobacter pylori infection with zinc peroxide-based nanoparticles: A ROS reservoir via photochemical reaction - Ka Ioi Wong; Shen Wang; Ming Li; Gang Zhao; Caixia Wang; Lei Wu; Huizhen Fan; Min Yao; Min Lu (Chemical Engineering Journal, 2024)

Effective value-added strategy of furan compounds with short straight-chain monohydric alcohols based on acid site regulation of zirconium based mesoporous carbon - Jian Xiong; Liying Li; Xuebin Lu; Lei Ye; Zhihao Yu; Wei Li; Ming Zhang; Yiming Li; Jiao Tao; Rui Zhang; Yina Qiao (Biomass and Bioenergy, 2024)

Basement characteristics reflected by aeromagnetic data in the northern coastal zone of Taizhou - Ming Wang; Jiao-Jiao Li; Yong-jun Zhang; Yi-chuan Li; Lu-ping Xu (Applied Geophysics, 2024)

Effects of different stocking densities and feeding frequencies on growth, physiological and biochemical indexes, and intestinal microflora of largemouth bass (Micropterus salmoides) under land-based round pond - Yu-Xiang Xie; Xue-Ming Yang; Gen Kaneko; Jun-Neng Liang; Lu-Ting Wen; Yi-Jian Li; Qui-Wei Ao; Li-Ming Huang; Pan Li; Wen-Wu Min; Lin-Yuan Jiang; Qiong Yang; et al. (Aquaculture, 2024)

Nocardia seriolae mediates granulomatous chronic inflammation of spleen in Micropterus salmoides through necroptosis - Zheng-Yang Zhou; Sheng-Yu He; Chen-Wang Lu; Shang-Jie Bai; Lin-Feng Kuang; Bin Yang; Sheng Lian; Zheng-Ran Jian; Meng-Meng Wang; Shuang-Yan Xiao; Qing Yu; Ming-Zhu Liu; et al. (Aquaculture, 2024)

Sustainable valorizing high-protein feather waste utilization through solid-state fermentation by keratinase-enhanced Streptomyces sp. SCUT-3 using a novel promoter - Wen-Jun Lu; Ming-Shu Zhang; De-Lin Lu; Zhi-Wei Li; Zhen-Dong Yang; Lei Wu; Jing-Tao Ni; Wei-Dong Chen; Jun-Jin Deng; Xiao-Chun Luo (Waste Management, 2024)

Mechanisms and targeted reversion/prevention of hepatic fibrosis caused by the non-hereditary toxicity of benzo(a)pyrene - Xinru Du; Ming Jin; Ruzhi Li; Fei Zhou; Yuanze Sun; Qinliang Mo; Sisi Song; Na Dong; Shuoke Duan; Maoxuan Li; Ming Lu; Chi Zhang; et al. (Science of The Total Environment, 2024)

A transition from porphyry Mo to vein-style Zn-Pb mineralization: Insights from hydrothermal fluid evolution of the Chalukou deposit, NE China - Lu-Ying Jin; Ke-Zhang Qin; Brian Rusk; Jun-Xing Zhao; Zhen-Zhen Li; Guang-Ming Li; Guo-Xue Song (Journal of Asian Earth Sciences, 2024)

Effects of high hydrostatic pressure sterilisation and thermal sterilisation combined with glutamine transaminase treatment on the properties of yoghurt - Yixuan Liu; Chenchen Huo; Xinxuan Wang; Danyang Liu; Yujiao Liu; Xinqian Wang; Chenyu Xu; Ming Li; Dingqiang Lu; Ruijuan Ren; Zhihe Hu (International Dairy Journal, 2024)

Community-level bioaugmentation results in enzymatic activity- and aroma-enhanced Daqu through altering microbial community structure and metabolic function - Wen-Hu Liu; Li-Juan Chai; Hong-Mei Wang; Zhen-Ming Lu; Xiao-Juan Zhang; Chen Xiao; Song-Tao Wang; Cai-Hong Shen; Jin-Song Shi; Zheng-Hong Xu (Food Bioscience, 2024)

The synergistic impact of socioeconomic and landscape factors on spatial patterns of human-wildlife conflicts - Jie Liu; Yumei Li; Kai Liu; Chao Zhang; Huayao Gao; Ming Lu; Yonggang Nie (Biological Conservation, 2024)

Intravenous immunoglobulin for treatment of hospitalized COVID-19 patients: an evidence mapping and meta-analysis - Mei-xuan Li; Yan-fei Li; Xin Xing; Jun-qiang Niu; Liang Yao; Meng-ying Lu; Ke Guo; Mi-na Ma; Xiao-tian Wu; Ning Ma; Dan Li; Zi-jun Li; et al. (Inflammopharmacology, 2024)

Gut microbiota influence frailty syndrome in older adults: mechanisms and therapeutic strategies - Xiao-Ming Wang; Lu Fan; Chen-Chen Meng; Yun-Jiao Wang; Li-E Deng; Zhuo Yuan; Jun-Ping Zhang; Yan-Yang Li; Shi-Chao Lv (Biogerontology, 2024)

Stronger latitudinal phylogenetic patterns in woody angiosperm assemblages with higher dispersal abilities in China - Lu Jin; Jia‐Jia Liu; Qiao‐Ming Li; Lu‐Xiang Lin; Xiao‐Na Shao; Tian‐Wen Xiao; Bu‐Hang Li; Xiang‐Cheng Mi; Hai‐Bao Ren; Yan Zhu; Xiu‐Juan Qiao; Ju‐Yu Lian; et al. (Journal of Biogeography, 2024)
Aim The equator‐to‐poles decline in the number of species, namely the latitudinal diversity gradient (LDG), is the most conspicuous pattern in biology, yet the underlying mechanisms of this pattern remain controversial. Species dispersal could have strong effects on large‐scale species distributions but has rarely been considered in understanding the LDG. Here we sought to examine how dispersal ability may influence the latitudinal phylogenetic patterns of woody angiosperm assemblages. Location China. Taxon Woody angiosperms. Methods Based on a highly supported mega‐phylogeny constructed from plastid genomes, we assessed the patterns of phylogenetic relatedness and dissimilarity of 1184 trees with three different seed dispersal modes (i.e. zoochory, anemochory and autochory) in 12 permanent forest dynamic plots covering tropical, subtropical and temperate zones in China. Results We found that, compared with zoochorous and anemochorous species, the less vagile autochorous trees exhibited a much weaker latitudinal pattern in phylogenetic relatedness and higher phylogenetic dissimilarity among plots. The phylogenetic dissimilarity pattern of autochorous trees was explained more by geographic distance than environmental factors, consistent with a dominant role for dispersal limitation. Main Conclusions Our study, for the first time, demonstrates that seed dispersal mode strongly influences the latitudinal phylogenetic patterns of woody angiosperm assemblages in China and highlights the importance of interaction between dispersal limitation and environmental filtering in determining the large‐scale distribution of forest biodiversity.

Effects of disturbance modes and carbon sources on the physiological traits and nutrient removal performance of microalgae (S. obliquus) for treating low C/N ratio wastewater - Xin Zhao; Shaoyong Lu; Xiaochun Guo; Ruigang Wang; Ming Li; Chunzhen Fan; Haiming Wu (Chemosphere, 2024)

Accurate genomic selection using low-density SNP panels preselected by maximum likelihood estimation - Shiyu Qu; Sheng Lu; Yang Liu; Ming Li; Songlin Chen (Aquaculture, 2024)

Quantification and visualization of groundwater contamination prevention regionalization based on analytic hierarchy process method (AHP) in Guangdong-Hong Kong-Macao Greater Bay Area, South China - Zhou Cheng; Guoping Lu; Ming Wu; Zhaohui Li; Yirong Deng; Jinzhe Wu; Yanru Hao; Cehui Mo; Qusheng Li; Jianfeng Wu; Jichun Wu; Bill X. Hu (Journal of Hydrology, 2024)

A study on compound flood prediction and inundation simulation under future scenarios in a coastal city - Ming Zhong; Lu Xiao; Xiaodi Li; Yiwen Mei; Tao Jiang; Lixiang Song; Xiaohong Chen (Journal of Hydrology, 2024)

Accumulation of livestock manure–derived heavy metals in the Hexi Corridor oasis agricultural alkaline soil and bioavailability to Chinese cabbage (Brassica pekinensis L.) after 4-year continuous application - Tian-Xia Guan; Zhao-Ping Lu; Ming Yue; Bao-Guo Li; Ai-Gen Fu; Xu-Dong Zhang; Zhong-Hu Li (Environmental Pollution, 2024)

Prioritization of risk genes in colorectal cancer by integrative analysis of multi-omics data and gene networks - Ming Zhang; Xiaoyang Wang; Nan Yang; Xu Zhu; Zequn Lu; Yimin Cai; Bin Li; Ying Zhu; Xiangpan Li; Yongchang Wei; Shaokai Zhang; Jianbo Tian; et al. (Science China Life Sciences, 2024)

Diversity and distribution of yeasts in intertidal zones of China - Hai-Yan Zhu; Da-Yong Han; Liang-Chen Guo; Jun-Ning Li; Xu-Yang Wei; Ri-Peng Zhang; Qi-Ming Wang; Yu-Jie Shang; Lu-Jun Luo; Yu-Hua Wei; Xin-Zhan Liu; Feng-Yan Bai (Frontiers in Marine Science, 2023)
China has the second greatest extent of intertidal zones in the world. The intertidal zone is the most dynamic environments in the biosphere and potentially supports high biodiversity. Marine yeasts show excellent performance in various industrial, environmental and medical applications, however, the marine yeast diversity has rarely been studied in China. In this study, we collected 1241 samples including marine sediments, marine water, plants, and benthos at 161 GPS sites in different types of intertidal zones along the Chinese coastline from north to south. A total of 4436 strains were isolated from these samples using different methods and 286 species including 39 potential novel species were identified from these strains based on the internal transcribed spacer (ITS) region or the D1/D2 domain of the large subunit rRNA gene sequence analysis. The majority of the yeast species in different geographical locations belong to the five orders Serinales , Saccharomycetales , Tremellales , Sporidiobolales , and Pichiales . The yeast species diversity varied depending on sample types, depth of marine sediments, intertidal zone types and geographical locations. Mean annual temperature (MAT), salinity and pH had the greatest effect on the community structures of the yeasts isolated from the intertidal zones. This study represents one of the most comprehensive surveys of marine yeasts in China to date and provides a better understanding of marine yeast diversity and distribution.

The effects of Spinosad on zebrafish larvae and THP-1 cells: Associated with immune cell damage and NF-kappa B signaling pathway activation - Wei-Guo Wang; Shou-Qian Xiong; Jin Lu; Lian-Hua Zhu; Cheng Zhang; Jia-Gao Cheng; Zhong Li; Wen-Ping Xu; Li-Ming Tao; Yang Zhang (Chemosphere, 2023)

Dietary inositol improved glucose and lipid metabolism mediated by the Insulin-PI3K-Akt signaling pathway in Pacific white shrimp (Litopenaeus vannamei) - Jingjing Lu; Xinyue Tao; Ming Li; Xin Zhang; Qicun Zhou; Jiaxiang Luo; Tingting Zhu; Lefei Jiao; Min Jin (Aquaculture, 2023)

Antagonizing pathological α-synuclein-mediated neurodegeneration by J24335 via the activation of immunoproteasome - Zhijian Pan; Chao-Wu Yu; Chen Zhao; Min Shao; Xuanjun Yang; Xiaonan Liang; Haitao Li; Yucong Lu; Qingqing Ye; Ji-Wang Chern; Jiahong Lu; Hefeng Zhou; et al. (Toxicology and Applied Pharmacology, 2023)

Occurrence of liquid crystal monomers in indoor and outdoor air particle matters (PM10): Implications for human exposure indoors - Li-Li Yao; Jun-Li Wang; Rong-Fa Xu; Ming Zhu; Yan Ma; Bin Tang; Qi-Yuan Lu; Feng-Shan Cai; Xiao Yan; Jing Zheng; Yun-Jiang Yu (Science of The Total Environment, 2023)

Microbial diversity and potential health risks of household municipal solid waste in China: A case study in winter during outbreak of COVID-19 - Yanqing Liu; Shuang Li; Zelin Zheng; Xiangyu Zheng; Muhammad Ajmal; Ming Zhao; Wenjing Lu (Science of The Total Environment, 2023)

Ultra-fast degradation of ciprofloxacin by the peroxymonosulfate activation using a Co/Al-LDH decorated magnetic hydrochar: Structural design, catalytic performance and synergistic effects - Jian Zhang; Jia-Fang Xie; Jia-Cheng E. Yang; Ding Li; Lu-Bin Zhong; Yu-Ming Zheng (Chemical Engineering Journal, 2023)

Insights into the adsorptive separation of iron from pickling waste acid: The overlooked role of FeCl3 species - Ling Yuan; Mujian Xu; Rongming Xu; Chenghan Ji; Hailun Yang; Hang Yu; Xiaoyang Li; Ming Hua; Lu Lv; Weiming Zhang (Chemical Engineering Journal, 2023)

Breakthrough Pressure Model of Shale Gas in Water-Saturated Nanopore-Throat Systems: Insights from Molecular Simulations - Yongxian Cheng; Xiancai Lu; Qin Li; Xiandong Liu; Ming Fan (Transport in Porous Media, 2023)

CDK6 is a novel predictive and prognosis biomarker correlated with immune infiltrates in multiple human neoplasms, including small cell lung carcinoma - Guo-Sheng Li; Zhi-Guang Huang; Dong-Ming Li; Yu-Lu Tang; Jin-Hua Zheng; Lin Yang; Yue Feng; Jun-Xi Peng; Jing-Xiao Li; Yu-Xing Tang; Neng-Yong Zeng; Mei-Hua Jin; et al. (Functional & Integrative Genomics, 2023)

A long way to go: impacts of urbanization on migrants’ livelihoods and rural ecology in less industrialized regions - Zhi-qi Zhang; Ming-jing Li; Wen-jun Li; Yi-ran Wei; Yi-lu Shi (Journal of Mountain Science, 2023)

Implicit finite difference wave equation forward modeling based on partial fraction expansion - Jian-yong Song; Hong Cao; Ming-hui Lu; Zhi-fang Yang; Xin-hai Hu; Hong-bing Li; Xin-fei Yan (Applied Geophysics, 2023)

Dual Z-scheme BiOI/Bi2S3/MgIn2S4 composite photocatalyst for effective photocatalytic degradation of Congo red - Borui Li; Xingze Zhao; Yajie Huang; Xiaohui Lu; Hao Jia; Ming Li (Environmental Science and Pollution Research, 2023)

Traditional Chinese medicine bufalin inhibits infectious pancreatic necrosis virus genogroups I and V infection in vitro and in vivo - Jing-Zhuang Zhao; Lin-Fang Li; Li-Ming Xu; Yi-Zhi Shao; Guang-Ming Ren; Qi Liu; Tong-Yan Lu (Aquaculture, 2023)

Wastewater inputs reduce the CO2 uptake by coastal oceans - Yunxiao Li; Liang Xue; Xufeng Yang; Qinsheng Wei; Ming Xin; Ming Xue; Chenhua Han; Ping Han; Xiangyu Liu; Han Zang; Pengjin Yang; Xiangbin Ran; et al. (Science of The Total Environment, 2023)

Maximum helical dichroism enabled by an exceptional point in non-Hermitian gradient metasurfaces - Xiao Li; Chuanjie Hu; Yuan Tian; Youwen Liu; Huanyang Chen; Yadong Xu; Ming-Hui Lu; Yangyang Fu (Science Bulletin, 2023)

Mineralogy, petrology and P-T conditions of the spodumene pegmatites and surrounding meta-sediments in Lhozhag, eastern Himalaya - Jia-Min Wang; Kang-Shi Hou; Lei Yang; Xiao-Chi Liu; Ru-Cheng Wang; Guang-Ming Li; Jian-Gang Fu; Fang-Yang Hu; Yu-Lu Tian; Fu-Yuan Wu (Lithos, 2023)

Characterizing nighttime vertical profiles of atmospheric particulate matter and ozone in a megacity of south China using unmanned aerial vehicle measurements - Zhanyong Wang; Ruhui Cao; Bai Li; Ming Cai; Zhong-Ren Peng; Guohua Zhang; Qingchang Lu; Hong-di He; Jinpu Zhang; Kai Shi; Yonghong Liu; Hui Zhang; et al. (Environmental Research, 2023)

Kilogram-scale synthesis of carbon dots with high-efficiency full-color solid-state fluorescence using an aggregation-induced emission strategy - Hui Ding; Ran Zhao; Zi-Hui Zhang; Jia-Jia Yang; Zheng Wang; Lu-Lan Xiao; Xue-Hua Li; Xin-Jian He; Huan-Ming Xiong (Chemical Engineering Journal, 2023)

Dual N-modification enables high-performance Solid-State Li metal batteries with Li5.5PS4.5Cl1.5 - Chaochao Wei; Ru Wang; Zhongkai Wu; Qiyue Luo; Ziling Jiang; Liang Ming; Long Zhang; Hongcheng Lu; Guangshe Li; Liping Li; Chuang Yu; Shijie Cheng (Chemical Engineering Journal, 2023)

Carbon nano-onions acting as artificial pili enhance chloramphenicol degradation in an anaerobic membrane bioreactor - Ming-Chao Zhu; Yong-Ze Lu; Shou-Wen Chen; Zhao-Xia Hu; Jing-Wei Wang; Na Li; Raymond Jian-Xiong Zeng (Chemical Engineering Journal, 2023)

A multifunctional surgical suture with electroactivity assisted by oligochitosan/gelatin-tannic acid for promoting skin wound healing and controlling scar proliferation - Hui Han; Liqin Tang; Yan Li; Yong Li; Ming Bi; Jun Wang; Fujun Wang; Lu Wang; Jifu Mao (Carbohydrate Polymers, 2023)

The regulative effect and repercussion of probiotics and prebiotics on osteoporosis: involvement of brain-gut-bone axis - Yuan-Wei Zhang; Mu-Min Cao; Ying-Juan Li; Guang-Chun Dai; Pan-Pan Lu; Ming Zhang; Li-Yong Bai; Xiang-Xu Chen; Cheng Zhang; Liu Shi; Yun-Feng Rui (Critical Reviews in Food Science and Nutrition, 2023)

Quantification of two-site kinetic transport parameters of polystyrene nanoplastics in porous media - Yuheng Wu; Zhou Cheng; Ming Wu; Yanru Hao; Guoping Lu; Cehui Mo; Qusheng Li; Jianfeng Wu; Jichun Wu; Bill X. Hu (Chemosphere, 2023)

A review of anaerobic granulation under high-salinity conditions: Mechanisms, influencing factors and enhancement strategies - Chen-Shun Lu; Jin-Ming Qiu; Yang Yang; Yong Hu; Yu-You Li; Takuro Kobayashi; Yong-Jun Zhang (Journal of Water Process Engineering, 2023)

Inventory of cadmium-transporter genes in the root of mangrove plant Avicennia marina under cadmium stress - Lu-Dan Zhang; Ling-Yu Song; Ming-Jin Dai; Jin-Yu Liu; Jing Li; Chao-Qun Xu; Ze-Jun Guo; Shi-Wei Song; Jing-Wen Liu; Xue-Yi Zhu; Hai-Lei Zheng (Journal of Hazardous Materials, 2023)

Co-transformation of HMs-PAHs in rhizosphere soils and adaptive responses of rhizobacteria during whole growth period of rice (Oryza sativa L.) - Shengwei Yi; Feng Li; Chen Wu; Fei Ge; Chuang Feng; Ming Zhang; Yun Liu; Hainan Lu (Journal of Environmental Sciences, 2023)

Preparation and identification of novel antioxidant peptides from camel bone protein - Jianing Wang; Geng Yang; Hanfeng Li; Tong Zhang; Di Sun; Wei Peng Lu; Weijie Zhang; Yihu Wang; Ming Ma; Xiaofeng Cao; Bing Zhang; Yanchuan Guo (Food Chemistry, 2023)

E-eye, flash GC E-nose and HS-GC-MS combined with chemometrics to identify the adulterants and geographical origins of Ziziphi Spinosae Semen - Jiu-ba Zhang; Ming-xuan Li; Yun-fei Zhang; Yu-wen Qin; Yu Li; Lian-lin Su; Lin Li; Zhen-hua Bian; Tu-lin Lu (Food Chemistry, 2023)

α-Fe2O3 nanospindles as an efficient catalyst for optical and magnetic fields co-assisted Li-O2 cells - Daming Yang; Guiru Sun; Xinru Wang; Fengyang Li; Ze Gao; Pingli Zhang; Wei Lu; Ming Feng (Chemical Engineering Journal, 2023)

Insights into the pyrolysis mechanisms of epoxy resin polymers based on the combination of experiments and ReaxFF-MD simulation - Ming-xin Xu; Jin-yi Di; Ya-chang Wu; Xiang-xi Meng; Haiwen-Ji; Hao Jiang; Ji-hong Li; Qiang Lu (Chemical Engineering Journal, 2023)

Icariin inhibits hypertrophy by regulation of GPER1 and CaMKII/HDAC4/MEF2C signaling crosstalk in ovariectomized mice - Wenxia Zhao; Xiaoli Shan; Xueqin Li; Shuang Lu; Lei Xia; Huihua Chen; Chen Zhang; Wei Guo; Ming Xu; Rong Lu; Pei Zhao (Chemico-Biological Interactions, 2023)

Study on pore-water pressure variation and deformation characteristics of warm frozen soils under confined dynamic loading - Jintao Hu; Hu Zhang; Zheng Li; Suiqiao Yang; Shengrong Zhang; Hongchun Li; Ming Lu (Cold Regions Science and Technology, 2023)

A pervasive phosphorylation cascade modulation of plant transcription factors in response to abiotic stress - Wang Baoxiang; Sun Zhiguang; Liu Yan; Xu Bo; Li Jingfang; Chi Ming; Xing Yungao; Yang Bo; Li Jian; Liu Jinbo; Chen Tingmu; Fang Zhaowei; et al. (Planta, 2023)

Risk SNP in a transcript of RP11-638I2.4 increases lncRNA–YY1 interaction and pancreatic cancer susceptibility - Ming Zhang; Yanmin Li; Fuwei Zhang; Hui Geng; Yimin Cai; Zequn Lu; Bin Li; Caibo Ning; Wenzhuo Wang; Haijie Li; Jianbo Tian; Ying Zhu; et al. (Archives of Toxicology, 2023)

Isolation of tumor stem-like cells from primary laryngeal squamous cell carcinoma cells (FD-LS-6) - Duo Zhang; Di Tang; Pen-tao Liu; Lei Tao; Li-ming Lu (Human Cell, 2023)

Serum exosomal hsa_circRNA_0001842 is the potential biomarker for diagnosing lower limb vascular disease in type 2 diabetes mellitus - Qian-Qian Liu; Xing-Hui Liu; Hai-Ming Wang; Li-Min Xu; Xiao-Jing Zhao; Shu-Guang Han; Zuo-Hua Lu (Journal of Genetics, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Molecular mechanism by which StSN2 overexpression inhibits the enzymatic browning of potato - Li-qin Li; Yu-lu Mu; Jing Chen; Qiang Wang; Yi-fei Lu; Sun Xin; Shi-min Yang; Xue-li Huang; Xi-yao Wang; Li-ming Lu (Postharvest Biology and Technology, 2023)

Pilot-scale study on an advanced Fe-Cu process for refractory wastewater pretreatment - Jin-Hong Fan; Zhen-long Yao; De-li Wu; Xia Liu; Lu-ming Ma (Journal of Hazardous Materials, 2023)

In situ titanite ages and Mesozoic metamorphism of Paleoproterozoic mafic granulites from the Wuhe metamorphic complex, southeastern North China Craton - Xu Kong; Jun-Sheng Lu; Ming-Guo Zhai; Gang Liu; Qiang Feng; Yu-Ting Li; Yi-Yi Zhang (Journal of Asian Earth Sciences, 2023)

The largest deflation basin in Asia reveals that the Miocene basin-filling sediments in the eastern Gobi Desert are an important dust source - Jingxian Yin; Zhiyong Han; Yuqiang Zeng; Lisha Qin; Rouxian Pan; Yuwen Zhou; Ming Lu; Hanzhi Zhang; Xusheng Li (Geomorphology, 2023)

Experimental study on remediation of petroleum-contaminated soil by combination of freeze-thaw and electro-osmosis - Suiqiao Yang; Hu Zhang; Yang Hu; Huijun Jin; Jintao Hu; Hongchun Li; Ming Lu (Environmental Pollution, 2023)

Activation of Cannabinoid Receptor 1 in GABAergic Neurons in the Rostral Anterior Insular Cortex Contributes to the Analgesia Following Common Peroneal Nerve Ligation - Ming Zhang; Cong Li; Qian Xue; Chang-Bo Lu; Huan Zhao; Fan-Cheng Meng; Ying Zhang; Sheng-Xi Wu; Yan Zhang; Hui Xu (Neuroscience Bulletin, 2023)
The rostral agranular insular cortex (RAIC) has been associated with pain modulation. Although the endogenous cannabinoid system (eCB) has been shown to regulate chronic pain, the roles of eCBs in the RAIC remain elusive under the neuropathic pain state. Neuropathic pain was induced in C57BL/6 mice by common peroneal nerve (CPN) ligation. The roles of the eCB were tested in the RAIC of ligated CPN C57BL/6J mice, glutamatergic, or GABAergic neuron cannabinoid receptor 1 (CB1R) knockdown mice with the whole-cell patch-clamp and pain behavioral methods. The E/I ratio (amplitude ratio between mEPSCs and mIPSCs) was significantly increased in layer V pyramidal neurons of the RAIC in CPN-ligated mice. Depolarization-induced suppression of inhibition but not depolarization-induced suppression of excitation in RAIC layer V pyramidal neurons were significantly increased in CPN-ligated mice. The analgesic effect of ACEA (a CB1R agonist) was alleviated along with bilateral dorsolateral funiculus lesions, with the administration of AM251 (a CB1R antagonist), and in CB1R knockdown mice in GABAergic neurons, but not glutamatergic neurons of the RAIC. Our results suggest that CB1R activation reinforces the function of the descending pain inhibitory pathway via reducing the inhibition of glutamatergic layer V neurons by GABAergic neurons in the RAIC to induce an analgesic effect in neuropathic pain.

Cordythiazole A, the first member of thiazole alkaloids from Chinese cordyceps, with α-glucosidase inhibitory activity - Xue Han; Li-Hua Liu; Xiao-Ying Fang; Shu-Tai Jiang; Huan Zhao; Zheng-Ming Qian; Zhi-Nan Yin; Li-Gong Lu; Chuan-Xi Wang; Xin-Sheng Yao; Hao Gao (Journal of Natural Medicines, 2023)

Non-monotonic Association Between Chlorinated Polyfluorinated Ether Sulfonic Acids Exposure and the Risk of Overweight/Obesity Status in Adults - Chu Chu; Qiu-Ling Fang; Xin-Xin Cui; Peng-Xin Dong; Zhengmin Qian; Stephen Edward McMillin; Steven W. Howard; Yan-Qiu Ou; Qing-Qing Li; Lu-Yin Wu; Li-Xia Liang; Shuang-Jian Qin; et al. (Exposure and Health, 2023)

Quantum computer-aided design for advanced superconducting qubit: Plasmonium - Feng-Ming Liu; Can Wang; Ming-Cheng Chen; He Chen; Shao-Wei Li; Zhong-Xia Shang; Chong Ying; Jian-Wen Wang; Yong-Heng Huo; Cheng-Zhi Peng; Xiaobo Zhu; Chao-Yang Lu; et al. (Science Bulletin, 2023)

Applying mass flow analysis and aeration optimization strategy to reduce energy consumption of a full-scale anaerobic/anoxic/oxic system - Lu-Man Jiang; Wen Zhang; Yunhui Li; Yanjun Shao; Zhenjian Zhang; Ming Zhang; Junli He; Ji Qiu; Wenxiang Li; Junwei Wang; Zhen Zhou (Journal of Water Process Engineering, 2023)

Dual-modular immunosensor for bongkrekic acid detection using specific monoclonal antibody - Xue-Ming Cao; Li-Hua Li; Hong-Zhi Liang; Jia-Dong Li; Zi-Jian Chen; Lin Luo; Yi-Na Lu; Yu-Xin Zhong; Yu-Dong Shen; Hong-Tao Lei; Hong Wang; Zhen-Lin Xu (Journal of Hazardous Materials, 2023)

Changes in physicochemical characteristics and metabolites in the fermentation of goji juice by Lactiplantibacillus plantarum - Han Xie; Pengyan Gao; Zhen-Ming Lu; Fang-Zhou Wang; Li-Juan Chai; Jin-Song Shi; Hui-Ling Zhang; Yan Geng; Xiao-Juan Zhang; Zheng-Hong Xu (Food Bioscience, 2023)

Emerging roles of air pollution and meteorological factors in autoimmune eye diseases - Fan Cao; Zhuo-Ran Liu; Qin-Yu Ni; Chen-Kai Zha; Shu-Jie Zhang; Jia-Min Lu; Yue-Yang Xu; Li-Ming Tao; Zheng-Xuan Jiang; Hai-Feng Pan (Environmental Research, 2023)

Recombinant Streptomyces netropsis transglutaminase expressed in Komagataella phaffii (Pichia pastoris) and applied in plant-based chicken nugget - Ming-Li Shen; Jhih-Ying Ciou; Lu-Sheng Hsieh; Chuan-Liang Hsu (World Journal of Microbiology and Biotechnology, 2023)

A marine lipopeptides-producing Bacillus amyloliquefaciens HY2-1 with a broad-spectrum antifungal and antibacterial activity and its fermentation kinetics study - Lin-ru Huang; Xiao-ning Ling; Shuai-ying Peng; Ming-hui Tan; Lu-qi Yan; Ying-yin Liang; Gang-hui Li; Kun-tai Li (World Journal of Microbiology and Biotechnology, 2023)

Inulin-type oligosaccharides of Morinda officinalis exerted antidepressant effects by reducing hippocampal inflammation - Zhao-Kai Lai; Yong-Yu Yin; Jiao-Zhao Yan; Qian-Qian Wei; Bin Wang; Yun-Feng Li; Li-Ming Zhang; Yu-Lu Wang (Metabolic Brain Disease, 2023)

Effect of humic acid-modified attapulgite on polycyclic aromatic hydrocarbon adsorption and release from paddy soil into the overlying water in a rice-crab coculture paddy ecosystem and the underlying process - Nan Sun; Jin Liu; Bo-Wei Qi; Li-Li Lu; Hui-Ling Du; Shuang Li; Chang-Qing Li; Si-Wen Jiang; Zi-Jian Wang; An-Pei Yang; Guang-Lei Zhu; Tian-Yi Wang; et al. (Chemosphere, 2023)

Corrigendum to: “Exposure to polystyrene microplastics impairs hippocampus-dependent learning and memory in mice” J. Hazard. Mater. 430 (2022) 128431 - Chiang-Wen Lee; Lee-Fen Hsu; I.-Lin Wu; Yung-Li Wang; Wei-Chen Chen; Yan-Jun Liu; Lu-Tang Yang; Chong-Lun Tan; Yueh-Hsia Luo; Chia-Ching Wang; Hui-Wen Chiu; Thomas Chung-Kuang Yang; et al. (Journal of Hazardous Materials, 2023)

Steam reforming of biomass gasification tar over Ni-based catalyst supported by TiO2-SiO2 composite - Ming-xin Xu; Zi-shu Liu; Xin-yu Zhang; Jin-yi Di; Xiang-xi Meng; Li Zhao; Qiang Lu (Fuel, 2023)

Extraction optimization and identification of four advanced glycation-end products inhibitors from lotus leaves and interaction mechanism analysis - Lu Zhang; Qi-ming Zhou; Liang Xu; Xing Xie; Pei-xin Wang; Zuo-hua Xie; Jin-lin Li; Zong-cai Tu (Food Chemistry, 2023)

Exogenous interference and autofluorescence-free ratiometric aptasensor for detection of OTA based on dual-colored persistent luminescence nanoparticles - Jing-Xuan Guo; Lu-Ming Pan; Meng-Chao Wang; Li-Jian Chen; Xu Zhao (Food Chemistry, 2023)

The Regulation of the AMPK/mTOR Axis Mitigates Tendon Stem/Progenitor Cell Senescence and Delays Tendon Aging - Guangchun Dai; Yingjuan Li; Ming Zhang; Panpan Lu; Yuanwei Zhang; Hao Wang; Liu Shi; Mumin Cao; Renwang Shen; Yunfeng Rui (Stem Cell Reviews and Reports, 2023)

Beta-naphthoflavone increases the differentiation of osteoblasts and suppresses adipogenesis in human adipose derived stem cells involving STAT3 pathway - Ming Lu; Min Li; Tao Luo; Yongsui Li; Mingxin Wang; Huashi Xue; Mengchen Zhang; Qiu Chen (Molecular & Cellular Toxicology, 2023)

Chitinolyticbacter albus sp. Nov., A Novel Chitin-Degrading Bacterium Isolated from Ancient Wood Rhizosphere Soil - Meng-Yu Zhang; Jiang-Yuan Zhao; Le-Le Li; Cheng Ling; Jing Tang; Song-Guo Liang; Jian-Yu Li; Xiao-Di Liu; Lu-Yao Feng; Pei-Wen Yang; Zhu-Feng Shi; Zhang-Gui Ding; et al. (Current Microbiology, 2023)

Exploring the interaction between agronomic practices and soil characteristics on the presence of antibiotic resistance genes in soil - Xiao-Ming Lu; Li-Bo Lu; Yu-Hang Lin; Zi-Yi Chen; Jia-Hao Chen (Applied Soil Ecology, 2023)

HSPA12A was identified as a key driver in colorectal cancer GWAS loci 10q26.12 and modulated by an enhancer–promoter interaction - Zequn Lu; Linyun Fan; Fuwei Zhang; Chaoqun Huang; Yimin Cai; Can Chen; Gaoyuan Li; Ming Zhang; Jinyu Huang; Caibo Ning; Yanmin Li; Wenzhuo Wang; et al. (Archives of Toxicology, 2023)

Dose-response association of polycyclic aromatic hydrocarbon with self-reported trouble sleeping in adults: evidence from the National Health and Nutrition Examination Survey - Jiaqi Chen; Yufei Li; Xiaolin Yin; Jinyu Man; Xuening Zhang; Tongchao Zhang; Xiaorong Yang; Ming Lu (Environmental Science and Pollution Research, 2023)

Important effects of polypropylene on migration of ciprofloxacin in groundwater - Yanna Chen; Cehui Mo; Ming Wu; Yanru Hao; Zhou Cheng; Guoping Lu; Qusheng Li; Bill X. Hu; Jianfeng Wu; Jichun Wu (Journal of Environmental Chemical Engineering, 2023)

Preferential, synergistic sorption and reduction of Cr(VI) from chromium–rhodamine B mixed wastewater by magnetic porous biochar derived from wasted Myriophyllum aquaticum biomass - Dong Zhang; Danli Zhou; Li Lu; Ming Zhang; Ting Lü; Jingang Huang; Hongting Zhao; Jie Zhou; Jörg Rinklebe (Environmental Pollution, 2023)

An injectable antibacterial hydrogel to regulate ocular immune for endophthalmitis treatment - Zunzhen Ming; Lin Han; Huanhuan Zhu; Meiyu Bao; Qiangyuan Fan; Shaobo Xue; Kesheng Wang; Yue Zhang; Meiling Lu; Chongshun Xu; Qi Wu; Tingting Li; et al. (Chemical Engineering Journal, 2023)

The cotton protein GhIQD21 interacts with GhCaM7 and modulates organ morphogenesis in Arabidopsis by influencing microtubule stability - Xing Li; Li Wang; Yupeng Cui; Chen Liu; Yujie Liu; Lili Lu; Ming Luo (Plant Cell Reports, 2023)

Runx2 overexpression promotes bone repair of osteonecrosis of the femoral head (ONFH) - Hai-Jia Xu; Xiang-Zhong Liu; Lu Yang; Yu Ning; Liang-Liang Xu; Da-Ming Sun; Wen Liao; Yi Yang; Zhang-Hua Li (Molecular Biology Reports, 2023)
Background Runt-related transcription factor-2 (Runx2) has been considered an inducer to improve bone repair ability of mesenchymal stem cells (MSCs). Methods and results Twenty-four rabbits were used to establish Osteonecrosis of the femoral head (ONFH) and randomly devided into four groups: Adenovirus Runx2 (Ad-Runx2) group, Runx2-siRNA group, MSCs group and Model group. At 1 week after model establishment, the Ad-Runx2 group was treated with 5 × 107 MSCs transfected through Ad-Runx2, the Runx2-siRNA group was treated with 5 × 107 MSCs transfected through Runx2-siRNA, the MSCs group was injected with 5 × 107 untreated MSCs, and the Model group was treated with saline. The injection was administered at 1 week and 3 weeks after model establishment. The expression of bone morphogenetic protein 2 (BMP-2), Runx2 and Osterix from the femoral head was detected at 3 and 6 weeks after MSCs being injected, and Masson Trichrome Staining, Gross Morphology, X-ray and CT images observation were used to evaluate the repair effect of ONFH. The data revealed that the expression of BMP-2, Runx2 and Osterix in the Runx2-siRNA group was reduced at 3 weeks compared with the MSCs group, and then the expression further reduced at 6 weeks, but was still higher than the Model group besides Osterix; The expression of these three genes in the Ad-Runx2 group was higher than in the MSCs group. Masson Trichrome Staining, Gross Morphology and X-ray and CT images observation revealed that necrotic femoral head of the MSCs group was more regular and smooth than the Runx2-siRNA group, which has a collapsed and irregular femoral head. In the Ad-Runx2 group, necrotic femoral head was basically completely repaired and covered by rich cartilage and bone tissue. Conclusions Overexpression of Runx2 can improve osteoblastic phenotype maintenance of MSCs and promote necrotic bone repair of ONFH.

Human TFF2-Fc fusion protein alleviates DSS-induced ulcerative colitis in C57BL/6 mice by promoting intestinal epithelial cells repair and inhibiting macrophage inflammation - Meng Guo; Rongrong Wang; Jiajia Geng; Zhen Li; Mingfei Liu; Xuxiu Lu; Jianteng Wei; Ming Liu (Inflammopharmacology, 2023)

Correction to: Remote effect of model systematic bias in tropical SST on the cold bias over the Tibetan Plateau - Yuting Wu; Xiaoming Hu; Zhenning Li; Ming Cai; Mengmeng Lu; Song Yang (Climate Dynamics, 2023)

Pseudomonas subflava sp. nov., a new Gram-negative bacterium isolated from Guishan in Yunnan province, south–west China - Cheng Ling; Jiang-Yuan Zhao; Le-Le Li; Zhang-Gui Ding; Meng-Yu Zhang; Jing Tang; Song-Guo Liang; Jian-Yu Li; Xiao-Di Liu; Lu-Yao Feng; Pei-Wen Yang; Yao Lu; et al. (Antonie van Leeuwenhoek, 2023)

Derivation of copper water quality criteria in Bohai Bay for the protection of local aquatic life and the ecological risk assessment - Yang Li; Di Mu; Hong-Qing Wu; Hai-Jiao Liu; Yong-Hui Wang; Guo-Chen Ma; Xue-Min Duan; Jian-Jun Zhou; Chun-Ming Zhang; Xing-Hua Lu; Xian-Hua Liu; Jun Sun; et al. (Marine Pollution Bulletin, 2023)

Quantum neuronal sensing of quantum many-body states on a 61-qubit programmable superconducting processor - Ming Gong; He-Liang Huang; Shiyu Wang; Chu Guo; Shaowei Li; Yulin Wu; Qingling Zhu; Youwei Zhao; Shaojun Guo; Haoran Qian; Yangsen Ye; Chen Zha; et al. (Science Bulletin, 2023)

Dynamic risk analysis of oil depot storage tank failure using a fuzzy Bayesian network model - Qing-Yun Zhou; Bei Li; Yi Lu; Jie Chen; Chi-Min Shu; Ming-shu Bi (Process Safety and Environmental Protection, 2023)

Machine learning based age-authentication assisted by chemo-kinetics: Case study of strong-flavor Chinese Baijiu - Qing-Ru Liu; Xiao-Juan Zhang; Lei Zheng; Lian-Jun Meng; Guang-Qian Liu; Ting Yang; Zhen-Ming Lu; Li-Juan Chai; Song-Tao Wang; Jin-Song Shi; Cai-Hong Shen; Zheng-Hong Xu (Food Research International, 2023)

Intercropped soybean boosts nitrogen benefits and amends nitrogen use pattern under plastic film mulching in the semiarid maize field - Wei Zhang; Yong-Xian Wei; Aziz Khan; Jun-Sheng Lu; Jun-Lan Xiong; Shuang-Guo Zhu; Xiang-Wen Fang; Wei Wang; Meng Hao; Ling Zhao; Xiao-Lin Zhang; Jian-Ming Deng; et al. (Field Crops Research, 2023)

Diffusion and enrichment of high-risk antibiotic resistance genes (ARGs) via the transmission chain (mulberry leave, guts and feces of silkworm, and soil) in an ecological restoration area of manganese mining, China: Role of heavy metals - Kanxuan Yan; Ming Wei; Feng Li; Chen Wu; Shengwei Yi; Jiang Tian; Yun Liu; Hainan Lu (Environmental Research, 2023)

Emestrin-type thiodiketopiperazines from Aspergillus nidulans SD-531, a fungus obtained from the deep-sea sediment of cold seep in the South China Sea - Feng-Yi Lv; Attila Mándi; Xiao-Ming Li; Lu-Ping Chi; Xin Li; Bin-Gui Wang; Tibor Kurtán; Ling-Hong Meng (Deep Sea Research Part I: Oceanographic Research Papers, 2023)

A critical analysis of sources, pollution, and remediation of selenium, an emerging contaminant - Habib Ullah; Lu Lun; Audil Rashid; Noor Zada; Baoliang Chen; Asfandyar Shahab; Ping Li; Muhammad Ubaid Ali; Siyi Lin; Ming Hung Wong (Environmental Geochemistry and Health, 2023)

BPA induces placental trophoblast proliferation inhibition and fetal growth restriction by inhibiting the expression of SRB1 - Yuming Cao; Sihan Chen; Jing Lu; Ming Zhang; Lei Shi; Juling Qin; Jing Lv; Danyang Li; Ling Ma; Yuanzhen Zhang (Environmental Science and Pollution Research, 2023)

Hyperbranched polyethyleneimine-functionalised chitosan aerogel for highly efficient removal of melanoidins from wastewater - Jia-Yi Tang; Yan-Shu Xiong; Ming-Xing Li; Ran Jia; Li-Shu Zhou; Bo-Huan Fan; Kai Li; Wen Li; Hong Li; Hai-Qin Lu (Journal of Hazardous Materials, 2023)

Bacteria and filamentous fungi running a relay race in Daqu fermentation enable macromolecular degradation and flavor substance formation - Wen-Hu Liu; Li-Juan Chai; Hong-Mei Wang; Zhen-Ming Lu; Xiao-Juan Zhang; Chen Xiao; Song-Tao Wang; Cai-Hong Shen; Jin-Song Shi; Zheng-Hong Xu (International Journal of Food Microbiology, 2023)

In-situ growth of carbon nanotubes for improving the performance of Co-N/C catalysts in proton exchange membrane fuel cell - Xi-Ming Qu; Shu-Hu Yin; Ya-Ni Yan; Jian Yang; Yan-Rong Li; Xiao-Yang Cheng; Fa Lu; Chong-Tai Wang; Yan-Xia Jiang; Shi-Gang Sun (Chemical Engineering Journal, 2023)

Free-standing [0 0 1]-oriented one-dimensional crystal-structured antimony selenide films for self-powered flexible near-infrared photodetectors - Xixing Wen; Zonghuan Lu; Bingxiang Li; Gwo-Ching Wang; Morris A. Washington; Qiang Zhao; Toh-Ming Lu (Chemical Engineering Journal, 2023)

Sulphur-dopant induced breaking of the scaling relation on low-valence Ni sites in nickel ferrite nanocones for water oxidation with industrial-level current density - Hai-Jun Liu; Ren-Ni Luan; Lu-Yao Li; Ren-Qing Lv; Yong-Ming Chai; Bin Dong (Chemical Engineering Journal, 2023)

Targeting Senescent Tendon Stem/Progenitor Cells to Prevent or Treat Age-Related Tendon Disorders - Hao Wang; Guang-Chun Dai; Ying-Juan Li; Min-Hao Chen; Pan-Pan Lu; Yuan-Wei Zhang; Ming -Zhang; Mu-Min Cao; Yun-Feng Rui (Stem Cell Reviews and Reports, 2023)

Remote effect of model systematic bias in tropical SST on the cold bias over the Tibetan Plateau - Yuting Wu; Xiaoming Hu; Zhenning Li; Ming Cai; Mengmeng Lu; Song Yang (Climate Dynamics, 2023)
Most state-of-the-art climate models substantially underestimate the near-surface air temperature (SAT) over the Tibetan Plateau (TP), especially for the cold season. While previous studies have attributed this cold bias to local factors such as the elevation difference, coarse resolution, and excessive snow cover, this investigation addresses the potential contributions of the systematic bias of tropical sea surface temperature (SST) to the TP cold bias. Experiments with the NCAR Community Atmosphere Model demonstrate that tropical SST bias results in an apparent cold bias over the TP, especially in boreal winter, and explains about 40% of the deviation in multi-model mean SAT over the TP relative to station observations. Forced by the tropical SST bias, heat flux exhibits an anomalous divergence over the plateau, causing a cooling center in the mid- and lower-troposphere over the TP. This atmospheric cooling in turn leads to a reduction of the downward longwave radiative fluxes reaching the surface, less energy supply, and thus a cold bias over the TP.

Dietary lysine facilitates muscle growth and mediates flesh quality of Pacific white shrimp (Litopenaeus vannamei) reared in low-salinity water - Meili Wu; Meifeng Li; Hua Wen; Lijuan Yu; Ming Jiang; Xing Lu; Juan Tian; Feng Huang (Aquaculture International, 2023)

In-Situ versatile characterization and manipulation toward Amorphous-to-Crystalline phase transition via nanoparticles strategy for organic luminescent materials and its applications - Wenbin Chen; Fanwei Ye; Zicong Situ; Jiahong Xu; Xiaolong Lu; Hefeng Zhang; Shun-Li Chen; Zhengya Dong; Li Dang; Ming-De Li (Chemical Engineering Journal, 2023)

Isopropanol-regulated adhesion-controllable conductive gels for robust bioelectric signal monitoring and flexible underwater robots - Xiaojuan Ming; Weibing Zhong; Yiming Ke; Jing Lu; Kangyu Jia; Xincheng Ding; Haiqing Jiang; Mufang Li; Dong Wang (Chemical Engineering Journal, 2023)

Fucoidan from Fucus vesiculosus prevents the loss of dopaminergic neurons by alleviating mitochondrial dysfunction through targeting ATP5F1a - Meimei Xing; Guoyun Li; Yang Liu; Luyao Yang; Youjiao Zhang; Yuruo Zhang; Jianhua Ding; Ming Lu; Guangli Yu; Gang Hu (Carbohydrate Polymers, 2023)

Research on the Purification Performance of a Floating Island System Treating the Effluent of WWTP Under Different Seasons - Zhao-xu Peng; Ning-qi Niu; Ting-mei Li; Lu-ji Yu; Li-kun Gu; Ming-hui Liu (Water, Air, & Soil Pollution, 2023)

Analysis of PAT1 subfamily members in the GRAS family of upland cotton and functional characterization of GhSCL13-2A in Verticillium dahliae resistance - Chen Chen; Li-Li Lu; Shu-Ya Ma; Yan-Peng Zhao; Na Wu; Wen-Jie Li; Li Ma; Xian-Hui Kong; Zong-Ming Xie; Yu-Xia Hou (Plant Cell Reports, 2023)

Changes in planting methods will change the potential distribution of rice in South China under climate warming - Shuo Li; Zhou Lu; Jie Zhao; Ming Luo; Fu Chen; Qingquan Chu (Agricultural and Forest Meteorology, 2023)

Performance and mechanism of sacrificed iron anode coupled with constructed wetlands (E-Fe) for simultaneous nitrogen and phosphorus removal - Ming Zhou; Jiashun Cao; Yuanyuan Qiu; Yanhong Lu; Jinyan Guo; Chao Li; Yantang Wang; Liangshan Hao; Hongqiang Ren (Environmental Science and Pollution Research, 2023)

Surfactant recovery and efficient separation of PAHs from surfactant solutions by low-cost waste activated sludge and two-stage design optimization - Dong Zhang; Biao Shen; Ming Zhang; Yuchi Zhong; Ting Lü; Jingang Huang; Hongting Zhao; Li Lu (Environmental Science and Pollution Research, 2023)

Comprehensive profiling of the distribution, risks and priority of pharmaceuticals and personal care products: A large-scale study from rivers to coastal seas - Shuang Lu; Jing Wang; Baodong Wang; Ming Xin; Chunye Lin; Xiang Gu; Maoshan Lian; Yun Li (Water Research, 2023)

Prediction of diffuse solar radiation by integrating radiative transfer model and machine-learning techniques - Yunbo Lu; Renlan Zhang; Lunche Wang; Xin Su; Ming Zhang; Huaping Li; Shiyu Li; Jiaojiao Zhou (Science of The Total Environment, 2023)

Multi-stage planning of LID-GREI urban drainage systems in response to land-use changes - Yu Zhang; Mo Wang; Dongqing Zhang; Zhongming Lu; Amin E. Bakhshipour; Ming Liu; Zhiyu Jiang; Jianjun Li; Soon Keat Tan (Science of The Total Environment, 2023)

Enhanced removal of typical odor compounds in constructed wetlands integrated with iron carbon and tidal flow - Yuwei She; Yan Zhao; Hongyan Ding; Qian Feng; Zhaoxia Xue; Jingyang Luo; Minfeng Lu; Qian Hu; Jiashun Cao; Yu Dai; Ming Li (Journal of Water Process Engineering, 2023)

Mechanism of β-blocker biodegradation by wastewater microorganisms - Ming Yi; Jinxiu Lou; Wanlu Zhu; Dan Li; Pingfeng Yu; Huijie Lu (Journal of Hazardous Materials, 2023)

Probing the stability of perovskite solar cell under working condition through an ultra-thin silver electrode: Beyond the halide ion diffusion and metal diffusion - Hao Li; Zheng Yan; Min Li; Xiaoyan Wen; Shuo Deng; Sisi Liu; Wallace C.H. Choy; Lijie Li; Ming-Yu Li; Haifei Lu (Chemical Engineering Journal, 2023)

Highly efficient shrimp shell recovery by solid-state fermentation with Streptomyces sp. SCUT-3 - De-Lin Lu; Ming-Shu Zhang; Jun-Jin Deng; Wen-Jun Lu; Zhen-Dong Yang; Zhi-Wei Li; Yu-Chen Chen; Xiao-Chun Luo (Chemical Engineering Journal, 2023)

Photoactivatable metal organic framework for synergistic ferroptosis and photodynamic therapy using 450 nm laser - Yuhang Chen; Lijiang Gu; Bohan Ma; Xing Li; Yibo Mei; Jinlai Zhou; Yue Chong; Minghai Ma; Mengzhao Zhang; Lu Wang; Yifan Cheng; Kaijie Wu; et al. (Chemical Engineering Journal, 2023)

4,4′-Bis(trinitromethyl)-3,3′-azo/azoxy-furazan: High-energy dense oxidizers - Shuaiqi Wang; Yuangang Xu; Shuaijie Jiang; Feng Yang; Dongxue Li; Pengcheng Wang; Qiuhan Lin; Ming Lu (Chemical Engineering Journal, 2023)

A novel method based on solid phase extraction and liquid chromatography-tandem mass spectrometry warrants occurrence of trace xanthates in water - Yu-Ting Qiao; Ying-Xin Lu; Peng-Fei Yu; Nai-Xian Feng; Yan-Wen Li; Hai-Ming Zhao; Quan-Ying Cai; Lei Xiang; Ce-Hui Mo; Qing X. Li (Chemosphere, 2023)

A review of gas-phase chemical mechanisms commonly used in atmospheric chemistry modelling - Yanhui Liu; Jiayin Li; Yufang Ma; Ming Zhou; Zhaofeng Tan; Limin Zeng; Keding Lu; Yuanhang Zhang (Journal of Environmental Sciences, 2023)

Freezing-induced loss of wheat starch granule-associated proteins affected dough quality: From water distribution, rheological properties, microstructure, and gluten development - Han Tao; Fan Lu; Xue-Feng Zhu; Hui-Li Wang; Xue-Ming Xu (Journal of Cereal Science, 2023)

Region, vintage, and grape maturity co-shaped the ionomic signatures of the Cabernet Sauvignon wines - Xiao Han; Hao-Cheng Lu; Yu Wang; Xiao-Tong Gao; Hui-Qing Li; Meng-Bo Tian; Ning Shi; Ming-Yu Li; Xiao-Li Yang; Fei He; Chang-Qing Duan; Jun Wang (Food Research International, 2023)

Patternable thermal conductive interface materials enabled by vitrimeric phase change materials - Li-Mei Peng; Zhao Xu; Jie Yang; Lu Bai; Rui-Ying Bao; Ming-Bo Yang; Wei Yang (Chemical Engineering Journal, 2023)

Two silver energetic coordination polymers based on a new N-amino-contained ligand: Towards good detonation performance and excellent laser-initiating ability - Qing Lang; Xinyi Li; Jianxin Zhou; Yuangang Xu; Qiuhan Lin; Ming Lu (Chemical Engineering Journal, 2023)

Inspired by philosophizing of “point to area”: Ion pre-intercalation induces the reconstitution of interlayer environment of MXene for lithium storage - Miao Liu; Xin Qu; Yixuan Wang; Yukai Zhang; Cuimei Zhao; Bo Liu; Xiangxin Xue; Junkai Zhang; Zhao Wang; Jiaming Li; Wenjuan Han; Shichong Xu; et al. (Chemical Engineering Journal, 2023)

TRIM11, a new target of p53, facilitates the migration and invasion of nasopharyngeal carcinoma cells - Ziyi Zhao; Jinkuang Deng; Ming Lu; Jun Yang; Linlin Chen; DianYuan Li; Yi Sang (Molecular Biology Reports, 2023)
Background Although tripartite motif-containing protein 11 (TRIM11) is known to be associated with a variety of cancers, its role in nasopharyngeal carcinoma (NPC) is unclear. Methods and results To investigate the role of TRIM11 in NPC, TRIM11 was stably overexpressed in 6–10B and CNE2 cells with lentiviral vectors and knocked down in S18 and 5–8F cells using the CRISPR/Cas9 system. Transwell assays and wound-healing assays revealed that TRIM11 facilitated the migration and invasion of NPC cells. Mechanistically, we found that p53 inhibits TRIM11 expression by binding to its promoter. Conclusions TRIM11 may serve as a potential diagnostic marker for NPC and has a certain therapeutic value.

Brevibacillus daliensis sp. nov., Isolated From Soil in Machangqing Nature Reserve - Shi-Qiang Ye; Jiang-Yuan Zhao; Le-Le Li; Cheng Ling; Meng-Yu Zhang; Jing Tang; Song-Guo Liang; Jian-Yu Li; Pei-Wen Yang; Jiao Xiong; Lu-Yao Feng; Zhu-Feng Shi; et al. (Current Microbiology, 2023)

UHPLC-QTOF-MS/MS based characterization of anti-tumor constituents in Ceratocarpus arenarius L. and identification of EGFR-TK inhibitors by virtual screening - Le Pan; Li Li; Lu Xu; Jiaojiao Zhang; Jiashan Li; Ming Gao; JinMen Yu; Lu Jin; Dongyu Lei (Natural Product Research, 2022)

Body mass index–based predictions and personalized clinical strategies for colorectal cancer in the context of PPPM - Yun-Jia Gu; Li-Ming Chen; Mu-En Gu; Hong-Xiao Xu; Jing Li; Lu-Yi Wu (EPMA Journal, 2022)
Currently colorectal cancer (CRC) is the third most prevalent cancer worldwide. Body mass index (BMI) is frequently used in CRC screening and risk assessment to quantitatively evaluate weight. However, the impact of BMI on clinical strategies for CRC has received little attention. Within the framework of the predictive, preventive, and personalized medicine (3PM/PPPM), we hypothesized that BMI stratification would affect the primary, secondary, and tertiary care options for CRC and we conducted a critical evidence-based review. BMI dynamically influences CRC outcomes, which helps avoiding adverse treatment effects. The outcome of surgical and radiation treatment is adversely affected by overweight (BMI ≥ 30) or underweight (BMI < 20). A number of interventions, such as enhanced recovery after surgery and robotic surgery, can be applied to CRC at all levels of BMI. BMI-controlling modalities such as exercise, diet control, nutritional therapy, and medications may be potentially beneficial for patients with CRC. Patients with overweight are advised to lose weight through diet, medication, and physical activity while patients suffering of underweight require more focus on nutrition. BMI assists patients with CRC in better managing their weight, which decreases the incidence of adverse prognostic events during treatment. BMI is accessible, noninvasive, and highly predictive of clinical outcomes in CRC. The cost–benefit of the PPPM paradigm in developing countries can be advanced, and the clinical benefit for patients can be improved with the promotion of BMI-based clinical strategy models for CRC.

Environmental impact of typical zinc smelting that implements solid waste collaborative utilization in China - Wei-Ning Liu; Yao Shi; Chen-Mu Zhang; Lang-Ming Liu; Hui-Quan Li; Bin Lu; Yuan-Bo Xie; Cai-Bei Zhuang; Tian-You Sun; Wei-Ping Liu; Xue Guan; Ying-Yan Hu (The International Journal of Life Cycle Assessment, 2022)

Increasing soil heterogeneity strengthens the inhibition of a native woody plant by an invasive congener - Yi Hu; Zhen-Wei Xu; Ming-Yan Li; Jordan R. Croy; Zhong-Yi Zhang; Hai-Mei Li; Wei-Hua Guo; Xiao-Lei Jiang; Hui-Cui Lu; Xiao Guo (Plant and Soil, 2022)

Transplantation of Nasal Olfactory Mucosa Mesenchymal Stem Cells Benefits Alzheimer’s Disease - Chun-Gu Hong; Meng-Lu Chen; Ran Duan; Xin Wang; Zhi-Lin Pang; Li-Te Ge; Ming Lu; Hui Xie; Zheng-Zhao Liu (Molecular Neurobiology, 2022)

Role of carnitine in adaptation of Chromohalobacter salexigens DSM 3043 and its mutants to osmotic and temperature stress in defined medium - Xiang-Lin Meng; Xia Gao; Yuan-Ming Si; Li-Li Xu; Li-Zhong Guo; Wei-Dong Lu (Extremophiles, 2022)

Immunogenicity and protective efficacy of a DNA vaccine inducing optimal expression of the SARS-CoV-2 S gene in hACE2 mice - Zhuo-xin Li; Sheng Feng; He Zhang; Xin-yu Zhuang; Chao Shang; Shi-yu Sun; Ji-cheng Han; Yu-biao Xie; Jin-yong Zhang; Wei Wang; Cheng-hui Li; Guan-yu Zhao; et al. (Archives of Virology, 2022)

Dongia deserti sp. nov., Isolated from the Gurbantunggut Desert Soil - Chun-Yan Lu; Lei Dong; Dong Wang; Shuai Li; Bao-Zhu Fang; Ming-Xian Han; Feng Liu; Hong-Chen Jiang; Iftikhar Ahmed; Wen-Jun Li (Current Microbiology, 2022)

Genetic variations in the bitter taste receptor gene TAS2R38 are related to cigarette smoking behavior in Han Chinese smokers - Fei-Yan Qi; Zhou-Hai Zhu; Meng Li; Ying Guan; Qi-Yuan Peng; She-Ming Lu; Zhi-Hua Liu; Ming-Feng Wang; Ming-Ming Miao; Zhang-Yu Chen; Xue-Mei Li; Jie Bai; et al. (Genes & Genomics, 2022)

The ignored risk: heavy metal pollution of medicine and food homologous substances - Yayuan Huang; Xinqi Wang; Yimin Zhou; Bingyu Li; Huihui Du; Boqing Tie; Xiangyang Lu; Si Qin; Ming Lei (Environmental Science and Pollution Research, 2022)

Palmitoylation of MDH2 by ZDHHC18 activates mitochondrial respiration and accelerates ovarian cancer growth - Xuan Pei; Kai-Yue Li; Yuan Shen; Jin-Tao Li; Ming-Zhu Lei; Cai-Yun Fang; Hao-Jie Lu; Hui-Juan Yang; Wenyu Wen; Miao Yin; Jia Qu; Qun-Ying Lei (Science China Life Sciences, 2022)

The Key Role of Magnetic Resonance Imaging in the Detection of Neurodegenerative Diseases-Associated Biomarkers: A Review - Ke-Ru Li; An-Guo Wu; Yong Tang; Xiao-Peng He; Chong-Lin Yu; Jian-Ming Wu; Guang-Qiang Hu; Lu Yu (Molecular Neurobiology, 2022)

Cassane diterpenoids from Caesalpinia pulcherrima and their anti-inflammatory and α -glycosidase inhibitory activities - Xin Yun; Xiu-Mei Chen; Jia-Yun Wang; Wang Lu; Zi-Han Zhang; Young Ho Kim; Shi-Chun Zong; Chun-Huan Li; Jin-Ming Gao (Natural Product Research, 2022)

Key factors affecting carbon prices from a time-varying perspective - Ming-Fang LI; Hui HU; Lu-Tao ZHAO (Environmental Science and Pollution Research, 2022)

Long-term changes in zooplankton in the Changjiang estuary from the 1960s to 2020 - Ping Du; Wen-Jian Ye; Bang-Ping Deng; Ming Mao; Yuan-Li Zhu; Fang-Ping Cheng; Zhi-Bing Jiang; Lu Shou; Quan-Zhen Chen (Frontiers in Marine Science, 2022)
The Changjiang estuary (CJE) is a large estuary that is affected by multiple anthropogenic stressors and climate change. The long-term trend of zooplankton in the CJE is an important indicator of the ecological response to stressors. We applied the Mann–Kendall trend analysis and Pettitt test to detect the trend and breakpoints of the biomass of the large mesozooplankton (LMZ; 505–20 000 μm) in four seasons, abundance of main LMZ taxa in summer from the 1960s to 2020, and abundance of dominant species in summer from 2000 to 2020 in the CJE. Results showed that LMZ biomass increased significantly during spring and summer, and the breakpoints both occurred in the 1980s. After the breakpoint, the mean biomass increased from 142.88 to 429.42 mg/m 3 in spring and from 296.28 to 723.92 mg/m 3 in summer. After 2000, the abundance of Copepoda in summer increased by more than 10 times compared to the 1960s. Under the conditions of warming and increased dinoflagellate abundance in the CJE, the abundance of the warm-water and omnivorous small calanoid copepod Paracalanus aculeatus increased significantly. Meanwhile, the significant decrease in the abundance of the temperate brackish species Labidocera euchaeta was probably mainly related to warming. The rapid changes in LMZ biomass during the late 1980s and mid-1990s is probably the result of a combination of enhanced bottom–up support, reduced top–down pressure, and promotion of temperature. This study provides scientific evidence and insights into the adaptive management of the Changjiang Basin.

Human Umbilical Cord-Derived Mesenchymal Stem Cells Ameliorate Skin Aging of Nude Mice Through Autophagy-Mediated Anti-Senescent Mechanism - Ting Li; Li Zhou; Mengqiang Fan; Zuxiang Chen; Li Yan; Haishan Lu; Ming Jia; Huiling Wu; Letian Shan (Stem Cell Reviews and Reports, 2022)

Lead Exposure in Developmental Ages Promotes Aβ Accumulation by Disturbing Aβ Transportation in Blood-Cerebrospinal Fluid Barrier/Blood–Brain Barriers and Impairing Aβ Clearance in the Liver - Can-Can Zhou; Xu-Jie Wang; Zi-Chen Li; Wen-Jie Lu; Yun-Ting Zhang; Fu-Ming Shen; Dong-Jie Li (Biological Trace Element Research, 2022)

Cohnella mopanensis sp. nov., a new Gram-negative bacterium isolated from soil in Xinping Mountain National Forest Park - Jing Tang; Jiang-Yuan Zhao; Le-Le Li; Zhang-Gui Ding; Shi-Qiang Ye; Cheng Ling; Meng-Yu Zhang; Song-Guo Liang; Jian-Yu Li; Pei-Wen Yang; Jiao Xiong; Lu-Yao Feng; et al. (Archives of Microbiology, 2022)

RIG-I acts as a tumor suppressor in melanoma via regulating the activation of the MKK/p38MAPK signaling pathway - Rui Guo; Shun-Yuan Lu; Jin-Xia Ma; Qian-Lan Wang; Lu Zhang; Ling-Yun Tang; Yan Shen; Chun-Ling Shen; Jin-Jin Wang; Li-Ming Lu; Zhu-Gang Wang; Hong-Xin Zhang (Human Cell, 2022)
Studies have indicated that RIG-I may act as a tumor suppressor and participate in the tumorigenesis of some malignant diseases. However, RIG-I induces distinct cellular responses via different downstream signaling pathways depending on the cell type. To investigate the biological function and underlying molecular mechanism of RIG-I in the tumorigenesis of melanoma, we constructed RIG-I knockout, RIG-I -overexpressing B16-F10 and RIG-I knockdown A375 melanoma cell lines, and analyzed the RIG-I-mediated change in the biological behavior of tumor cells in spontaneous and poly (I:C)-induced RIG-I activation. Cell proliferation, cell cycling, apoptosis and migration were detected by CCK-8 assay, BrdU incorporation assay, Annexin V–PI staining assay and Transwell assay, respectively. In vivo tumorigenicity was evaluated by tumor xenograft growth in nude mice and subsequently by Ki67 staining and TUNEL assays. Furthermore, Western blotting was utilized to explore the underlying mechanism of RIG-I in melanoma cells. Our data showed that RIG-I promotes apoptosis and inhibits proliferation by G1 phase cell cycle arrest in the melanoma cell lines. Mechanistically, RIG-I induced the phosphorylation of p38 MAPK and MAPK kinases MKK3 and MKK4. In conclusion, the current study demonstrated that RIG-I suppressed the development of melanoma by regulating the activity of the MKK/p38 MAPK signaling pathway, which is relevant to research on novel therapeutic targets for this malignant disease.

Wuzi Yanzong pill attenuates MPTP-induced Parkinson’s Disease via PI3K/Akt signaling pathway - Wei Hang; Hui-jie Fan; Yan-rong Li; Qi Xiao; Lu Jia; Li-juan Song; Yao Gao; Xiao-ming Jin; Bao-guo Xiao; Jie-zhong Yu; Cun-gen Ma; Zhi Chai (Metabolic Brain Disease, 2022)

FLO8 deletion leads to decreased adhesion and virulence with downregulated expression of EPA1, EPA6, and EPA7 in Candida glabrata - Jun-Tao Zhao; Ke-Zhi Chen; Jin-Yan Liu; Wei-Hua Li; Yu-Zhu Wang; Lu-Ling Wang; Ming-Jie Xiang (Brazilian Journal of Microbiology, 2022)

Therapeutic Effects of Sodium Para-Aminosalicylic Acid on Cognitive Deficits and Activated ERK1/2-p90RSK/NF-κB Inflammatory Pathway in Pb-Exposed Rats - Li-li Lu; Yu-wen Zhang; Zhao-cong Li; Yuan-yuan Fang; Lei-lei Wang; Yue-song Zhao; Shao-jun Li; Shi-yan Ou; Michael Aschner; Yue-ming Jiang (Biological Trace Element Research, 2022)

Electrical resistivity imaging in Shibaozhai area using magnetotelluric sounding: Enlightenment of hydrocarbon reservoirs on the eastern edge of the Sichuan Basin - Shu-Ming Wang; Qing-Yun Di; Gui-An Zou; Xiao-Lu Su; Cai Qian; Ruo Wang; De-Shan Li (Applied Geophysics, 2022)

Effect of Culture Period and Stocking Density on Input Demand and Scale Economies of Milkfish (Chanos chanos) Polycultures with White Shrimp (Penaeus indicus) - Wei-Tse Pai; Christian Schafferer; Jie-Min Lee; Li-Ming Ho; Yung-Hsiang Lu; Han-Chung Yang; Chun-Yuan Yeh (Fishes, 2022)
Milkfish, Chanos chanos, is one of the major inland cultured fish species in Taiwan. Variations in land resources and climate have led to the application of two distinct culture practices of milkfish polycultures with white shrimp, Penaeus indicus. This study applies a translog cost function model to analyze the production scale economy and input demand price elasticity of four milkfish polyculture systems with two different culture periods (OWC and NOWC) and two different white shrimp–milkfish fry stocking ratios (low SMR: 10–55 fry/ha; high SMR: 56–100 fry/ha). The findings show that the four milkfish polyculture systems require different operational adjustments to increase production while reducing the average culture cost. More specifically, overwinter cultures (OWC) have economies of scale. Farmers may reduce the average cost by expanding the production scale. Non-overwinter polycultures (NOWC) with high SMR are at the stage of decreasing return to scale, meaning that gains in output of milkfish cannot reduce the average cost. In terms of input factor use, farmers of OWC systems with high SMR are sensitive to fluctuations in the fry price since fry constitutes the input factor exhibiting the highest own-price elasticity. Moreover, fry and feed of OWC households with high SMR have high levels of substitutability, whereas fry and other input exhibit substitutability in OWC systems with low SMR. In NOWC farming households with high SMR, fry and capital have substitutability. It is thus recommended to modify the input factor use according to the culture mode and the white shrimp–milkfish stocking density ratio. Moreover, the study found that NOWCs have considerably higher SMR than OWCs, which may lead to a deterioration of the water quality in NOWC fishponds and lower survival rates. It is thus recommended to reduce the SMR to 31:1 to achieve economies of scale in production and increase the survival rate of milkfish and white shrimp.

Identification and management of GCK-MODY complicating pregnancy in Chinese patients with gestational diabetes - Yanyan Jiang; Fusong Jiang; Ming Li; Qingkai Wu; Chenming Xu; Rong Zhang; Mingqiang Song; Yanzhong Wang; Ying Wang; Yating Chen; Juan Zhang; Xiaoxu Ge; et al. (Molecular and Cellular Biochemistry, 2022)

Distinct co-occurrence patterns and driving forces of abundant and rare bacterial communities in the multispecies solid-state fermentation process of cereal vinegar - Ming-Ye Peng; Zhen-Ming Lu; Xiao-Juan Zhang; Ting Huang; Yong-Jian Deng; Li-Juan Chai; Jin-Song Shi; Zheng-Hong Xu (Systems Microbiology and Biomanufacturing, 2022)

Microseismic signal denoising by combining variational mode decomposition with permutation entropy - Zhang Xing-Li; Cao Lian-Yue; Chen Yan; Jia Rui-Sheng; Lu Xin-Ming (Applied Geophysics, 2022)

MoOpy2 is essential for fungal development, pathogenicity, and autophagy in Magnaporthe oryzae - Ying‐Ying Cai; Jing‐Yi Wang; Xi‐Yu Wu; Shuang Liang; Xue‐Ming Zhu; Lin Li; Jian‐Ping Lu; Xiao‐Hong Liu; Fu‐Cheng Lin (Environmental Microbiology, 2022)
Summary The development and pathogenicity of the fungus Magnaporthe oryzae , the causal agent of destructive rice blast disease, require it to perceive external environmental signals. Opy2, an overproduction‐induced pheromone‐resistant protein 2, is a crucial protein for sensing external signals in Saccharomyces cerevisiae . However, the biological functions of the homologue of Opy2 in M. oryzae are unclear. In this study, we identified that MoOPY2 is involved in fungal development, pathogenicity, and autophagy in M. oryzae . Deletion of MoOPY2 resulted in pleiotropic defects in hyphal growth, conidiation, germ tube extension, appressorium formation, appressorium turgor generation, and invasive growth, therefore leading to attenuated pathogenicity. Furthermore, MoOpy2 participates in the Osm1 MAPK pathway and the Mps1 MAPK pathway by interacting with the adaptor protein Mst50. The interaction sites of Mst50 and MoOpy2 colocalized with the autophagic marker protein MoAtg8 in the preautophagosomal structure sites (PAS). Notably, the Δ Moopy2 mutant caused cumulative MoAtg8 lipidation and rapid GFP‐MoAtg8 degradation in response to nitrogen starvation, showing that MoOpy2 is involved in the negative regulation of autophagy activity. Taken together, our study revealed that MoOpy2 of M. oryzae plays an essential role in the orchestration of fungal development, appressorium penetration, autophagy and pathogenesis.

Endosomal sorting complexes required for transport‐0 ( ESCRT ‐0) are essential for fungal development, pathogenicity, autophagy and ER ‐phagy in Magnaporthe oryzae - Li‐Xiao Sun; Hui Qian; Meng‐Yu Liu; Ming‐Hua Wu; Yun‐Yun Wei; Xue‐Ming Zhu; Jian‐Ping Lu; Fu‐Cheng Lin; Xiao‐Hong Liu (Environmental Microbiology, 2022)
Summary Magnaporthe oryzae is an important plant pathogen that causes rice blast. Hse1 and Vps27 are components of ESCRT‐0 involved in the multivesicular body (MVB) sorting pathway and biogenesis. To date, the biological functions of ESCRT‐0 in M. oryzae have not been determined. In this study, we identified and characterized Hse1 and Vps27 in M. oryzae . Disruption of MoHse1 and MoVps27 caused pleiotropic defects in growth, conidiation, sexual development and pathogenicity, thereby resulting in loss of virulence in rice and barley leaves. Disruption of MoHse1 and MoVps27 triggered increased lipidation of MoAtg8 and degradation of GFP‐MoAtg8, indicating that ESCRT‐0 is involved in the regulation of autophagy. ESCRT‐0 was determined to interact with coat protein complex II (COPII), a regulator functioning in homeostasis of the endoplasmic reticulum (ER homeostasis), and disruption of MoHse1 and MoVps27 also blocked activation of the unfolded protein response (UPR) and autophagy of the endoplasmic reticulum (ER‐phagy). Overall, our results indicate that ESCRT‐0 plays critical roles in regulating fungal development, virulence, autophagy and ER‐phagy in M. oryzae .

Methods for the construction of DEMs of artificial slopes considering morphological features and semantic information - Yan Xu; Ming-wei Zhao; Jie Lu; Chun Wang; Ling Jiang; Can-can Yang; Xiao-li Huang (Journal of Mountain Science, 2022)

Dopaminergic Projection from Ventral Tegmental Area to Substantia Nigra Pars Reticulata Mediates Chronic Social Defeat Stress–Induced Hypolocomotion - Feng He; Pei Zhang; Qian Zhang; Guangjian Qi; Hongwei Cai; Tongxia Li; Ming Li; Jiazhen Lu; Jiaen Lin; Jie Ming; Bo Tian (Molecular Neurobiology, 2021)

Heat stress inhibits TLR4-NF-κB and TLR4-TBK1 signaling pathways in broilers infected with Salmonella Typhimurium - Wei-Hao Li; Yi-Lei Liu; Jian-Chi Lun; Yong-Ming He; Lu-Ping Tang (International Journal of Biometeorology, 2021)
With the global warming, the harm of heat stress (HS) to the breeding industry has become more common, which causes the decline of animal production performance and low immunity. This study aimed to analyze the effect of HS on the intestinal immune function of Salmonella- infected chickens. Fourteen-day-old broilers were divided into the following four groups of eight replicates: control (Control), heat stress (HS), Salmonella Typhimurium (ST), and heat stress + Salmonella Typhimurium (HS+ST). The broilers were subjected to a heat stress of 35 °C from 15 to 28 days of age. Salmonella Typhimurium (ST, 14028, 10 9 cfu/mL) was inoculated, via oral administration at 29 days of age, into ST and HS+ST group birds. On the 4th day after Salmonella Typhimurium administration, an increase in jejunum IgA levels was observed in chickens infected with Salmonella Typhimurium. Mechanistic regulation of TLR4-NFκB-NLRP3 and TLR4-TBK1 signaling by heat stress was evaluated in Salmonella Typhimurium–infected broilers. Heat stress markedly inhibited the expression of cytokines including TNF-α, IL-6, IL-1β, NLRP3, caspase-1, NF-κB-p65, and p-NF-κB-p65, and the TLR4-TBK1 cytokines IFN-α, IFN-γ, p-IRF3, and p-TBK1 in jejunum of broilers infected with Salmonella Typhimurium. Collectively, our results demonstrate that heat stress can inhibit intestinal immune response by downregulating the expression of TLR4-NFκB-NLRP3 and TLR4-TBK1 signaling pathways in broilers infected with Salmonella Typhimurium.

A new strategy combined HASM and classical interpolation methods for DEM construction in areas without sufficient terrain data - Jing Wang; Ming-wei Zhao; Ling Jiang; Can-can Yang; Xiao-li Huang; Yan Xu; Jie Lu (Journal of Mountain Science, 2021)

Genetic control and phenotypic characterization of panicle architecture and grain yield-related traits in foxtail millet (Setaria italica) - Hui Zhi; Qiang He; Sha Tang; Junjun Yang; Wei Zhang; Huifang Liu; Yanchao Jia; Guanqing Jia; Aiying Zhang; Yuhui Li; Erhu Guo; Ming Gao; et al. (Theoretical and Applied Genetics, 2021)

Improvement in the risk assessment of oral leukoplakia through morphology-related copy number analysis - Xiaotian Li; Lu Liu; Jianyun Zhang; Ming Ma; Lisha Sun; Xuefen Li; Heyu Zhang; Jianbin Wang; Yanyi Huang; Tiejun Li (Science China Life Sciences, 2021)

Arsenate toxicity to the marine microalga Chlorella vulgaris increases under phosphorus-limited condition - Xinya Li; Jin-Fen Pan; Zhiying Lu; Ming Wei; Zhongsheng Gao; Zhenguang Yan (Environmental Science and Pollution Research, 2021)

Application of Plant Print Identification Technology in Salt-resistant Soybean Breeding - Yan Li; Xia Li; Zi-qi Chen; Ying Ma; Guang-yu Yang; Ying Zhang; Ming-chun Sun; Li-hong Zhang; Jin-meng Chu; Jing-mei Lu; Jun Zhu; Ji-hong You (Journal of Plant Growth Regulation, 2021)

Transforming growth factor β as a possible independent factor in chronic hepatitis B - Ming-hui Li; Yao Lu; Fang-fang Sun; Qi-qi Chen; Lu Zhang; Hui-hui Lu; Zhan Zeng; Wei Yi; Yao Xie (Archives of Virology, 2021)

Vertical Profiles of Volatile Organic Compounds in Suburban Shanghai - Yuhan Liu; Hongli Wang; Shengao Jing; Ming Zhou; Shenrong Lou; Kun Qu; Wanyi Qiu; Qian Wang; Shule Li; Yaqin Gao; Yusi Liu; Xiaobing Li; et al. (Advances in Atmospheric Sciences, 2021)

Different posterior hippocampus and default mode network modulation in young APOE ε4 carriers: a functional connectome-informed phenotype longitudinal study - Li Juan Zheng; Li Lin; U. Joseph Schoepf; Akos Varga-Szemes; Rock H. Savage; Han Zhang; Yun Fei Wang; Xin Yuan Zhang; Song Luo; Ya Liu; Gui Fen Yang; Guang Ming Lu; et al. (Molecular Neurobiology, 2021)

OsGSTU6 Contributes to Cadmium Stress Tolerance in Rice by Involving in Intracellular ROS Homeostasis - Xiu-Qing Jing; Meng-Ru Zhou; Xiu-Min Nie; Lu Zhang; Peng-Tao Shi; Abdullah Shalmani; Hai Miao; Wen-Qiang Li; Wen-Ting Liu; Kun-Ming Chen (Journal of Plant Growth Regulation, 2021)

Supercooling capacity and cold tolerance of the South American tomato pinworm, Tuta absoluta, a newly invaded pest in China - Xiao-wei Li; Dong Li; Zhi-jun Zhang; Jun Huang; Jin-ming Zhang; Muhammad Hafeez; Li-kun Wang; Wen-chao Guo; Yao-bin Lu (Journal of Pest Science, 2021)
Tuta absoluta is a devastating invasive pest worldwide, causing severe damage to the global tomato industry. It has been recorded recently in the northwestern border areas of China, posing a significant threat to tomato production. It was presumed that the region's winter-related low temperatures would avert the alien species from successfully overwintering. In this study, the supercooling capacity and low-temperature tolerance of this pest were examined under laboratory conditions and its overwintering potential in Xinjiang was estimated. The results showed that the lowest supercooling point was recorded in the adult stage (− 19.47 °C), while the highest (− 18.11 °C) was recorded in the pupal stage. The supercooling points of pupae and adults were not influenced by gender. The Ltemp 50 and Ltemp 90 of female and male adults were the lowest when exposed to cold for 2 h. However, when the duration of exposure extended from 4 to 10 h, the Ltemp 50 and Ltemp 90 of female and male pupae were the lowest. Comparison of the lowest Ltemp 50 and Ltemp 90 with temperatures in January indicated that T. absoluta might not be able to overwinter in most of the northern and central regions of Xinjiang. However, in the southern regions, the extremely low temperature was higher than the Ltemp 90 , suggesting that T. absoluta has a higher overwintering potential in these regions. These results form a basis for predicting the dispersal potential and possible geographic range of this pest in Xinjiang. In addition, our findings provide guidance for the control of this pest by reducing overwintering shelters.

Enhancement of IUdR Radiosensitization in Cancer Therapy by Low-Energy Transmission X Ray Irradiation - Chien-Chih Ke; Jia-Je Li; Hsueh-Peng Wu; Wen-Wang Kuo; Yi-An Chen; Cheng-Hsiu Lu; Hsin-Ell Wang; Shih-Ming Hsu; Ya-Ju Hsieh; Ren-Shyan Liu (Journal of Medical and Biological Engineering, 2021)

Antibacterial and anti-biofilm effects of fatty acids extract of dried Lucilia sericata larvae against Staphylococcus aureus and Streptococcus pneumoniae in vitro - Jing Liu; Jun Jiang; Junwei Zong; Bin Li; Taowen Pan; Yunpeng Diao; Zhen Zhang; Xueyang Zhang; Ming Lu; Shouyu Wang (Natural Product Research, 2021)

Study on Microwave Heating Order and Electromagnetic Characteristics of Copper and Gold Ores - Feng Lin; Xia-Ting Feng; Gao-Ming Lu; Xiang-Xin Su; Shi-Ping Li; Jiu-yu Zhang (Rock Mechanics and Rock Engineering, 2021)

Synthesis and antitumor evaluation of (aryl)methyl-amine derivatives of dehydroabietic acid-based B ring-fused-thiazole as potential PI3K/AKT/mTOR signaling pathway inhibitors - Nai-Yuan Chen; Yu-Lan Xie; Guo-Dong Lu; Fang Ye; Xin-Yu Li; Yu-Wen Huang; Ming-Li Huang; Tie-Yu Chen; Cui-Ping Li (Molecular Diversity, 2021)

Targeted deletion of HAI-1 increases prostasin proteolysis but decreases matriptase proteolysis in human keratinocytes - Dajun D. Lu; Yayun Gu; Sheng-Wen A. Li; Robert J. Barndt; Shih-Ming Huang; Jehng-Kang Wang; Hui Chen Su; Michael D. Johnson; Chen-Yong Lin (Human Cell, 2021)

EEG-Based Anxious States Classification Using Affective BCI-Based Closed Neurofeedback System - Chao Chen; Xuecong Yu; Abdelkader Nasreddine Belkacem; Lin Lu; Penghai Li; Zufeng Zhang; Xiaotian Wang; Wenjun Tan; Qiang Gao; Duk Shin; Changming Wang; Sha Sha; et al. (Journal of Medical and Biological Engineering, 2021)

Simultaneous detection of multiple bacterial and viral aquatic pathogens using a fluorogenic loop‐mediated isothermal amplification‐based dual‐sample microfluidic chip - Qian‐Jin Zhou; Jian‐Fei Lu; Xiu‐Rong Su; Jing‐Lei Jin; Shang‐Yang Li; Yan Zhou; Lei Wang; Xin‐Bin Shao; Yao‐Hua Wang; Mao‐Cang Yan; Ming‐Yun Li; Jiong Chen (Journal of Fish Diseases, 2021)
Rapid and user‐friendly diagnostic tests are necessary for early diagnosis and immediate detection of diseases, particularly for on‐site screening of pathogenic microorganisms in aquaculture. In this study, we developed a dual‐sample microfluidic chip integrated with a real‐time fluorogenic loop‐mediated isothermal amplification assay (dual‐sample on‐chip LAMP) to simultaneously detect 10 pathogenic microorganisms, that is Aeromonas hydrophila , Edwardsiella tarda , Vibrio harveyi , V. alginolyticus , V. anguillarum , V. parahaemolyticus , V. vulnificus , infectious hypodermal and haematopoietic necrosis virus, infectious spleen and kidney necrosis virus, and white spot syndrome virus. This on‐chip LAMP provided a nearly automated protocol that can analyse two samples simultaneously, and the tests achieved limits of detection (LOD) ranging from 10 0 to 10 –1 pg/μl for genomic DNA of tested bacteria and 10 –4 to 10 –5 pg/μl for recombinant plasmid DNA of tested viruses, with run times averaging less than 30 min. The coefficient of variation for the time‐to‐positive value was less than 10%, reflecting a robust reproducibility. The clinical sensitivity and specificity were 93.52% and 85.53%, respectively, compared to conventional microbiological or clinical methods. The on‐chip LAMP assay provides an effective dual‐sample and multiple pathogen analysis, and thus would be applicable to on‐site detection and routine monitoring of multiple pathogens in aquaculture.

Changes in soil available cadmium and bacterial communities after fallowing depend on contamination levels - Xinqi Wang; Xia Lu; Xingyun Yi; Zhuoqing Li; Yimin Zhou; Guilan Duan; Ming Lei (Journal of Soils and Sediments, 2021)

EPG-recorded Feeding Behaviors Reveal Adaptability and Competitiveness in Two Species of Bemisia tabaci (Hemiptera: Aleyrodidae) - Shao-hua Lu; Jing-jing Li; Run-e Bai; Feng-ming Yan (Journal of Insect Behavior, 2021)

Noroleanane-type triterpenoids from Dolichos trilobus L. and their anti-α-glucosidase activities - Ming Luo; Yan-Hong Li; Ya Lu; Yan Yuan; Rong-Sheng Ruan; Yong-Ming Chuan; Kai Tian; Xiang-Zhong Huang (Natural Product Research, 2021)

QTL mapping for foxtail millet plant height in multi-environment using an ultra-high density bin map - Qiang He; Hui Zhi; Sha Tang; Lu Xing; Suying Wang; Haigang Wang; Aiying Zhang; Yuhui Li; Ming Gao; Haijin Zhang; Guoqiu Chen; Shutao Dai; et al. (Theoretical and Applied Genetics, 2021)

Task-related functional magnetic resonance imaging-based neuronavigation for the treatment of depression by individualized repetitive transcranial magnetic stimulation of the visual cortex - Zhijun Zhang; Hongxing Zhang; Chun-Ming Xie; Meng Zhang; Yachen Shi; Ruize Song; Xiang Lu; Haisan Zhang; Kun Li; Bi Wang; Yongfeng Yang; Xianrui Li; et al. (Science China Life Sciences, 2021)

Geochemical characteristics and geological significance of chert nodules in Qixia formation, Pingding Mountain, lower Yangtze Plate - Jun Li; Lu-wang Chen; Chun-ming Hao; Jie Zhang; Song Chen; He-rong Gui (Journal of Mountain Science, 2021)

Localization and characterization of Citrus centromeres by combining half-tetrad analysis and CenH3-associated sequence profiling - Qiang-Ming Xia; Lu-Ke Miao; Kai-Dong Xie; Zhao-Ping Yin; Xiao-Meng Wu; Chun-Li Chen; Jude W. Grosser; Wen-Wu Guo (Plant Cell Reports, 2020)

Iron Aggravates the Depressive Phenotype of Stressed Mice by Compromising the Glymphatic System - Shanshan Liang; Yan Lu; Zexiong Li; Shuai Li; Beina Chen; Manman Zhang; Binjie Chen; Ming Ji; Wenliang Gong; Maosheng Xia; Alexei Verkhratsky; Xu Wu; et al. (Neuroscience Bulletin, 2020)

Using sowing date management to promote micronutrient quality and alleviate cadmium accumulation in rice grains - Lin-lin Shi; Ming-xing Shen; Hong-jun Wu; Chang-ying Lu; Li-juan Mei; Xin-lian Zhu; Hai-hou Wang; Yun-Sheng Song (Cereal Research Communications, 2020)

HuR Promotes Ovarian Cancer Cell Proliferation by Regulating TIMM44 mRNA Stability - Xiaohui Yu; Yujiao Li; Yumei Ding; Hong Zhang; Ning Ding; Ming Lu (Cell Biochemistry and Biophysics, 2020)

Gut dysbiosis-influence on amygdala-based functional activity in patients with end stage renal disease: a preliminary study - Li Juan Zheng; Li Lin; Jianhui Zhong; Zhihong Zhang; Yu Bing Ye; Xin Yuan Zhang; Yun Fei Wang; Han Zhang; Ya Liu; Guang Ming Lu; Dehua Gong; Long Jiang Zhang (Brain Imaging and Behavior, 2020)

Analysis of genetic architecture and favorable allele usage of agronomic traits in a large collection of Chinese rice accessions - Xiuxiu Li; Zhuo Chen; Guomin Zhang; Hongwei Lu; Peng Qin; Ming Qi; Ying Yu; Bingke Jiao; Xianfeng Zhao; Qiang Gao; Hao Wang; Yunyu Wu; et al. (Science China Life Sciences, 2020)

Genome-wide transcriptome and proteome profiles indicate an active role of alternative splicing during de-etiolation of maize seedlings - Zhen Yan; Zhuo Shen; Zhe Li; Qing Chao; Lei Kong; Zhi-Fang Gao; Qing-Wei Li; Hai-Yan Zheng; Cai-Feng Zhao; Cong-Ming Lu; Ying-Wei Wang; Bai-Chen Wang (Planta, 2020)

Multiple environmental factors analysis of flash flood risk in Upper Hanjiang River, southern China - Ming Zhong; Tao Jiang; Kun Li; Qiaoqian Lu; Jiao Wang; Jiajun Zhu (Environmental Science and Pollution Research, 2020)

Postchemotherapy hippocampal functional connectivity patterns in patients with breast cancer: a longitudinal resting state functional MR imaging study - Yun Feng; Dilihumaer Tuluhong; Zhao Shi; Li Juan Zheng; Tao Chen; Guang Ming Lu; Shaohua Wang; Long Jiang Zhang (Brain Imaging and Behavior, 2020)

Comparison of mRNA Expression of P2X Receptor Subtypes in Different Arterial Tissues of Rats - Ling-Zhi Li; Li-Hui Yue; Zhi-Min Zhang; Jing Zhao; Lei-Ming Ren; Hong-Jie Wang; Lu Li (Biochemical Genetics, 2020)

Genome-Wide Association Study of Plant and Ear Height in Maize - Shi Lu; Mu Li; Mo Zhang; Ming Lu; Xinqi Wang; Piwu Wang; Wenguo Liu (Tropical Plant Biology, 2020)

Addition of oyster shell to enhance organic matter degradation and nitrogen conservation during anaerobic digestate composting - Ming-Yi Lu; Xiao-Shuang Shi; Xu Li; Shu-Juan Lian; Dong-Yan Xu; Rong-Bo Guo (Environmental Science and Pollution Research, 2020)

A fundamental theorem for eco-environmental surface modelling and its applications - Tianxiang Yue; Na Zhao; Yu Liu; Yifu Wang; Bin Zhang; Zhengping Du; Zemeng Fan; Wenjiao Shi; Chuanfa Chen; Mingwei Zhao; Dunjiang Song; Shihai Wang; et al. (Science China Earth Sciences, 2020)

Influences of ABC transporter and CYP3A4/5 genetic polymorphisms on the pharmacokinetics of lenvatinib in Chinese healthy subjects - Jiaming Li; Xiaoqian Wang; Chen Ning; Zhaoyu Wang; Yao Wang; Ming Zheng; Siliang Zhang; Yang Lu; Yongjie Zhang; Ning Li; Xijing Chen; Di Zhao (European Journal of Clinical Pharmacology, 2020)

Identification of Ala2Thr mutation in insulin gene from a Chinese MODY10 family - Juan Zhang; Yanjun Liu; Ming Li; Xiaoxu Ge; Ying Wang; Xin Huang; Di Yang; Rong Zhang; Yating Chen; Ming Lu; Jun Yin; Mingqiang Song; et al. (Molecular and Cellular Biochemistry, 2020)

MicroRNA-153-3p enhances the sensitivity of chronic myeloid leukemia cells to imatinib by inhibiting B-cell lymphoma-2-mediated autophagy - Yu-Ling Li; Jia-Ming Tang; Xiao-Yun Chen; Bing Luo; Guo-Hua Liang; Qian Qu; Zi-Yuan Lu (Human Cell, 2020)

Dust contamination on surface of transmission line insulators in air-polluted regions in China: statistical characteristics, adhesion mechanism, and environmental impact factors - Miao Jiang; Jingrun Guo; Yunpeng Jiang; Lee Li; Ming Lu (Environmental Science and Pollution Research, 2020)

Immunomagnetic separation-based nanogold enhanced surface plasmon resonance and colloidal gold test strips for rapid detection of Vibrio parahaemolyticus - Jun Zhou; Chundan Zhang; Xuan Zhang; Chenyang Lu; Tinghong Ming; Ye Li; Xiurong Su (Archives of Microbiology, 2020)

Genome-wide identification of the NPR1-like gene family in Brassica napus and functional characterization of BnaNPR1 in resistance to Sclerotinia sclerotiorum - Zheng Wang; Lu-Yue Ma; Xiao Li; Feng-Yun Zhao; Rehman Sarwar; Jun Cao; Yu-Long Li; Li-Na Ding; Ke-Ming Zhu; Yan-Hua Yang; Xiao-Li Tan (Plant Cell Reports, 2020)

LINC01410/miR-23c/CHD7 functions as a ceRNA network to affect the prognosis of patients with endometrial cancer and strengthen the malignant properties of endometrial cancer cells - Ming Lu; Ning Ding; Shichao Zhuang; Yujiao Li (Molecular and Cellular Biochemistry, 2020)

Short-term associations between ambient fine particulate matter pollution and hospital visits for chronic obstructive pulmonary disease in Yinzhou District, China - Cheng-yi Lin; Die Li; Jie-ming Lu; Zhe-bin Yu; Yao Zhu; Peng Shen; Meng-ling Tang; Ming-juan Jin; Hong-bo Lin; Li-ming Shui; Kun Chen; Jian-bing Wang (Environmental Science and Pollution Research, 2020)

Optimization of an mRNA vaccine assisted with cyclodextrin-polyethyleneimine conjugates - Lu Tan; Tao Zheng; Man Li; Xiaofang Zhong; Yao Tang; Ming Qin; Xun Sun (Drug Delivery and Translational Research, 2020)

MicroRNA-625-5p Sponges lncRNA MALAT1 to Inhibit Cervical Carcinoma Cell Growth by Suppressing NF-κB Signaling - Yujiao Li; Yumei Ding; Ning Ding; Hong Zhang; Ming Lu; Xiaorong Cui; Xiaohui Yu (Cell Biochemistry and Biophysics, 2020)

Phylogenetic patterns of shrub communities along the longitudinal and latitudinal gradients on the northeastern Qinghai–Tibetan Plateau - Yuan-ming Xiao; Lu-cun Yang; Xiu-qing Nie; Chang-bin Li; Feng Xiong; Guo-ying Zhou (Journal of Mountain Science, 2020)

Xanthohumol protects neuron from cerebral ischemia injury in experimental stroke - Yang Jiao; Yuze Cao; Xiaoyu Lu; Jianjian Wang; Aigul Saitgareeva; Xiaotong Kong; Chang Song; Jie Li; Kuo Tian; Shuoqi Zhang; Ming Bai; Shuang Li; et al. (Molecular Biology Reports, 2020)

Separation and preparation of N-glycans based on ammonia-catalyzed release method - Meifang Yang; Ming Wei; Chengjian Wang; Yu Lu; Wanjun Jin; Xi Gao; Cheng Li; Langhong Wang; Linjuan Huang; Zhongfu Wang (Glycoconjugate Journal, 2020)

NMR-based metabolomics reveals the metabolite profiles of Vibrio parahaemolyticus under blood agar stimulation - Jun Zhou; Chundan Zhang; Jiaojiao Han; Chenyang Lu; Ye Li; Tinghong Ming; Xiurong Su (Archives of Microbiology, 2020)

Phosphate-modified ferric-based material remediates lead and arsenic co-contaminated soil and enhances maize seedling growth - Yining Yuan; Ming Lu; Naimei Tu; Yaoyao Li (Environmental Science and Pollution Research, 2020)

Seismic acceleration signal analysis and application - Huai-Bang Zhang; Lu-Ming Li; Guang-De Zhang; Bo-Han Zhang; Miao-Miao Sun (Applied Geophysics, 2020)

An accounting of the external environmental costs of coal in Inner Mongolia using the pollution damage method - Hao-Dong Lv; Jin-Sheng Zhou; Lin Yang; Yi-Ming Li; Lu Liu (Environment, Development and Sustainability, 2020)

Evidence for the paternal mitochondrial DNA in the crucian carp-like fish lineage with hybrid origin - Shi Wang; Ni Jiao; Lu Zhao; Meiwen Zhang; Pei Zhou; Xuexue Huang; Fangzhou Hu; Conghui Yang; Yuqin Shu; Wuhui Li; Chun Zhang; Min Tao; et al. (Science China Life Sciences, 2020)

Changes in cultivated land patterns and driving forces in the Three Gorges Reservoir area, China, from 1992 to 2015 - Yu-xin Zhang; Yu-kuan Wang; Bin Fu; Ming Li; Ya-feng Lu; Amod Mani Dixit; Suresh Chaudhary; Shan Wang (Journal of Mountain Science, 2020)

Lactobacillus jinshani sp. nov., isolated from solid-state vinegar culture of Zhenjiang aromatic vinegar - Yongjian Yu; Xin Li; Junhong Zhang; Li-Juan Chai; Zhen-Ming Lu; Zheng-Hong Xu (Antonie van Leeuwenhoek, 2020)

Microencapsulated β-carotene preparation using different drying treatments - Xiang-yu Li; Mian-bin Wu; Min Xiao; Shu-huan Lu; Zhi-ming Wang; Jian-ming Yao; Li-rong Yang (Journal of Zhejiang University-SCIENCE B, 2019)

MiR-26a promotes fracture healing of nonunion rats possibly by targeting SOSTDC1 and further activating Wnt/β-catenin signaling pathway - Liang Sun; Zhong Li; Hanzhong Xue; Teng Ma; Cheng Ren; Ming Li; Yao Lu; He Sun; Kun Zhang (Molecular and Cellular Biochemistry, 2019)

Endoscopic ultrasonography is useful in the diagnosis and treatment of rectal neuroendocrine neoplasms: a case series - Qing Gu; Yi-ming Lin; Li Cen; Min Xu; Hong-zhang Li; Xian-chu Lin; Chao Lu (Journal of Zhejiang University-SCIENCE B, 2019)

Conflict between wild boars (Sus scrofa) and farmers: distribution, impacts, and suggestions for management of wild boars in the Three Gorges Reservoir Area - Qin Liu; Kun Yan; Ya-feng Lu; Ming Li; Yang-yang Yan (Journal of Mountain Science, 2019)

Identification of the optimal insertion site for expression of a foreign gene in an infectious hematopoietic necrosis virus vector - Jing-Zhuang Zhao; Li-Ming Xu; Miao Liu; Yong-Sheng Cao; Jia-Sheng Yin; Hong-Bai Liu; Tong-Yan Lu; Zhen-Yu Zhang (Archives of Virology, 2019)

The Microwave-Induced Fracturing of Hard Rock - Gao-Ming Lu; Xia-Ting Feng; Yuan-Hui Li; Xiwei Zhang (Rock Mechanics and Rock Engineering, 2019)

Paeoniflorin attenuates impairment of spatial learning and hippocampal long-term potentiation in mice subjected to chronic unpredictable mild stress - Si-Cheng Liu; Wei-Yan Hu; Wei-Yuan Zhang; Lu Yang; Yan Li; Zhi-Cheng Xiao; Ming Zhang; Zhi-Yong He (Psychopharmacology, 2019)

Solidification/stabilization of municipal solid waste incineration fly ash using uncalcined coal gangue–based alkali-activated cementitious materials - Shujie Zhao; Faheem Muhammad; Lin Yu; Ming Xia; Xiao Huang; Binquan Jiao; Ning Lu; Dongwei Li (Environmental Science and Pollution Research, 2019)

Experimental Investigation on the Effects of Microwave Treatment on Basalt Heating, Mechanical Strength, and Fragmentation - Gao-Ming Lu; Xia-Ting Feng; Yuan-Hui Li; Ferri Hassani; Xiwei Zhang (Rock Mechanics and Rock Engineering, 2019)

Cloud Radiative Feedbacks during the ENSO Cycle Simulated by CAMS-CSM - Lin Chen; Lijuan Hua; Xinyao Rong; Jian Li; Lu Wang; Guo Zhang; Ming Sun; Zi’an Ge (Journal of Meteorological Research, 2019)

F‐box proteins MoFwd1, MoCdc4 and MoFbx15 regulate development and pathogenicity in the rice blast fungus Magnaporthe oryzae - Huan‐Bin Shi; Nan Chen; Xue‐Ming Zhu; Shuang Liang; Lin Li; Jiao‐Yu Wang; Jian‐Ping Lu; Fu‐Cheng Lin; Xiao‐Hong Liu (Environmental Microbiology, 2019)
Summary The Skp1‐Cul1‐F‐box‐protein (SCF) ubiquitin ligases are important parts of the ubiquitin system controlling many cellular biological processes in eukaryotes. However, the roles of SCF ubiquitin ligases remain unclear in phytopathogenic Magnaporthe oryzae . Here, we cloned 24 F‐box proteins and confirmed that 17 proteins could interact with MoSkp1, showing their potential to participate in SCF complexes. To determine their functions, null mutants of 21 F‐box‐containing genes were created. Among them, the F‐box proteins MoFwd1, MoCdc4 and MoFbx15 were found to be required for growth, development and full virulence. Fluorescent‐microscopy observations demonstrated that both MoFbx15 and MoCdc4 were localized to the nucleus, compared with MoFwd1, which was distributed in the cytosol. MoCdc4 and MoFwd1 bound to MoSkp1 via the F‐box domain, the deletion of which abrogated their function. Race tube and qRT‐PCR assays confirmed that MoFwd1 was involved in circadian rhythm by regulating transcription and protein stability of the core circadian clock regulator MoFRQ . Moreover, MoFWD1 also orchestrates conidial germination by influencing conidial amino acids pools and oxidative stress release. Overall, our results indicate that SCF ubiquitin ligases play indispensable roles in development and pathogenicity in M. oryzae .

Evaluation of the integrated multi-satellite retrievals for global precipitation measurement over the Tibetan Plateau - Lu Ma; Lin Zhao; Li-ming Tian; Li-ming Yuan; Yao Xiao; Le-le Zhang; De-fu Zou; Yong-ping Qiao (Journal of Mountain Science, 2019)

Identification and Evaluation of Resistance to Sugarcane Streak Mosaic Virus (SCSMV) and Sorghum Mosaic Virus (SrMV) in Excellent Sugarcane Innovation Germplasms in China - Wen-Feng Li; Hong-Li Shan; Xiao-Yan Cang; Xin Lu; Rong-Yue Zhang; Xiao-Yan Wang; Jiong Yin; Zhi-Ming Luo; Ying-Kun Huang (Sugar Tech, 2019)

MOTS-c peptide regulates adipose homeostasis to prevent ovariectomy-induced metabolic dysfunction - Huanyu Lu; Ming Wei; Yue Zhai; Qingyang Li; Zichen Ye; Li Wang; Wenjing Luo; Jingyuan Chen; Zifan Lu (Journal of Molecular Medicine, 2019)

l-Carnitine inhibits the senescence-associated secretory phenotype of aging adipose tissue by JNK/p53 pathway - Lian-wei Yang; Ming Song; Yu-lin Li; Ya-peng Liu; Chun Liu; Lu Han; Zhi-hao Wang; Wei Zhang; Yan-qiu Xing; Ming Zhong (Biogerontology, 2019)

Experimental Study and Estimation of Groundwater Fluctuation and Ground Settlement due to Dewatering in a Coastal Shallow Confined Aquifer - Jiong Li; Ming-Guang Li; Lu-Lu Zhang; Hui Chen; Xiao-He Xia; Jin-Jian Chen (Journal of Marine Science and Engineering, 2019)
The coastal micro-confined aquifer (MCA) in Shanghai is characterized by shallow burial depth, high artesian head, and discontinuous distribution. It has a significant influence on underground space development, especially where the MCA is directly connected with deep confined aquifers. In this paper, a series of pumping well tests were conducted in the MCA located in such area to investigate the dewatering-induced groundwater fluctuations and stratum deformation. In addition, a numerical method is proposed for the estimation of hydraulic parameter, and an empirical prediction method is developed for dewatering-induced ground settlement. Test results show that groundwater drawdowns and soil settlement can be observed not only in MCA but also in the aquifers underneath it. This indicates that there is a close hydraulic connection among each aquifer. Moreover, the distributions and development of soil settlement at various depths are parallel to those of groundwater drawdowns in most areas of the test site except the vicinity of pumping wells, where collapse-induced subsidence due to high-speed flow may occur. Furthermore, the largest deformation usually occurs at the top of the pumping aquifer instead of the ground surface, because the top layer is expanded due to the stress arch formed in it. Finally, the proposed methods are validated to be feasible according to the pumping well test results and can be employed to investigate the responses of groundwater fluctuations and stratum deformations due to dewatering in MCA.

Detection of coastal wetland change in China: a case study in Hangzhou Bay - Nan Li; Longwei Li; Dengsheng Lu; Yinlong Zhang; Ming Wu (Wetlands Ecology and Management, 2019)

Heterologous overexpression of Lithospermum erythrorhizon LeERF-1 gene increases drought and pathogen resistance in Arabidopsis - Rong-Jun Fang; Ai-Qian Li; Ru-Nan Tian; Wen-Ju Zhang; Ai-Lan Zou; Feng-Yao Wu; Yong-Hui Liao; Xiao-Ming Wang; Yan-Jun Pang; Rong-Wu Yang; Gui-Hua Lu; Jin-Liang Qi; et al. (Acta Physiologiae Plantarum, 2019)

Correlation between S100A11 and the TGF-β1/SMAD4 pathway and its effects on the proliferation and apoptosis of pancreatic cancer cell line PANC-1 - Yi-Fei Ji; Tao Li; Feng Jiang; Wen-Kai Ni; Cheng-Qi Guan; Zhao-Xiu Liu; Cui-Hua Lu; Run-Zhou Ni; Wei Wu; Ming-Bing Xiao (Molecular and Cellular Biochemistry, 2019)

Coastal wetland classification with multiseasonal high-spatial resolution satellite imagery - Nan Li; Dengsheng Lu; Ming Wu; Yinlong Zhang; Linying Lu (International Journal of Remote Sensing, 2018)

β2-AR regulates the expression of AKR1B1 in human pancreatic cancer cells and promotes their proliferation via the ERK1/2 pathway - Ming-Bing Xiao; Dan-Dan Jin; Yu-Jie Jiao; Wen-Kai Ni; Jin-Xia Liu; Li-Shuai Qu; Cui-Hua Lu; Run-Zhou Ni; Feng Jiang; Wei-Chang Chen (Molecular Biology Reports, 2018)

PVP VA64 as a novel release-modifier for sustained-release mini-matrices prepared via hot melt extrusion - Yongcheng Li; Ming Lu; Chuanbin Wu (Drug Delivery and Translational Research, 2018)

Cryo-EM structure reveals cylindrical nucleocapsids from two polydnaviruses - Ji-Hui Cui; Ya-Bin Chen; Ming Li; Qiu-Chen Cai; Li-Dan Zhang; Zi-Yun Lu; Jian-Cheng Li; Qi-Shun Zhu; Gang Ji; Kai-Jun Luo (Archives of Virology, 2018)

Genome-wide identification and characterization of ALTERNATIVE OXIDASE genes and their response under abiotic stresses in Camellia sinensis (L.) O. Kuntze - Chang-Qing Ding; Sophia Ng; Lu Wang; Yu-Chun Wang; Na-Na Li; Xin-Yuan Hao; Jian-Ming Zeng; Xin-Chao Wang; Ya-Jun Yang (Planta, 2018)

Acute effect of fine and coarse particular matter on cardiovascular visits in Ningbo, China - Pei-wen Zheng; Peng Shen; Zhen-hua Ye; Zhen-yu Zhang; Peng-fei Chai; Die Li; Ming-juan Jin; Meng-Ling Tang; Huai-chu Lu; Hong-bo Lin; Jian-bing Wang; Kun Chen (Environmental Science and Pollution Research, 2018)

The primate extinction crisis in China: immediate challenges and a way forward - Baoguo Li; Ming Li; Jinhua Li; Pengfei Fan; Qingyong Ni; Jiqi Lu; Xuming Zhou; Yongcheng Long; Zhigang Jiang; Peng Zhang; Zhipang Huang; Chenming Huang; et al. (Biodiversity and Conservation, 2018)

Development of a TaqMan probe-based quantitative reverse transcription PCR assay for detection of Getah virus RNA - Ning Shi; Hao Liu; Li-xia Li; Bo Hu; Lei Zhang; Chuan-fang Zhao; Xiao-yu Deng; Xin-tong Li; Xiang-hong Xue; Xue Bai; Hai-ling Zhang; Rong-guang Lu; et al. (Archives of Virology, 2018)

Dynamic behaviour of weathered red mudstone in Sichuan (China) under triaxial cyclic loading - Chong-lei Zhang; Guan-lu Jiang; Li-jun Su; Wei-ming Liu (Journal of Mountain Science, 2018)

Impacts of future climate change (2030-2059) on debris flow hazard: A case study in the Upper Minjiang River basin, China - Ming Li; Cong-shan Tian; Yu-kuan Wang; Qin Liu; Ya-feng Lu; Wang Shan (Journal of Mountain Science, 2018)

An improved grey wolf optimizer algorithm for the inversion of geoelectrical data - Si-Yu Li; Shu-Ming Wang; Peng-Fei Wang; Xiao-Lu Su; Xin-Song Zhang; Zhi-Hui Dong (Acta Geophysica, 2018)

Effect of dry density on the liquefaction behaviour of Quaternary silt - Chong-lei Zhang; Guan-lu Jiang; Li-jun Su; Wei-ming Liu; Gong-dan Zhou (Journal of Mountain Science, 2018)

Physiological and quantitative proteomic analyses unraveling potassium deficiency stress response in alligator weed (Alternanthera philoxeroides L.) root - Li-qin Li; Lun Liu; Wei Zhuo; Qian Chen; Sheng Hu; Shuang Peng; Xi-yao Wang; Yi-fei Lu; Li-ming Lu (Plant Molecular Biology, 2018)

Tissue Distribution and Gender-Specific Protein Expression of Cytochrome P450 in five Mouse Genotypes with a Background of FVB - Jiamei M. Chen; Qisong S. Zhang; Xiaoyan Y. Li; Xia Gong; Yanjiao J. Ruan; Sijing J. Zeng; Linlin L. Lu; Xiaoxiao X. Qi; Ying Wang; Ming Hu; Lijun J. Zhu; Zhongqiu Q. Liu (Pharmaceutical Research, 2018)

Protection of plasma transfusion against lipopolysaccharide/d-galactosamine-induced fulminant hepatic failure through inhibiting apoptosis of hepatic cells in mice - Bing-yu Chen; Lu-xi Jiang; Ke Hao; Lu Wang; Ying Wang; Yi-wei Xie; Jian Shen; Meng-hua Zhu; Xiang-ming Tong; Kai-qiang Li; Zhen Wang (Journal of Zhejiang University-SCIENCE B, 2018)

Association between short-term exposure to ambient air pollution and daily mortality: a time-series study in Eastern China - Die Li; Jian-bing Wang; Zhen-yu Zhang; Peng Shen; Pei-wen Zheng; Ming-juan Jin; Huai-chu Lu; Hong-bo Lin; Kun Chen (Environmental Science and Pollution Research, 2018)

Identification of blasting vibration and coal-rock fracturing microseismic signals - Xing-Li Zhang; Rui-Sheng Jia; Xin-Ming Lu; Yan-Jun Peng; Wei-Dong Zhao (Applied Geophysics, 2018)

Three-dimensional analysis of ozone and PM2.5 distributions obtained by observations of tethered balloon and unmanned aerial vehicle in Shanghai, China - Xiao-Bing Li; Dongfang Wang; Qing-Chang Lu; Zhong-Ren Peng; Qingyan Fu; Xiao-Ming Hu; Juntao Huo; Guangli Xiu; Bai Li; Chao Li; Dong-Sheng Wang; Hanyu Wang (Stochastic Environmental Research and Risk Assessment, 2018)

Avian influenza viruses (AIVs) H9N2 are in the course of reassorting into novel AIVs - Hui-ping Chang; Li Peng; Liang Chen; Lu-fang Jiang; Zhi-jie Zhang; Cheng-long Xiong; Gen-ming Zhao; Yue Chen; Qing-wu Jiang (Journal of Zhejiang University-SCIENCE B, 2018)

Toxic effect and mechanism of four ionic liquids on seedling taproots of Arabidopsis thaliana - Ming Li; Yonglai Xue; Zhenjiang Liu; Jin Guo; Liyun Liu; Yuanyuan Zhang; Lu Gao; Lizhao Wang; Yin Cui; Daolin Du (Environmental Science and Pollution Research, 2018)

Similar simulation device for unloading effect of deep roadway excavation and its application - Chun-liang Dong; Guang-ming Zhao; Xiao-yu Lu; Xiang-rui Meng; Ying-ming Li; Xiang Cheng (Journal of Mountain Science, 2018)

Different Hippocampus Functional Connectivity Patterns in Healthy Young Adults with Mutations of APP/Presenilin-1/2 and APOEε4 - Li Juan Zheng; Yun Yan Su; Yun Fei Wang; U. Joseph Schoepf; Akos Varga-Szemes; Jonathan Pannell; Xue Liang; Gang Zheng; Guang Ming Lu; Gui Fen Yang; Long Jiang Zhang (Molecular Neurobiology, 2018)

Effects of air pollution on hospital visits for pneumonia in children: a two-year analysis from China - Die Li; Jian-bing Wang; Zhen-yu Zhang; Peng Shen; Pei-wen Zheng; Ming-juan Jin; Huai-chu Lu; Hong-bo Lin; Kun Chen (Environmental Science and Pollution Research, 2018)

PKM2 knockdown influences SREBP activation and lipid synthesis in bovine mammary-gland epithelial MAC-T cells - Bing-Qian Su; Ying-Qian Han; Shuang-Shuang Fan; Sheng-Li Ming; Bo Wan; Wei-Fei Lu; Bei-Bei Chu; Guo-Yu Yang; Jiang Wang (Biotechnology Letters, 2018)

Surface wave attenuation based polarization attributes in time-frequency domain for multicomponent seismic data - Xuan-Lin Kong; Hui Chen; Zhi-Quan Hu; Jia-Xing Kang; Tian-Ji Xu; Lu-Ming Li (Applied Geophysics, 2018)

Gender-Related Hippocampal Proteomics Study from Young Rats After Chronic Unpredicted Mild Stress Exposure - Lin-Na Ning; Teng Zhang; Jiang Chu; Na Qu; Li Lin; Ying-Yan Fang; Yan Shi; Peng Zeng; Er-Li Cai; Xiao-Ming Wang; Qun Wang; You-Ming Lu; et al. (Molecular Neurobiology, 2018)

Effects of mutual intercropping on the cadmium accumulation in accumulator plants Stellaria media, Malachium aquaticum, and Galium aparine - Qiyu Lu; Jianhua Li; Fabo Chen; Ming’an Liao; Lijin Lin; Yi Tang; Dong Liang; Hui Xia; Yunsong Lai; Xun Wang; Cheng Chen; Wei Ren (Environmental Monitoring and Assessment, 2017)

Cloning and characterization of Agp1, the gene encoding the small subunit of ADP-glucose pyrophosphorylase from wheat and its relatives - Xiao-Wei Zhang; Qing Wang; Ling-Ling Zhang; Xiao-Juan Zhong; Qian-Tao Jiang; Jian Ma; Peng-Fei Qi; Wei Li; Guo-Yue Chen; Xiu-Jin Lan; Mei Deng; Zhen-Xiang Lu; et al. (Biologia, 2017)

Using P wave modulus to estimate the mechanical parameters of rock mass - Xiaoming Shen; Ming Chen; Wenbo Lu; Long Li (Bulletin of Engineering Geology and the Environment, 2017)

Cenozoic evolutionary history of Zelkova (Ulmaceae), evidenced from ITS, trnL-trnF, psbA-trnH, and rbcL - Ming-Li Zhang; Lu Wang; Yun Lei; Stewart C. Sanderson (Tree Genetics & Genomes, 2017)

Experimental Study on Longmaxi Shale Breaking Mechanism with Micro-PDC Bit - Teng Wang; Xiaohua Xiao; Haiyan Zhu; Jingying Zhao; Yuheng Li; Ming Lu (Rock Mechanics and Rock Engineering, 2017)

Study on the groundwater sustainable problem by numerical simulation in a multi-layered coastal aquifer system of Zhanjiang, China - Pengpeng Zhou; Ming Li; Yaodong Lu (Journal of Earth System Science, 2017)

Salt-response analysis in two rice cultivars at seedling stage - Yan Liu; Baoxiang Wang; Jian Li; Zhaoqiang Song; Baiguan Lu; Ming Chi; Bo Yang; Jinbo Liu; Ying-Wai Lam; Jiaxu Li; Dayong Xu (Acta Physiologiae Plantarum, 2017)

Expression of Iron Transporters and Pathological Hallmarks of Parkinson’s and Alzheimer’s Diseases in the Brain of Young, Adult, and Aged Rats - Li-Na Lu; Zhong-Ming Qian; Ka-Chun Wu; Wing-Ho Yung; Ya Ke (Molecular Neurobiology, 2017)

An amplitude suppression method based on the decibel criterion - Xuan-Lin Kong; Hui Chen; Jin-Long Wang; Zhi-quan Hu; Dan Xu; Lu-Ming Li (Applied Geophysics, 2017)

Algorithm to improve accuracy of energy expended in a room calorimeter - Haiying Quan; Wenrui Hao; Lu Li; Ming Sun; Kuan Zhang (Medical & Biological Engineering & Computing, 2017)

Emission characteristics of toxic pollutants from an updraft fixed bed gasifier for disposing rural domestic solid waste - Ming Lei; Jing Hai; Jiang Cheng; Li Gui; Jiawei Lu; Ming-Zhong Ren; Feng Zhu; Zong-Hui Yang (Environmental Science and Pollution Research, 2017)

Air pollution and hospital visits for acute upper and lower respiratory infections among children in Ningbo, China: A time-series analysis - Pei-wen Zheng; Jian-bing Wang; Zhen-yu Zhang; Peng Shen; Peng-fei Chai; Die Li; Ming-juan Jin; Meng-Ling Tang; Huai-chu Lu; Hong-bo Lin; Kun Chen (Environmental Science and Pollution Research, 2017)

Cloning and Stress-Induced Expression Analysis of Calmodulin in the Antarctic Alga Chlamydomonas sp. ICE-L - Ying-ying He; Yi-bin Wang; Zhou Zheng; Fang-ming Liu; Mei-ling An; Xiao-dong He; Chang-feng Qu; Lu-lu Li; Jin-lai Miao (Current Microbiology, 2017)

Response of linear and cyclic electron flux to moderate high temperature and high light stress in tomato - Tao Lu; Jie-wei Shi; Zhou-ping Sun; Ming-fang Qi; Yu-feng Liu; Tian-lai Li (Journal of Zhejiang University-SCIENCE B, 2017)

Effects of Carpal Tunnel Syndrome on Force Coordination and Muscle Coherence during Precision Pinch - Szu-Ching Lu; Kaihua Xiu; Ke Li; Tamara L. Marquardt; Peter J. Evans; Zong-Ming Li (Journal of Medical and Biological Engineering, 2017)

Trans-ethnic fine-mapping of genetic loci for body mass index in the diverse ancestral populations of the Population Architecture using Genomics and Epidemiology (PAGE) Study reveals evidence for multiple signals at established loci - Lindsay Fernández-Rhodes; Jian Gong; Jeffrey Haessler; Nora Franceschini; Mariaelisa Graff; Katherine K. Nishimura; Yujie Wang; Heather M. Highland; Sachiko Yoneyama; William S. Bush; Robert Goodloe; Marylyn D. Ritchie; et al. (Human Genetics, 2017)

Lower functional connectivity of default mode network in cognitively normal young adults with mutation of APP, presenilins and APOE ε4 - Yun Yan Su; Xiao Dong Zhang; U. Joseph Schoepf; Akos Varga-Szemes; Andrew Stubenrauch; Xue Liang; Li Juan Zheng; Gang Zheng; Xiang Kong; Qiang Xu; Shou Ju Wang; Rong Feng Qi; et al. (Brain Imaging and Behavior, 2017)

The Research on the Relationship of RAGE, LRP-1, and Aβ Accumulation in the Hippocampus, Prefrontal Lobe, and Amygdala of STZ-Induced Diabetic Rats - Lou-Yan Ma; Yu-Lang Fei; Xiao-Ye Wang; Song-Di Wu; Jun-Hui Du; Mei Zhu; Long Jin; Ming Li; Hai-Long Li; Jia-Jia Zhai; Lu-Peng Ji; Ran-Ran Ma; et al. (Journal of Molecular Neuroscience, 2017)

Altered Amygdala Resting-State Functional Connectivity in Maintenance Hemodialysis End-Stage Renal Disease Patients with Depressive Mood - Hui Juan Chen; Yun Fei Wang; Rongfeng Qi; U. Joseph Schoepf; Akos Varga-Szemes; B. Devon Ball; Zhe Zhang; Xiang Kong; Jiqiu Wen; Xue Li; Guang Ming Lu; Long Jiang Zhang (Molecular Neurobiology, 2017)

TRPV1 attenuates intracranial arteriole remodeling through inhibiting VSMC phenotypic modulation in hypertension - Ming-Jie Zhang; Yun Liu; Zi-Cheng Hu; Yi Zhou; Yan Pi; Lu Guo; Xu Wang; Xue Chen; Jing-Cheng Li; Li-Li Zhang (Histochemistry and Cell Biology, 2017)

Molecular and morphological identification of a human biting tick, Amblyomma testudinarium (Acari: Ixodidae), in Taiwan - Li-Lian Chao; Chun-Wei Lu; Ying-Fang Lin; Chien-Ming Shih (Experimental and Applied Acarology, 2017)

High genetic diversity and absence of phylogeographic structure in breeding populations of vulnerable Saundersilarus saundersi (Charadriiformes: Laridae) in Bohai Bay, China - Ya-Nan Zhang; Bo-Ye Liu; Lu Dong; Hong-Xing Jiang; Xuan Wang; Xue-Min Wang; Chang-Zhan Song; Xiu-Ming Li; Shu-Hong Li (Conservation Genetics, 2017)

Complete genomic sequence of an infectious pancreatic necrosis virus isolated from rainbow trout (Oncorhynchus mykiss) in China - Feng Ji; Jing-zhuang Zhao; Miao Liu; Tong-yan Lu; Hong-bai Liu; Jiasheng Yin; Li-Ming Xu (Virus Genes, 2017)

Implementation of the strain hardening model into buffer material in high level waste repository - Lu Chen; Lan Qiao; Ming Cui; Qingwen Li (Geosciences Journal, 2017)

Outbreak of severe pseudorabies virus infection in pig-offal-fed farmed mink in Liaoning Province, China - Hao Liu; Xin-Tong Li; Bo Hu; Xiao-Yu Deng; Lei Zhang; Shi-Zhen Lian; Hai-Ling Zhang; Shuang Lv; Xiang-Hong Xue; Rong-Guang Lu; Ning Shi; Ming-Hao Yan; et al. (Archives of Virology, 2017)

Mutations in IL36RN are associated with geographic tongue - Jianying Liang; Peichen Huang; Huaguo Li; Jia Zhang; Cheng Ni; Yirong Wang; Jinwen Shen; Chunxiao Li; Lu Kang; Jie Chen; Hui Zhang; Zhen Wang; et al. (Human Genetics, 2017)

Heterosis and combining ability of seven maize germplasm populations - Xiaocong Zhang; Hongjun Yong; Zhiqiang Zhou; Chaoshu Zhang; Ming Lu; Qi Sun; Lin Zhang; Mingshun Li; Degui Zhang; Jianfeng Weng; Zhuanfang Hao; Shihuang Zhang; et al. (Euphytica, 2017)

Two new sesquiterpenoids produced by halophilic Nocardiopsis chromatogenes YIM 90109 - Ming-Wei Sun; Xiao-Mei Zhang; Hui-Li Bi; Wen-Jun Li; Chun-Hua Lu (Natural Product Research, 2017)

A bifunctional type III polyketide synthase from raspberry (Rubus idaeus L.) with both chalcone synthase and benzalacetone synthase activity - Hui-Li Guo; Ya-Dong Yang; Ya-Di Ma; Wen-Bin Liu; Jing Feng; Zai-Qi Luo; He-Shu Lu; Chun-Mei Liu; Ming-Feng Yang; You-Nian Wang; Lan-Qing Ma (Journal of Plant Biochemistry and Biotechnology, 2017)

Geochemistry of fine-grained clastic rocks in the Mesoproterozoic Kawabulake Group: implications for provenance and the tectonic model of the Eastern Tianshan, Xinjiang, NW China - Deng-Feng Li; Hua-Yong Chen; Li Zhang; Philip Fralick; Pete Hollings; Mei Mi; Wan-Jian Lu; Jin-Sheng Han; Cheng-Ming Wang; Jing Fang (International Journal of Earth Sciences, 2017)

The angiotensin-I converting enzyme gene I/D variation contributes to end-stage renal disease risk in Chinese patients with type 2 diabetes receiving hemodialysis - Ming Lu; Jianzhong Zhang; Ming Li; Xiaoxu Ge; Xu Dai; Jiao Zhao; Mingzhou Fu; Tao Wang; Xiyao Fang; Can Li; Rong Zhang; Weijing Zhao; et al. (Molecular and Cellular Biochemistry, 2016)

Assessment of biostimulation and bioaugmentation for removing chlorinated volatile organic compounds from groundwater at a former manufacture plant - Shu Zhang; Zhen Hou; Xiao-ming Du; Dong-ming Li; Xiao-xia Lu (Biodegradation, 2016)

In Vivo Exposure of Kaempferol Is Driven by Phase II Metabolic Enzymes and Efflux Transporters - Liang Zheng; Lijun Zhu; Min Zhao; Jian Shi; Yuhuan Li; Jia Yu; Huangyu Jiang; Jinjun Wu; Yunli Tong; Yuting Liu; Ming Hu; Linlin Lu; et al. (The AAPS Journal, 2016)

Effects of Thermal Treatment on the Dynamic Mechanical Properties of Coal Measures Sandstone - Ming Li; Xianbiao Mao; Lili Cao; Hai Pu; Rongrong Mao; Aihong Lu (Rock Mechanics and Rock Engineering, 2016)

VRC01 antibody protects against vaginal and rectal transmission of human immunodeficiency virus 1 in hu-BLT mice - Ming Sun; Yue Li; Zhe Yuan; Wuxun Lu; Guobin Kang; Wenjin Fan; Qingsheng Li (Archives of Virology, 2016)

Genomic characterization of symbiotic mycoplasmas from the stomach of deep‐sea isopod bathynomus sp - Yong Wang; Jiao‐Mei Huang; Shao‐Lu Wang; Zhao‐Ming Gao; Ai‐Qun Zhang; Antoine Danchin; Li‐Sheng He (Environmental Microbiology, 2016)
Deep‐sea isopod scavengers such as Bathynomus sp. are able to live in nutrient‐poor environments, which is likely attributable to the presence of symbiotic microbes in their stomach. In this study we recovered two draft genomes of mycoplasmas, Bg1 and Bg2, from the metagenomes of the stomach contents and stomach sac of a Bathynomus sp. sample from the South China Sea (depth of 898 m). Phylogenetic trees revealed a considerable genetic distance to other mycoplasma species for Bg1 and Bg2. Compared with terrestrial symbiotic mycoplasmas, the Bg1 and Bg2 genomes were enriched with genes encoding phosphoenolpyruvate‐dependent phosphotransferase systems (PTSs) and sodium‐driven symporters responsible for the uptake of sugars, amino acids and other carbohydrates. The genome of mycoplasma Bg1 contained sialic acid lyase and transporter genes, potentially enabling the bacteria to attach to the stomach sac and obtain organic carbons from various cell walls. Both of the mycoplasma genomes contained multiple copies of genes related to proteolysis and oligosaccharide degradation, which may help the host survive in low‐nutrient conditions. The discovery of the different types of mycoplasma bacteria in the stomach of this deep‐sea isopod affords insights into symbiotic model of deep‐sea animals and genomic plasticity of mycoplasma bacteria.

Cerebral blood flow changes in hemodialysis and peritoneal dialysis patients: an arterial-spin labeling MR imaging - Xiao Lu Jiang; Ji Qiu Wen; Long Jiang Zhang; Gang Zheng; Xue Li; Zhe Zhang; Ya Liu; Li Juan Zheng; Long Wu; Hui Juan Chen; Xiang Kong; Song Luo; et al. (Metabolic Brain Disease, 2016)

Voriconazole combined with low-dose amphotericin B liposome for treatment of cryptococcal meningitis - Shan-Shan Li; Xin-Yue Tang; Sheng-Guo Zhang; Shun-Lan Ni; Nai-Bin Yang; Ming-Qin Lu (Infectious Diseases, 2016)

Salusin β Within the Nucleus Tractus Solitarii Suppresses Blood Pressure Via Inhibiting the Activities of Presympathetic Neurons in the Rostral Ventrolateral Medulla in Spontaneously Hypertensive Rats - Hong-Bao Li; Yan Lu; Jin-Jun Liu; Yu-Wang Miao; Tian-Zhen Zheng; Qing Su; Jie Qi; Hong Tan; Zu-Yi Yuan; Guo-Qing Zhu; Yu-Ming Kang (Cardiovascular Toxicology, 2016)

Calpain-Dependent ErbB4 Cleavage Is Involved in Brain Ischemia-Induced Neuronal Death - Ying-mei Lu; Yin-ping Gao; Rong-rong Tao; Mei-hua Liao; Ji-yun Huang; Gang Wu; Feng Han; Xiao-ming Li (Molecular Neurobiology, 2016)

Infralimbic Endothelin1 Is Critical for the Modulation of Anxiety-Like Behaviors - Lin-Lin Bi; Ming Chen; Lei Pei; Shu Shu; Hui-Juan Jin; Hong-Lin Yan; Na Wei; Shan Wang; Xin Yang; Huan-Huan Yan; Meng-meng Xu; Cheng-Ye Yao; et al. (Molecular Neurobiology, 2016)

Increased expression of long noncoding RNAs LOC100652951 and LOC100506036 in T cells from patients with rheumatoid arthritis facilitates the inflammatory responses - Ming-Chi Lu; Hui-Chun Yu; Chia-Li Yu; Hsien-Bin Huang; Malcolm Koo; Chien-Hsueh Tung; Ning-Sheng Lai (Immunologic Research, 2016)

Sodium Para-aminosalicylic Acid Protected Primary Cultured Basal Ganglia Neurons of Rat from Manganese-Induced Oxidative Impairment and Changes of Amino Acid Neurotransmitters - Shao-Jun Li; Yong Li; Jing-Wen Chen; Zong-Xiang Yuan; Yu-Huan Mo; Guo-Dong Lu; Yue-Ming Jiang; Chao-Yan Ou; Fang Wang; Xiao-Wei Huang; Yi-Ni Luo; Shi-Yan Ou; et al. (Biological Trace Element Research, 2016)

Mechanical Analysis of Static Stress Within Fault-Pillars Based on a Voussoir Beam Structure - Zhen-lei Li; Lin-ming Dou; Wu Cai; Gui-feng Wang; Yan-lu Ding; Yong Kong (Rock Mechanics and Rock Engineering, 2016)

Low temperature destruction of PCDD/Fs by catalysis coupled with activated carbon - Ming-feng Yu; Xiao-dong Li; Tong Chen; Sheng-yong Lu; Jian-hua Yan (Environmental Science and Pollution Research, 2016)

Recombinant expression, purification, and characterization of an acyl-CoA binding protein from Aspergillus oryzae - Qing Hao; Xiaoguang Liu; Guozhong Zhao; Lu Jiang; Ming Li; Bin Zeng (Biotechnology Letters, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Roadway Stagger Layout for Effective Control of Gob-Side Rock Bursts in the Longwall Mining of a Thick Coal Seam - Zhen-lei Li; Lin-ming Dou; Wu Cai; Gui-feng Wang; Yan-lu Ding; Yong Kong (Rock Mechanics and Rock Engineering, 2016)

Vascular endothelial growth factor-C protects heart from ischemia/reperfusion injury by inhibiting cardiomyocyte apoptosis - Xu-guang Chen; Yan-xia Lv; Dan Zhao; Lei Zhang; Fei Zheng; Jian-Ye Yang; Xiao-lin Li; Lu Wang; Lin-Yun Guo; Ya-mu Pan; Yu-wen Yan; Shi-You Chen; et al. (Molecular and Cellular Biochemistry, 2016)

Feasibility of diagnosing unstable plaque in patients with acute coronary syndrome using iMap-IVUS - Jian Liu; Zhao Wang; Wei-min Wang; Qi Li; Yu-liang Ma; Chuan-fen Liu; Ming-yu Lu; Hong Zhao (Journal of Zhejiang University-SCIENCE B, 2015)

Astragalus Polysaccharide Inhibits Autophagy and Apoptosis from Peroxide-Induced Injury in C2C12 Myoblasts - Yi Yin; Lu Lu; Dongtao Wang; Ying Shi; Ming Wang; Yanfeng Huang; Dexiu Chen; Cong Deng; Jiebin Chen; Peijia Lv; Yanjing Wang; Chengjie Li; et al. (Cell Biochemistry and Biophysics, 2015)

A CD44 specific peptide developed by phage display for targeting gastric cancer - Dan Zhang; Huan Jia; Yan Wang; Wei-Ming Li; Ying-Chun Hou; Shi-Wei Yin; Thomas D. Wang; Shui-Xiang He; Shao-Ying Lu (Biotechnology Letters, 2015)

The impact of hemodialysis on cognitive dysfunction in patients with end-stage renal disease: a resting-state functional MRI study - Hui Juan Chen; Rongfeng Qi; Xiang Kong; Jiqiu Wen; Xue Liang; Zhe Zhang; Xue Li; Guang Ming Lu; Long Jiang Zhang (Metabolic Brain Disease, 2015)

Loss of Egr-1 sensitizes pancreatic β-cells to palmitate-induced ER stress and apoptosis - Mun-Wai Cheong; Li-Hua Kuo; Yi-Ning Cheng; Pei-Jane Tsai; Li-Chun Ho; Haw-Chih Tai; Wen-Tai Chiu; Shun-Hua Chen; Pei-Jung Lu; Yan-Shen Shan; Lee-Ming Chuang; Yau-Sheng Tsai (Journal of Molecular Medicine, 2015)

The E23K and A190A variations of the KCNJ11 gene are associated with early-onset type 2 diabetes and blood pressure in the Chinese population - Langen Zhuang; Yu Zhao; Weijing Zhao; Ming Li; Ming Yu; Ming Lu; Rong Zhang; Xiaoxu Ge; Taishan Zheng; Can Li; Jun Yin; Jingyuan Yin; et al. (Molecular and Cellular Biochemistry, 2015)

Establishment and maintenance of a standardized glioma tissue bank: Huashan experience - Abudumijiti Aibaidula; Jun-feng Lu; Jin-song Wu; He-jian Zou; Hong Chen; Yu-qian Wang; Zhi-yong Qin; Yu Yao; Ye Gong; Xiao-ming Che; Ping Zhong; Shi-qi Li; et al. (Cell and Tissue Banking, 2015)

Triple Recycling Processes Impact Systemic and Local Bioavailability of Orally Administered Flavonoids - Peimin Dai; Lijun Zhu; Feifei Luo; Linlin Lu; Qiang Li; Liping Wang; Ying Wang; Xinchun Wang; Ming Hu; Zhongqiu Liu (The AAPS Journal, 2015)

Pitavastatin calcium improves endothelial function and delays the progress of atherosclerosis in patients with hypercholesterolemia - Jing Zhao; Hui-min Yan; Ya Li; Jia Wang; Lu Han; Zhi-hao Wang; Meng-xiong Tang; Wei Zhang; Yun Zhang; Ming Zhong (Journal of Zhejiang University-SCIENCE B, 2015)

The effects of land use and landscape position on labile organic carbon and carbon management index in red soil hilly region, southern China - Zhong-wu Li; Xiao-dong Nie; Xiao-lin Chen; Yin-mei Lu; Wei-guo Jiang; Guang-ming Zeng (Journal of Mountain Science, 2015)

Significantly Decreased and More Variable Expression of Major CYPs and UGTs in Liver Microsomes Prepared from HBV-Positive Human Hepatocellular Carcinoma and Matched Pericarcinomatous Tissues Determined Using an Isotope Label-free UPLC-MS/MS Method - Tongmeng Yan; Song Gao; Xiaojuan Peng; Jian Shi; Cong Xie; Qiang Li; Linlin Lu; Ying Wang; Fuyuan Zhou; Zhongqiu Liu; Ming Hu (Pharmaceutical Research, 2015)

Interactions between household air pollution and GWAS-identified lung cancer susceptibility markers in the Female Lung Cancer Consortium in Asia (FLCCA) - H. Dean Hosgood; Minsun Song; Chao Agnes Hsiung; Zhihua Yin; Xiao-Ou Shu; Zhaoming Wang; Nilanjan Chatterjee; Wei Zheng; Neil Caporaso; Laurie Burdette; Meredith Yeager; Sonja I. Berndt; et al. (Human Genetics, 2015)

Comparison of chemical, electrical, and combined activation methods for in vitro matured porcine oocytes - Shuai Liu; Kuiqing Cui; Hong Li Li; Jun Ming Sun; Xing Rong Lu; Kai Yuan Shen; Qing You Liu; De Shun Shi (In Vitro Cellular & Developmental Biology - Animal, 2015)

Distribution of PCDD/Fs in the fly ash and atmospheric air of two typical hazardous waste incinerators in eastern China - Tong Chen; Ming-xiu Zhan; Xiao-qing Lin; Jian-ying Fu; Sheng-yong Lu; Xiao-dong Li (Environmental Science and Pollution Research, 2015)

MiR-218-targeting-Bmi-1 mediates the suppressive effect of 1,6,7-trihydroxyxanthone on liver cancer cells - Wei-Ming Fu; Li-Peng Tang; Xiao Zhu; Ying-Fei Lu; Yan-Ling Zhang; Wayne Yuk-Wai LEE; Hua Wang; Yang Yu; Wei-Cheng Liang; Chun-Hay Ko; Hong-Xi Xu; Hsiang-Fu Kung; et al. (Apoptosis, 2015)

Lipopolysaccharides Upregulate Hepcidin in Neuron via Microglia and the IL-6/STAT3 Signaling Pathway - Zhong-Ming Qian; Xuan He; Tuo Liang; Ka-Chun Wu; Yik-Chun Yan; Li-Na Lu; Guang Yang; Qian Qian Luo; Wing-Ho Yung; Ya Ke (Molecular Neurobiology, 2014)

KIM-1 and NGAL as biomarkers of nephrotoxicity induced by gentamicin in rats - Qi-hui Luo; Meng-lu Chen; Feng-jiao Sun; Zheng-li Chen; Ming-yang Li; Wen Zeng; Li Gong; An-chun Cheng; Xi Peng; Jing Fang; Li Tang; Yi Geng (Molecular and Cellular Biochemistry, 2014)

Epitope mapping of the infectious hematopoietic necrosis virus glycoprotein by flow cytometry - Li-Ming Xu; Miao Liu; Jing-Zhuang Zhao; Yong-Sheng cao; Jia-Sheng Yin; Hong-Bai Liu; Tongyan Lu (Biotechnology Letters, 2014)

Prediction of Selenoprotein T Structure and Its Response to Selenium Deficiency in Chicken Immune Organs - Lu You; Ci Liu; Zi-jiang Yang; Ming Li; Shu Li (Biological Trace Element Research, 2014)

A pre-breeding screening program for transgenic boars based on fluorescence in situ hybridization assay - Gerelchimeg Bou; Mingju Sun; Ming Lv; Jiang Zhu; Hui Li; Juan Wang; Lu Li; Zhongfeng Liu; Zhong Zheng; Wenteng He; Qingran Kong; Zhonghua Liu (Transgenic Research, 2014)

Differential proteome analysis of mature and germinated seeds of Magnolia sieboldii K. Koch - Xiao-lin Zhang; Guang-lin Liu; Tian-lai Li; Ming-fang Qi; Mei Mei; Xiu-jun Lu (Trees, 2014)

Diurnal and seasonal dynamics of soil respiration at temperate Leymus chinensis meadow steppes in western Songnen Plain, China - Ming Wang; Xingtu Liu; Jitao Zhang; Xiujun Li; Guodong Wang; Xiaoyu Li; Xinrui Lu (Chinese Geographical Science, 2014)

Difference in organic carbon contents and distributions in particle-size fractions between soil and sediment on the Southern Loess Plateau, China - Guang-lu Li; Xiao-ming Pang (Journal of Mountain Science, 2014)

Infection of Prions and Treatment of PrP106–126 Alter the Endogenous Status of Protein 14-3-3 and Trigger the Mitochondrial Apoptosis Possibly via Activating Bax Pathway - Qi Shi; Qin-Qin Song; Peng Sun; Jin Zhang; Juan Song; Li-Na Chen; Kang Xiao; Shao-Bin Wang; Ya-Zhou Zhang; Gong-Qi Li; Lin-Jun Sheng; Bao-Dong Wang; et al. (Molecular Neurobiology, 2014)

The metabolism of 8-heptadecene in Pyropia (Bangiaceae, Rhodophyta) - Min Zhang; Rui-Xia Li; Chuan-Ming Hu; Li-En Yang; Jun Tang; Qin-Qin Lu; Tao Zhang; Zong-Gen Shen; Song-Dong Shen; Pu Xu; Jian-Yi Zhu (Journal of Applied Phycology, 2014)

Numerical modeling of the effects of beach slope on water-table fluctuation in the unconfined aquifer of Donghai Island, China - Pengpeng Zhou; Guomin Li; Yaodong Lu; Ming Li (Hydrogeology Journal, 2014)

Cloning and characterization of squalene synthase gene from Poria cocos and its up-regulation by methyl jasmonate - Jian-Rong Wang; Jun-Fang Lin; Li-Qiong Guo; Lin-Feng You; Xian-Lu Zeng; Jia-Ming Wen (World Journal of Microbiology and Biotechnology, 2014)

Activation of mammalian target of rapamycin contributes to pain nociception induced in rats by BmK I, a sodium channel-specific modulator - Feng Jiang; Li-Ming Hua; Yun-Lu Jiao; Pin Ye; Jin Fu; Zhi-Jun Cheng; Gang Ding; Yong-Hua Ji (Neuroscience Bulletin, 2014)

The Leu72Met polymorphism of the GHRL gene prevents the development of diabetic nephropathy in Chinese patients with type 2 diabetes mellitus - Langen Zhuang; Ming Li; Changhua Yu; Can Li; Mingming Zhao; Ming Lu; Taishan Zheng; Rong Zhang; Weijing Zhao; Yuqian Bao; Kunsan Xiang; Weiping Jia; et al. (Molecular and Cellular Biochemistry, 2014)

Rice black-streaked dwarf virus genome segment S5 is a bicistronic mRNA in infected plants - Jian Yang; Heng-Mu Zhang; Lu Ying; Jing Li; Ming-Fang Lv; Li Xie; Pei-Pei Li; Xiao-Ya Liu; Dai Liang-Ying; Jian-Ping Chen (Archives of Virology, 2014)

A new indole alkaloidal glucoside from the aerial parts of Clematis terniflora DC. - Wen-Ting Li; Bing-Xian Yang; Wei Zhu; Ming-Hua Gong; Xiang-Dong Xu; Xiang-Hong Lu; Lian-Li Sun; Jing-Kui Tian; Lin Zhang (Natural Product Research, 2013)

Genetic analysis and detection of the gene MlLX99 on chromosome 2BL conferring resistance to powdery mildew in the wheat cultivar Liangxing 99 - Zihui Zhao; Huigai Sun; Wei Song; Ming Lu; Jiang Huang; Longfei Wu; Xiaoming Wang; Hongjie Li (Theoretical and Applied Genetics, 2013)

A novel peroxinectin involved in antiviral and antibacterial immunity of mud crab, Scylla paramamosain - Zhi-Qiang Du; Qian Ren; An-Ming Huang; Wen-Hong Fang; Jun-Fang Zhou; Lu-Jiao Gao; Xin-Cang Li (Molecular Biology Reports, 2013)

Peripheral Metabotropic Glutamate Receptor Subtype 5 Contributes to Inflammation-Induced Hypersensitivity of the Rat Temporomandibular Joint - Bo Li; Li Lu; Xuexin Tan; Ming Zhong; Yan Guo; Xin Yi (Journal of Molecular Neuroscience, 2013)

Proteomic analysis of apoptotic and oncotic pancreatic acinar AR42J cells treated with caerulein - Jiangtao Chu; Hongliang Ji; Ming Lu; Zhituo Li; Xin Qiao; Bei Sun; Weihui Zhang; Dongbo Xue (Molecular and Cellular Biochemistry, 2013)

Changes in extracellular polysaccharide content and morphology of Microcystis aeruginosa at different specific growth rates - Ming Li; Wei Zhu; Li Gao; Lin Lu (Journal of Applied Phycology, 2013)

Microparameter Prediction for a Triaxial Compression PFC3D Model of Rock Using Full Factorial Designs and Artificial Neural Networks - Miao-jun Sun; Hui-ming Tang; Xin-li Hu; Yun-feng Ge; Sha Lu (Geotechnical and Geological Engineering, 2013)

Partial or complete substitution of fish meal with soybean meal and cottonseed meal in Chinese mitten crab Eriocheir sinensis diets - Hai-Bo Jiang; Li-Qiao Chen; Jian-Guang Qin; Lu-Jiao Gao; Er-Chao Li; Na Yu; Sheng-Ming Sun; Xue-Qin Jiang (Aquaculture International, 2013)

Catalog of Erycina pusilla miRNA and categorization of reproductive phase-related miRNAs and their target gene families - Choun-Sea Lin; Jeremy J. W. Chen; Yao-Ting Huang; Chen-Tran Hsu; Hsiang-Chia Lu; Ming-Lun Chou; Li-Chi Chen; Chia-I Ou; Der-Chih Liao; Ysuan-Yu Yeh; Song-Bing Chang; Su-Chen Shen; et al. (Plant Molecular Biology, 2013)

Arbuscular mycorrhizal symbiosis and active ingredients of medicinal plants: current research status and prospectives - Yan Zeng; Lan-Ping Guo; Bao-Dong Chen; Zhi-Peng Hao; Ji-Yong Wang; Lu-Qi Huang; Guang Yang; Xiu-Ming Cui; Li Yang; Zhao-Xiang Wu; Mei-Lan Chen; Yan Zhang (Mycorrhiza, 2013)

Feeding by Whiteflies Suppresses Downstream Jasmonic Acid Signaling by Eliciting Salicylic Acid Signaling - Peng-Jun Zhang; Wei-Di Li; Fang Huang; Jin-Ming Zhang; Fang-Cheng Xu; Yao-Bin Lu (Journal of Chemical Ecology, 2013)

Halalkalicoccus paucihalophilus sp. nov., a halophilic archaeon from Lop Nur region in Xinjiang, northwest of China - Bing-Bing Liu; Shu-Kun Tang; Yong-Guang Zhang; Xin-Hua Lu; Li Li; Juan Cheng; Yuan-Ming Zhang; Li-Li Zhang; Wen-Jun Li (Antonie van Leeuwenhoek, 2013)

The enhancement of biofilm formation in Group B streptococcal isolates at vaginal pH - Yueh-Ren Ho; Chien-Ming Li; Chen-Hsiang Yu; Yuh-Jyh Lin; Ching-Ming Wu; I-Chen Harn; Ming-Jer Tang; Yi-Ting Chen; Fang-Chi Shen; Chien-Yi Lu; Tai-Chun Tsai; Jiunn-Jong Wu (Medical Microbiology and Immunology, 2013)

Enhancing production of a 24-membered ring macrolide compound by a marine bacterium using response surface methodology - Hua Chen; Mian-bin Wu; Zheng-jie Chen; Ming-lu Wang; Jian-ping Lin; Li-rong Yang (Journal of Zhejiang University-SCIENCE B, 2013)

Spatiotemporal dynamics of high-K+-induced epileptiform discharges in hippocampal slice and the effects of valproate - Jian-Sheng Liu; Jing-Bo Li; Xin-Wei Gong; Hai-Qing Gong; Pu-Ming Zhang; Pei-Ji Liang; Qin-Chi Lu (Neuroscience Bulletin, 2013)

HP-β-CD-PLGA nanoparticles improve the penetration and bioavailability of puerarin and enhance the therapeutic effects on brain ischemia–reperfusion injury in rats - Hai-quan Tao; Qingfeng Meng; Ming-hui Li; Hui Yu; Mei-fang Liu; Dan Du; Shou-li Sun; Hai-cheng Yang; Yan-ming Wang; Wei Ye; Li-zhuang Yang; Da-ling Zhu; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2013)

Effect of Long-Term Vinasse Application on Physico-chemical Properties of Sugarcane Field Soils - Ze-Pu Jiang; Yang-Rui Li; Guang-Po Wei; Qing Liao; Tian-Ming Su; Yan-Cheng Meng; Hai-Ying Zhang; Chang-Yan Lu (Sugar Tech, 2012)

ATP-binding cassette transporter A1 R219K polymorphism and coronary artery disease in Chinese population: a meta-analysis of 5,388 participants - Yan-yan Li; Hui Zhang; Xiao-yi Qin; Xin-zheng Lu; Bing Yang; Ming-long Chen (Molecular Biology Reports, 2012)

Orally Bioavailable Tubulin Antagonists for Paclitaxel-Refractory Cancer - Chien-Ming Li; Yan Lu; Jianjun Chen; Terrence A. Costello; Ramesh Narayanan; Mara N. Dalton; Linda M. Snyder; Sunjoo Ahn; Wei Li; Duane D. Miller; James T. Dalton (Pharmaceutical Research, 2012)

Novel Tubulin Polymerization Inhibitors Overcome Multidrug Resistance and Reduce Melanoma Lung Metastasis - Zhao Wang; Jianjun Chen; Jin Wang; Sunjoo Ahn; Chien-Ming Li; Yan Lu; Vivian S. Loveless; James T. Dalton; Duane D. Miller; Wei Li (Pharmaceutical Research, 2012)

VEGF upregulates VEGF receptor-2 on human outer root sheath cells and stimulates proliferation through ERK pathway - Wei Li; Zhong-Fa Lu; Xiao-Yong Man; Chun-Ming Li; Jiong Zhou; Jia-Qi Chen; Xiao-Hong Yang; Xian-Jie Wu; Sui-Qing Cai; Min Zheng (Molecular Biology Reports, 2012)

Metabolomic study of serum from rabbits with acute acalculous cholecystitis - Zhituo Li; Huaishu Shen; Yingmei Zhang; Ming Lu; Xin Qiao; Xianzhi Meng; Bei Sun; Dongbo Xue; Weihui Zhang (Inflammation Research, 2012)

Involvement of p38MAPK/NF-κB Signaling Pathways in Osteoblasts Differentiation in Response to Mechanical Stretch - Liang Wang; Jian-yu Li; Xi-zheng Zhang; Lu Liu; Zong-ming Wan; Rui-xin Li; Yong Guo (Annals of Biomedical Engineering, 2012)

Susceptibilities to Amphotericin B, Fluconazole and Voriconazole of Trichosporon Clinical Isolates - Moan Shane Tsai; Yun Liang Yang; An Huei Wang; Lih Shinn Wang; Daniel C. T. Lu; Ci Hong Liou; Li Yun Hsieh; Chi Jung Wu; Ming Fang Cheng; Zhi Yuan Shi; Hsiu Jung Lo (Mycopathologia, 2012)

Migration of natural estrogens around a concentrated dairy-feeding operation - Yan-xia Li; Wei Han; Ming Yang; Cheng-hong Feng; Xiao-fei Lu; Feng-song Zhang (Environmental Monitoring and Assessment, 2012)

Production of monoclonal antibody and application in indirect competitive ELISA for detecting okadaic acid and dinophytoxin-1 in seafood - Shi-Ying Lu; Yu Zhou; Yan-Song Li; Chao Lin; Xian-Mei Meng; Dong-Ming Yan; Zhao-Hui Li; Shi-Yu Yu; Zeng-Shan Liu; Hong-Lin Ren (Environmental Science and Pollution Research, 2012)

Genetic variant in TP63 on locus 3q28 is associated with risk of lung adenocarcinoma among never-smoking females in Asia - H. Dean Hosgood; Wen-Chang Wang; Yun-Chul Hong; Jiu-Cun Wang; Kexin Chen; I-Shou Chang; Chien-Jen Chen; Daru Lu; Zhihua Yin; Chen Wu; Wei Zheng; Biyun Qian; et al. (Human Genetics, 2012)

Effects of 1,1,1-trichloroethane on enzymatic activity and bacterial community in anaerobic microcosm form sequencing batch reactors - Hui Li; Wei Zhang; Lu Li; Yong-Di Liu; Kuang-Fei Lin; Shu-Guang Lu; Bo-Zhong Mu; Xiao-Ming Du; Qiang Lu; Qian Zhang; Ting-Ting Shen; Bing-Zhi Li; et al. (Ecotoxicology, 2012)

Prenatal expression of purinergic receptor P2X3 in human dorsal root ganglion - Aihua Pan; Haiping Wu; Ming Li; Dahua Lu; Xu He; Xinan Yi; Xiao-Xin Yan; Zhiyuan Li (Purinergic Signalling, 2012)

Integrated Benefit Evaluation of Pedestrian Bridge - Lu Li; Ming Cai; Yonghong Liu (Environmental Modeling & Assessment, 2012)

The Group III Two-Component Histidine Kinase AlHK1 is Involved in Fungicides Resistance, Osmosensitivity, Spore Production and Impacts Negatively Pathogenicity in Alternaria longipes - Yi Yong Luo; Jin Kui Yang; Ming Liang Zhu; Chen Jian Liu; Hai Yan Li; Ze Bao Lu; Wen Zheng Pan; Zhong Hua Zhang; Wei Bi; Ke Qin Zhang (Current Microbiology, 2012)

Polymorphic variations in manganese superoxide dismutase (MnSOD), glutathione peroxidase-1 (GPX1), and catalase (CAT) contribute to elevated plasma triglyceride levels in Chinese patients with type 2 diabetes or diabetic cardiovascular disease - Hong Chen; Ming Yu; Ming Li; Ruie Zhao; Qihan Zhu; Wenrui Zhou; Ming Lu; Yufeng Lu; Taishan Zheng; Jiamei Jiang; Weijing Zhao; Kunsan Xiang; et al. (Molecular and Cellular Biochemistry, 2012)

Polymorphisms of the bovine luteinizing hormone/choriogonadotropin receptor (LHCGR) gene and its association with superovulation traits - Wu-Cai Yang; Ke-Qiong Tang; Shu-Jing Li; Lu-Ming Chao; Li-Guo Yang (Molecular Biology Reports, 2012)

Clozapine Protects Dopaminergic Neurons from Inflammation-Induced Damage by Inhibiting Microglial Overactivation - Xiaoming Hu; Hui Zhou; Dan Zhang; Sufen Yang; Li Qian; Hung-Ming Wu; Po-See Chen; Belinda Wilson; Hui-Ming Gao; Ru-band Lu; Jau-Shyong Hong (Journal of Neuroimmune Pharmacology, 2012)

Advances in study of ginsenoside biosynthesis pathway in Panax ginseng C. A. Meyer - Juan Wang; Wen-Yuan Gao; Jian Zhang; Bei-Mei Zuo; Li-Ming Zhang; Lu-Qi Huang (Acta Physiologiae Plantarum, 2012)

The calcium-sensing receptor promotes adipocyte differentiation and adipogenesis through PPARγ pathway - Yong-Han He; Ying He; Xi-Lu Liao; Yu-Cun Niu; Guan Wang; Chen Zhao; Liang Wang; Ming-Jie Tian; Ying Li; Chang-Hao Sun (Molecular and Cellular Biochemistry, 2012)

Production of ginsenoside and polysaccharide by two-stage cultivation of Panax quinquefolium L. cells - Juan Wang; Wen-Yuan Gao; Jian Zhang; Bei-Mei Zuo; Li-Ming Zhang; Lu-Qi Huang (In Vitro Cellular & Developmental Biology - Plant, 2012)

Type 17 T-helper cells might be a promising therapeutic target for osteoporosis - Feng-Lai Yuan; Xia Li; Wei-Guo Lu; Yi-Qing Zhao; Cheng-Wan Li; Jian-Ping Li; Jun-Ming Sun; Rui-Sheng Xu (Molecular Biology Reports, 2012)

Different sperm sources and parameters can influence intracytoplasmic sperm injection outcomes before embryo implantation - Yue-hong Lu; Hui-juan Gao; Bai-jia Li; Ying-ming Zheng; Ying-hui Ye; Yu-li Qian; Chen-ming Xu; He-feng Huang; Fan Jin (Journal of Zhejiang University-SCIENCE B, 2012)

Efficient expression of an alkaline pectate lyase gene from Bacillus subtilis and the characterization of the recombinant protein - Yihan Liu; Guanqun Chen; Jianling Wang; Yujie Hao; Ming Li; Yu Li; Bo Hu; Fuping Lu (Biotechnology Letters, 2012)

Physiological significance of P2X receptor-mediated vasoconstriction in five different types of arteries in rats - Lu Li; Zhen-Hua Jia; Chao Chen; Cong Wei; Jian-Ke Han; Yi-Ling Wu; Lei-Ming Ren (Purinergic Signalling, 2011)

Single amino acid residue changes in subsite −1 of levansucrase from Zymomonas mobilis 10232 strongly influence the enzyme activities and products - Shuying Li; Yongliang Yan; Zhengfu Zhou; Haiying Yu; Yuhua Zhan; Wei Zhang; Ming Chen; Wei Lu; Shuzhen Ping; Min Lin (Molecular Biology Reports, 2011)

Molecular epidemiology of Echovirus 30 in Taiwan, 1988–2008 - Guan-Ming Ke; Kuei-Hsiang Lin; Po-Liang Lu; Yi-Chin Tung; Chu-Feng Wang; Liang-Yin Ke; Min-Sheng Lee; Pei-Chin Lin; Hui-Ju Su; Yi-Ying Lin; Tzu-Ping Huang; Jen-Ren Wang; et al. (Virus Genes, 2011)

Comparison of Non-covalent Interactions Between a Series of N-Phosphoryl Dipeptide or Methyl Esters and Protein by Electrospray Ionization Mass Spectrometry - Li-ming Qiang; Ming-xiu Lü; Xu-ru Dong; Shu-xia Cao; Kui Lu; Yu-fen Zhao (International Journal of Peptide Research and Therapeutics, 2011)

Polymorphism of prion protein gene in sheep of Inner Mongolian, China - Cai-Xia Han; Hong-Xiang Liu; Yi-Xin Lu; Ming-Xin Song; De-Ming Zhao; Xiang-Mei Zhou; Li-Feng Yang; Xiao-Yun Li (Virus Genes, 2011)

A web-based platform for rice microarray annotation and data analysis - DiJun Chen; Fan Zhang; ChunHui Yuan; Jing Lu; Xia Li; Ming Chen (Science China Life Sciences, 2010)

Flavonoid Production Is Effectively Regulated by RNAi Interference of Two Flavone Synthase Genes from Glycine max - Yi Na Jiang; Biao Wang; Hui Li; Lu Ming Yao; Tian Long Wu (Journal of Plant Biology, 2010)

Recurrent Cerebellar Hemorrhage: Case Report and Review of the Literature - Yung-Tsan Wu; Ming-Fu Hsieh; Heng-Yi Chu; Shao-Chi Lu; Shin-Tsu Chang; Tsung-Ying Li (The Cerebellum, 2010)

Can the soil seed bank contribute to revegetation of the drawdown zone in the Three Gorges Reservoir Region? - Zhi-Jun Lu; Lian-Fa Li; Ming-Xi Jiang; Han-Dong Huang; Da-Chuan Bao (Plant Ecology, 2010)

Spontaneous Rhythmic Inward Currents Recorded in Interstitial Cells of Rabbit Portal Vein - Xu Huang; Dan Zhao; Zuo-Yu Wang; Ming-Liang Zhang; Zhi-Qiang Yan; Yan-Fei Han; Hong-Li Lu; Wen-Xie Xu; Zong-Lai Jiang (Cell Biochemistry and Biophysics, 2010)

Co-culture with cardiomyocytes enhanced the myogenic conversion of mesenchymal stromal cells in a dose-dependent manner - Xiao-qing He; Min-sheng Chen; Shu-Hong Li; Shi-ming Liu; Yun Zhong; Heather Y. McDonald Kinkaid; Wei-Yang Lu; Richard D. Weisel; Ren-Ke Li (Molecular and Cellular Biochemistry, 2010)

Genetic analysis of strains of Japanese Encephalitis Virus isolated from swine in central China - Jian-Ming Fan; Jun Luo; Lu Chen; Man Teng; Dan Bu; Fang-Yu Wang; Li Wang; Chuan-Qing Wang; Gai-Ping Zhang (Virus Genes, 2010)

Isolation of a new monoterpenic ester from the leaves of Michelia compressa (Maxim.) Sargent var. formosana Kanehira (Magnoliaceae) - Ming-Jen Cheng; Wen-Li Lo; Jin-Cherng Huang; Yu-Ting Yeh; Zi-Ling Hong; Yu-Cheng Lu; Ming-Sung Chang; Chung-Yi Chen (Natural Product Research, 2010)

Secular trend of genome types of respiratory adenovirus type 3 during 1983–2005: a study from Taiwan - Yung-Cheng Lin; Kuei-Hsiang Lin; Guan-Ming Ke; Min-Sheng Lee; Pei-Chin Lin; Hsin-Fu Liu; Li-Ching Hsu; Po-Liang Lu (Archives of Virology, 2010)

Profiling Gene Expression During Gland Morphogenesis of a Glanded and a Glandless Upland Cotton - Ying-Fan Cai; Min Chen; Quan Sun; Yong-Fang Xie; Sheng-Wei Li; Ming-Feng Jiang; Jian-Chuan Mo; You-Lu Yuan; Yu-Zhen Shi; Huai-Zhong Jiang; Zheng Pan; Yun-Ling Gao; et al. (Journal of Plant Biology, 2009)

Molecular Cloning and Expression of cDNA Encoding the Cysteine Proteinase Inhibitor from Upland Cotton - Ming-feng Jiang; Sheng-wei Li; Min Chen; Ying-fan Cai; Yong-fang Xie; Biao Li; Quan Sun; Huai-zhong Jiang; Zheng Pan; Yun-ling Gao; You-Lu Yuan; Yu-zheng Shi (Journal of Plant Biology, 2009)

Environmental estrogenic effects and gonadal development in wild goldfish (Carassius auratus) - Chun-Ri Li; Sang-Hoon Lee; So-Sun Kim; Andre Kim; Keun Woo Lee; Ming Lu; Hee-Eun Kim; Im-Jung Kwak; Yun-Ju Lee; Dong-Kyoo Kim; Jung-Sick Lee; Shin-Won Kang; et al. (Environmental Monitoring and Assessment, 2009)

Expression and purification of bioactive high-purity human midkine in Escherichia coli - Zhong-hui Zhang; Li-juan Du; Di Xiang; Shun-ying Zhu; Ming-yuan Wu; Hui-li Lu; Yan Yu; Wei Han (Journal of Zhejiang University-SCIENCE B, 2009)

Genes Involved in the Benzoate Catabolic Pathway in Acinetobacter calcoaceticus PHEA-2 - Yuhua Zhan; Haiying Yu; Yongliang Yan; Ming Chen; Wei Lu; Shuying Li; Zixin Peng; Wei Zhang; Shuzhen Ping; Jin Wang; Min Lin (Current Microbiology, 2008)

Heregulin-β promotes matrix metalloproteinase-7 expression via HER2-mediated AP-1 activation in MCF-7 cells - Guogang Yuan; Lu Qian; Lun Song; Ming Shi; Dan Li; Ming Yu; Meiru Hu; Beifen Shen; Ning Guo (Molecular and Cellular Biochemistry, 2008)

A study of NO trafficking from dinitrosyl–iron complexes to the recombinant E. coli transcriptional factor SoxR - Feng-Chun Lo; Chang-Li Chen; Chien-Ming Lee; Ming-Che Tsai; Tsai-Te Lu; Wen-Feng Liaw; Steve S.-F. Yu (JBIC Journal of Biological Inorganic Chemistry, 2008)

A single residue mutation of 5-enoylpyruvylshikimate-3-phosphate synthase in Pseudomonas stutzeri enhances resistance to the herbicide glyphosate - Aimin Liang; Jiying Sha; Wei Lu; Ming Chen; Liang Li; Dan Jin; Yongliang Yan; Jin Wang; Shuzhen Ping; Wei Zhang; Yiding Wang; Min Lin (Biotechnology Letters, 2008)

An ethanol-tolerant recombinant Escherichia coli expressing Zymomonas mobilis pdc and adhB genes for enhanced ethanol production from xylose - Zhanchao Wang; Ming Chen; Yuquan Xu; Shuying Li; Wei Lu; Shuzhen Ping; Wei Zhang; Min Lin (Biotechnology Letters, 2008)

Isolation and molecular characterization of the Triticum aestivum L. ethylene-responsive factor 1 (TaERF1) that increases multiple stress tolerance - Zhao-Shi Xu; Lan-Qin Xia; Ming Chen; Xian-Guo Cheng; Rui-Yue Zhang; Lian-Cheng Li; Yun-Xiang Zhao; Yan Lu; Zhi-Yong Ni; Li Liu; Zhi-Gang Qiu; You-Zhi Ma (Plant Molecular Biology, 2007)

A rice phenomics study—phenotype scoring and seed propagation of a T-DNA insertion-induced rice mutant population - Chyr-Guan Chern; Ming-Jen Fan; Su-May Yu; Ai-Ling Hour; Po-Chang Lu; Yao-Cheng Lin; Fu-Jin Wei; Sheng-Chung Huang; Shu Chen; Ming-Hsing Lai; Ching-Shan Tseng; Hsing-Mu Yen; et al. (Plant Molecular Biology, 2007)

Identification of a New Gene Encoding EPSPS with High Glyphosate Resistance from the Metagenomic Library - Dan Jin; Wei Lu; Shuzhen Ping; Wei Zhang; Jian Chen; Baoqing Dun; Ruiqiang Ma; Zhonglin Zhao; Jiying Sha; Liang Li; Zhirong Yang; Ming Chen; et al. (Current Microbiology, 2007)

Effects of rosiglitazone on native low-density-lipoprotein-induced respiratory burst in circulating monocytes and on the leukocyte–endothelial interaction in cholesterol-fed rats - Long Sheng Lu; Li Man Hung; Chang Hui Liao; Chau Chung Wu; Ming Jai Su (Naunyn-Schmiedeberg's Archives of Pharmacology, 2007)

A rice gene activation/knockout mutant resource for high throughput functional genomics - Yue-Ie Hsing; Chyr-Guan Chern; Ming-Jen Fan; Po-Chang Lu; Ku-Ting Chen; Shuen-Fang Lo; Peng-Kai Sun; Shin-Lon Ho; Kuo-Wei Lee; Yi-Chieh Wang; Wen-Lii Huang; Swee-Suak Ko; et al. (Plant Molecular Biology, 2007)

BRD2 is one of BRD7-interacting proteins and its over-expression could initiate apoptosis - Ming Zhou; Xiao-Jie Xu; Hou-De Zhou; Hua-Ying Liu; Jia-Jin He; Xiao-Ling Li; Cong Peng; Wei Xiong; Song-Qing Fan; Jian-Hong Lu; Jue Ouyang; Shou-Rong Shen; et al. (Molecular and Cellular Biochemistry, 2006)

Ala45Thr variation in neuroD1 gene is associated with early-onset type 2 diabetes with or without diabetic pedigree in Chinese - Limei Liu; Weiping Jia; Taishan Zheng; Ming Li; Huijuan Lu; Kunsan Xiang (Molecular and Cellular Biochemistry, 2006)

Cardiomyoblast apoptosis induced by insulin-like growth factor (IGF)-I resistance is IGF-II dependent and synergistically enhanced by angiotensin II - Wei-Wen Kuo; Chung-Jung Liu; Li-Ming Chen; Chieh-Hsi Wu; Chun-Hsien Chu; Jer-Yuh Liu; Min-Chi Lu; James A. Lin; Shin-Da Lee; Chih-Yang Huang (Apoptosis, 2006)

Functional analysis of helicase and three tandem HRDC domains of RecQ in Deinococcus radiodurans - Li-fen Huang; Xiao-ting Hua; Hui-ming LU; Guan-jun Gao; Bing Tian; Bing-hui Shen; Yue-jin Hua (Journal of Zhejiang University-SCIENCE B, 2006)

In situ and in vitro colonization of Cathaya argyrophylla (Pinaceae) by ectomycorrhizal fungi - Lu-Min Vaario; Shu-Tang Xing; Zong-Qiang Xie; Zhi-Ming Lun; Xue Sun; Yu Hua Li (Mycorrhiza, 2006)

Investigation of iodine concentration in salt, water and soil along the coast of Zhejiang, China - Ying-li Lu; Ning-jian Wang; Lan Zhu; Guo-xing Wang; Hui Wu; Lin Kuang; Wen-ming Zhu (Journal of Zhejiang University-SCIENCE B, 2005)

Paraphyly of Cyrtomium (Dryopteridaceae): evidence from rbcL and trnL-F sequence data - Jin-Mei Lu; De-Zhu Li; Lian-Ming Gao; Xiao Cheng; Ding Wu (Journal of Plant Research, 2005)

U–Pb and Hf-isotope analysis of zircons in mafic xenoliths from Fuxian kimberlites: evolution of the lower crust beneath the North China craton - Jianping Zheng; W. L. Griffin; Suzanne Y. O’Reilly; Fengxiang Lu; Chunmei Yu; Ming Zhang; Huimin Li (Contributions to Mineralogy and Petrology, 2004)

Study on beijing’s emerging mobile communication industrial cluster and its policy implications - Tie-shan Sun; Guo-ping Li; Ming-hua Lu (Chinese Geographical Science, 2003)

Crystal structure studies on rubrerythrin: enzymatic activity in relation to the zinc movement - Mei Li; Ming-yih Liu; Jean LeGall; Lu-lu Gui; Jun Liao; Tao Jiang; Ji-ping Zhang; Dong-cai Liang; Wen-rui Chang (JBIC Journal of Biological Inorganic Chemistry, 2003)

GSTP1 polymorphisms and gastric cancer in a high-risk Chinese population - Veronica Wendy Setiawan; Zuo-Feng Zhang; Guo-Pei Yu; Qing-Yi Lu; Yong-Liang Li; Ming-Lan Lu; Ming-Rong Wang; Chun Hua Guo; Shun-Zhang Yu; Robert C Kurtz; Chung-Cheng Hsieh (Cancer Causes & Control, 2001)

Recovery of transgenic orchid plants with hygromycin selection by particle bombardment to protocorms - Zhihua Yu; Minyong Chen; Lin Nie; Huafei Lu; Xiaotian Ming; Honghong Zheng; Li-Jia Qu; Zhangliang Chen (Plant Cell, Tissue and Organ Culture (PCTOC), 1999)

Studies of the CAG repeat in the Machado-Joseph disease gene in Taiwan - Mingli Hsieh; Hui-Fang Tsai; Tsong-Ming Lu; Chien-Ying Yang; Hung-Ming Wu; S.-Y. Li (Human Genetics, 1997)